Geotechnical characteristics and mitigation strategies for loess subgrades in the Ili Valley, China - Yinuo Feng; Zheng Lu; Yang Zhao; Wanxin Mo; Zhihui Ze; Yuanbiao Li (European Journal of Environmental and Civil Engineering, 2026)

Deep vertical rotary tillage combined with biochar enhances rhizosphere soil aggregate stability in sugarcane fields by coupling pore structure and microbial communities - Tongdong Mo; Chengfan Yang; Daihua Jiang; Xuejiao Huang; Minghua Gu (Soil and Tillage Research, 2026)

L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Deguelin suppresses Nalm6 leukemia cell proliferation through lactate accumulation and ATP depletion - Xingyan Luo; Kaiyu Feng; Ketian Zhao; Ting Zhang; Juncheng Qiu; Huijie Guo; Yantang Wang; Shuxia Yang; Chunfen Mo; Yang Liu (Molecular Biology Reports, 2026)

Identification of novel loci regulating circulating melatonin and its causal relationship with hypertension - Lin Yan; Yang Qiu; Zhiwen Mo; Mingli Li; Xueran Huang; Yongfen Gao; Boteng Yan; Qiantu Hu; Haiying Zhang; Zengnan Mo; Rui Lin (Human Genetics, 2026)

Rapid visual detection of powdery mildew fungus Blumeria graminis in wheat via one-pot RPA-CRISPR/Cas12a assay - Jiangli Zhang; Lintao Sun; Yue Wang; Shuangjun Gong; Lijun Yang; Juncong Liu; Zhijian Zheng; Xiting Zhao; Mo Zhu; Jin Gao (Physiological and Molecular Plant Pathology, 2026)

Integrated lipidomic and transcriptomic analyses reveal stage-specific hepatic lipid remodeling during GCRV-II infection in grass carp (Ctenopharyngodon idella) - Minxuan Yang; Haibin Luo; Zhenyang Qiu; Yingying Wang; Yingying Li; Xubin Mo; Jiyuan Yin; Weiwei Zeng; Qing Wang; Shucheng Zheng (Fish & Shellfish Immunology, 2026)

Elucidating 6PPD-Q-induced metabolic reprogramming and systemic injury via ultrasensitive breathomics - Jiawei Dong; Bo Yang; Qirun Li; Zhen Li; Haiyan Wu; Mo Zhang; Meng Wang; Ting Lan; Zhongbing Lu; Liwei Cui; Yinwei Luo; Yi Yi; et al. (Environmental Pollution, 2026)

Identification of HsfA9 and a network of regulators involved in resistance to bacterial wilt under high temperature in tomato - Jing Li; Wenhao Zhong; Qiaoping Mo; Xiaoyu Qi; Juan Li; Hongling Yang; Jianghua Cai; Mengyun Xu; Guoping Wang (Plant Science, 2026)

Evolution of hydrochemical characteristics of shallow groundwater in the karst critical zone of Southwest China and its response to environmental changes - Mo Jinglin; Lyu Xiaoxi; Jiao Shulin; Cao Yang; Wang Dongnan; Zhu Chenyi (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Magnetic materials for micro- and nanoplastics capture, separation, and detection: Material design, working mechanisms, and key challenges - Kailan Yang; Zhenqing Dai; Rijian Mo; Ruikun Sun; Shiqi Jiang; Lei He; Liming Song; Chengyong Li (Journal of Environmental Chemical Engineering, 2026)

Effects of atmospheric cold plasma voltage on the interfacial properties of soy protein isolate-sodium alginate nanoemulsions co-loaded with curcumin and resveratrol and their application in surimi gels during chilled storage - Huiru Mo; Tingting Yang; Zhongyuan Liu; Guanghua Xia; Dawei Yu; Zhidong Liu; Yixiang Wang; Liming Zhang; Jiamei Wang (Food Research International, 2026)

Unveiling the toxicological burden of liquid crystal monomers: In vivo life parameter, oxidative stress, behavioral, and multixenobiotic resistance endpoints in the freshwater water flea Daphnia magna - Min-Jun Park; Haksoo Jeong; Yu Ri Jin; Jiezhang Mo; Lei Gu; Minghua Wang; Zhou Yang; Jae-Seong Lee; Jin-Sol Lee (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Entropy-defect synergy for dual luminescence mechanism in spinel: Time-resolved anti-counterfeiting and fingerprint visualization - Zemeng Pan; Shifa Wang; Jingyi Yang; Peilin Mo; Yanming Chen; Huajing Gao; Xianju Zhou; Dengfeng Li; Hua Yang; Huijun Zhang; Leiming Fang; Qingping Ding (Chemical Engineering Journal, 2026)

Autocatalytic DNA nanosphere assembly activated by endogenous APE1 for intracellular miR-21 imaging - Liuting Mo; Chunfen Zhang; Rongzheng Yuan; Yan Hong; Chan Yang; Weiying Lin (Analytica Chimica Acta, 2026)

Nanoscale interfacial scaffold enables perovskite/silicon tandems with 34% efficiency and an open-circuit voltage over 2.01 V - Huimin Zhang; Qingshui Zheng; Hongbo Mo; Fu Zhang; Zhijie Rao; Linyu Ning; Yue Yin; Dongsheng Yang; Zheng Fang; Lei Ding; Yongcai He; Xixiang Xu; et al. (Science Bulletin, 2026)

Precision agriculture meets explainable AI: A highly competitive ET0 prediction framework based on hybrid deep learning - Xianghui Xu; Qiang Fu; Yijia Wang; Wuyuan Liu; Jingkai Yang; Nan Wang; Mo Li (Computers and Electronics in Agriculture, 2026)

Synergistic integration of in situ generated Fe-S species and organohalide-respiring bacteria for complete dechlorination of carbon tetrachloride in groundwater - Boyu Jia; Rui Shen; Zhongdan Li; Yijun Mo; Yi Yang; Shanquan Wang (Water Research, 2026)

Associations of salinity and microplastics with microbial community assembly and functional potential in saline-alkali soils - Caidan Ding; Wen Hu; Xiuyuan Yang; Guanhai Mo; Linfeng He; Qiuxiao Yan; Zhenming Zhang (Journal of Hazardous Materials, 2026)

AI-2 type quorum-sensing signal enhances mercury resistance and adsorption in thermotolerant Bacillus subtilis - Shuo Han; Qianyun Mo; Xiaobin Wen; Xiangru Wang; Xiangqian Wang; Yao Yu; Yixiao Yang; Chunzhe Yang; Zhonghua Cai; Jin Zhou (Journal of Hazardous Materials, 2026)

Toxic effects and molecular mechanisms of Fluopyram on the liver of zebrafish (Danio rerio) - Yuqing Hou; Bo Cheng; Baihui Shi; Shuhan Li; Xuzhi Zhang; Lanjun Wang; Rui Yang; Lusheng Zhu; Jun Wang; Young Mo Kim; Jinhua Wang (Journal of Environmental Management, 2026)

A GA-XGBoost qualitative model for short-term rainfall forecasting based on GNSS PWV and meteorological parameters - Xu Yujing; Yu Hong; Zhang Jiajia; Liu Jizhou; Wang Shuaimin; Qiu Jiale; Mo Yanhan; Yang Hao (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Model compound study about catalytic Co-Pyrolysis of lignin and polyethylene by using online photoionization mass spectrometry and ReaxFF MD simulation - Zeyu Wu; Zhen Yang; Xinyue Zhao; Xi Gao; Yuan Xue; Mo Zheng; Liangyuan Jia; Zhongyue Zhou (Fuel, 2026)

Inhibition of protein-bound heterocyclic amines by citrus polymethoxyflavones via stabilizing myofibrillar protein conformation - Hui Xin; Diaodiao Yang; Shigang Liu; Lan Mo; Lei Zhou; Aihua Lou; Yan Liu; Qingwu Shen; Maomao Zeng; Jie Chen; Chaoyi Xue; Wei Quan; et al. (Food Chemistry, 2026)

Microeukaryotes are more vulnerable than picoeukaryotes to reservoir salinization: Evidence from multi-year high-frequency monitoring - Wanting Shi; Yuanyuan Mo; Hongteng Zhang; Erik Jeppesen; Xue Yan; Huihuang Chen; Haihan Zhang; Jun Yang (Environmental Research, 2026)

DSTs may affect the swimming ability of marine medaka by interfering with the neurotransmitter system and calcium signaling - Zi-min Chen; Mei-qi Li; Jing-xuan Jiang; Yan-hang Mo; Da-wei Li; Hong-ye Li; Wei-dong Yang (Environmental Pollution, 2026)

Breaking lignin barrier for co-producing hydrochar and crop salinity stress biostimulants - Fangfang Wu; Qianyi Deng; Wenqing Chen; Xueyi Zhong; Yanying He; Yixian Feng; Nijia Chen; Kai Qiu; Dingli Chen; Xueying Mo; Siyuan Chen; Long Chen; et al. (Chemical Engineering Journal, 2026)

Combined exposure to hypoxia and 17α-ethinylestradiol alters reproductive traits in marine medaka - Xian Qin; Jiezhang Mo; Huiju Lin; Yi Yang; Emily Sze Wan Wong; Min Pan; Sidney Man Ngai Chan; Rudolf Shiu Sun Wu; William Ka Fai Tse; Keng Po Lai (Aquatic Toxicology, 2026)

Effect of phosphate concentration on resistance of Pyropia yezoensis (Bangiales, Rhodophyta) to red rot disease (Pythium porphyrae) - Congcong Sun; Huichao Yang; Yongwei Yan; Zhaolan Mo; Yunxiang Mao; Jie Li (Journal of Applied Phycology, 2026)

Coral–Symbiodiniaceae holobiont responses to acute and chronic temperature stress in a marginal reef of the South China Sea - Qizhi Yang; Zhenjun Qin; Shuchang Chen; Lifei Wei; Mengling Lan; Changhao Mo; Wenzhi Deng; Yuan Xue; Jiming Jie (Coral Reefs, 2026)

From project-based mobilization to fragile stewardship: Governance configurations and sustainability trajectories of urban community gardens - Pingyang LIU; Yang MO (Urban Forestry & Urban Greening, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Retraction notice to “Spatio-temporal microbial regulation of aggregate-associated priming effects under contrasting tillage practices” [Sci. Total Environ. 925 (2024) 171564] - Yeye Zhang; Yunfei Ren; Shenglin Zhou; Xiaoyu Ning; Xiukang Wang; Yanming Yang; Shikun Sun; Nangia Vinay; Michael Bahn; Juan Han; Yang Liu; Youcai Xiong; et al. (Science of The Total Environment, 2026)

A tolerogenic mRNA-LNP vaccine alleviates neuroinflammation and demyelination in experimental autoimmune encephalomyelitis - Yi Song; Zhangchi Dongye; Jiaxi Yao; Xiaonan Zhao; Tao Mo; Shiyu Yang; Cong Sun; Tingting Zhao; Jian Li; Yuzhang Wu (Science Bulletin, 2026)

Synergistic depression of chalcopyrite by Fe(II) and Na2S in Chalcopyrite-Molybdenite separation: Mechanism investgation and industrial validation - Zhian Liang; Langfeng Tang; Zhenpeng Han; Tao Yue; Songtao Yang; Qiankun Wang; Zhenjun Mo; Haixiang Wu; Zhuanhua Wei; Yan Miao; Luzheng Chen (Minerals Engineering, 2026)

In-situ self-assembled integrated capture-detection platform based on cuttlebone-derived organic matrix for sensitive SERS quantification of polystyrene nanoplastics - Yuping Lai; Zhenqing Dai; Kailan Yang; Rijian Mo; Ruikun Sun; Shiqi Jiang; Lei He; Jingya Zhou; Aminmuhammad Usman; Chengyong Li (Journal of Hazardous Materials, 2026)

A land–sea coupled framework for revealing hierarchical drivers of mangrove dynamics - Minduan Xu; Xuan Zhang; Yang Liu; Zewen Mo; Qingling Zhang (Journal of Environmental Management, 2026)

Benzophenone-type UV filters in aquatic ecosystems: Sources, toxicological impacts, and interactions with coexisting stressors - Yu Ri Jin; Mi-Song Hong; Jin-Sol Lee; Jiezhang Mo; Piotr Maszczyk; Menghong Hu; Youji Wang; Zhou Yang; Minghua Wang; Da-Zhi Wang; Min-Chul Lee; Jae-Seong Lee (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Eccentric coaxial wet-spun magnetic composite actuators with decoupled magneto-pneumatic shape-morphing for biomedical applications - Ping-an Yang; Yixuan Han; Chunyan Mo; Mengjie Shou; Rui Li; Yi Lu; Decheng Wu; Qiao Chen; Zhiwei Huang (Chemical Engineering Journal, 2026)

A multifunctional interphase strategy to repel solvent molecules for stabilizing interfacial chemistry - Jinrui Liu; Xin Hu; Shu-Shen Lyu; Zongtao Qu; Yang Sun; Dong-Chuan Mo (Chemical Engineering Journal, 2026)

Multi-omics analysis of LFA-1 peptide-functionalized silk fibroin nanofibers targeting RPE and activating AMPK–HO-1 signaling to suppress pyroptosis and alleviate diabetic retinopathy progression - Zepeng Xu; Chenxiao Lu; Zhenting Wang; Yaojia Liu; Guangmeng Mo; Yan Yang; Xiaoli Lu; Kunmeng Li; Yihuan Zeng; Yan Dong; Ni Tian (Chemical Engineering Journal, 2026)

Integrated recovery and microplastic adsorption of spent lithium iron phosphate batteries: Ascorbic acid stripping-persulfate activation synergistic strategy - Yang Yang; Zhaodi Lan; Yang Dai; Xing Yang; Yu Fang; Mo Liu; Zhen Yao (Chemical Engineering Journal, 2026)

Health risk assessment-based indoor VOC thresholds for newly renovated environments in Chongqing, China: The necessity for stricter standards - Bo Liang; Teng Yun; Yang Song; Liang Wang; Zhaoxu Zhou; Hongbo Mo; Mi Tian (Atmospheric Pollution Research, 2026)

Compound microbial-composite carrier inoculant boosts sugarcane growth and reshapes rhizosphere bacterial community assembly - Dangsheng Pang; Tingting Yang; Jie Mo; Changju Liang; Changning Li; Yangrui Li; Dengfeng Dong; Yongxiu Xing (Applied Soil Ecology, 2026)

Fine-scale soil heterogeneity shapes compartment-specific microbial assembly and soil microbial functional differentiation in Lepturus repens on a coral island - Shengen Zhong; Shunfen Wang; Yimin He; Kaiwen Yang; Yuhang Wen; Ziyang Zhang; Mo Shi; Liaoyuan Zhang; Wenxiong Lin; Xin Qian (Plant and Soil, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

The quantitative assessment of stormwater regulation services under urbanized landscape pattern employed SCS model in the whole Nanning, China - Yunchuan Yang; Minhui Feng; Guangqiong Bi; Liping Liao; Jiaoyin Wei; Yaqian Tang; Yuhong Huang; Chongxun Mo; Guikai Sun; Xungui Li (Environment, Development and Sustainability, 2026)

Association between amygdala subregions and non-motor symptoms in Parkinson’s disease: a fixel-based analysis - Yuchen She; Jiahao Wei; Junyi Wang; Ying Liu; Sicheng Chen; Man Zhang; Qi Yang; Lijuan Mo; Changhong Tan; Xi Liu; Lifen Chen (Brain Imaging and Behavior, 2026)

UFL1-mediated UFMylation stabilizes ABI5 to strengthen ABA-dependent seed dormancy in Arabidopsis - Mengrui Wen; Ruihua Huang; Zixuan Ma; Huizi Huang; Jianhai Mo; Yifeng Yang; Minghui Liu; Zhengxi Wu; Yuxi Liao; Yixian Zeng; Miaolun Yuan; Qiuchan Lu; et al. (Molecular Plant, 2026)

Vpa1463, a DUF1566-domain protein, is indispensable for bile resistance and biofilm formation in Vibrio parahaemolyticus and is required for its adaptation to food-related environments - Min Chu; Jingli Li; Yu Sun; Xuehu Liu; Qiufen Mo; Yanming Ren; Yan Wang; Menghua Yang; Guangzhi Xu; Qinxue Ni (Food Research International, 2026)

Solid dispersion of co-amorphous Phloretin–Trilobatin in Erythritol: A multifunctional premix for enhanced solubility and synergistic glycolipid regulation - QiuruTan; Zhizhong Yang; Yuxia Mo; Tong Zhang; Jiao Wang; Xia Luo; Lingyun Chen; Yanni Ma; Wenping Wang (Food Chemistry, 2026)

Shake table tests of a full-scale stacked modular steel structure based on three-dimensional seismic isolation - Ze Mo; Ganping Shu; T.Y. Yang; Bin Wang; Binglin Lai (Engineering Structures, 2026)

Penguin-inspired Antarctic research station design strategies: Integrating proximal policy optimization with bio-inspiredheat-conservation strategies - Jiyuan Wu; Mo Yang; Wen Yang; Wei Wang (Energy and Buildings, 2026)

Phenolized lignin binders inducing ultrathin SEI of hard carbon for advanced sodium storage - Jinxing Li; Zhipeng Qiu; Fangbao Fu; Weifeng Liu; Jianbin Mo; Dongjie Yang; Xueqing Qiu (Chemical Engineering Journal, 2026)

Monitoring surface deformation caused by fluvial-aeolian interaction and its contribution to aeolian process in a small watershed of the Gonghe Basin, northeastern Tibetan Plateau - Na Gao; Guangyin Hu; Linhai Yang; Jingjing Hu; Haokun Mo; Jie Gao; Fengjun Xiao; Zhibao Dong (CATENA, 2026)

Cortical hemodynamic responses during action observation with and without audiovisual stimuli: a randomized controlled experimental trial - Yoon-Mo Yang; Ju-Hyung Park (Experimental Brain Research, 2026)

A Novel Cyclopentane Pyridine Compound Identified from Saccharothrix syringae NRRL B-16468 by PPTase-Based Activation - Yuxing Bi; Xu Han; Guihong Yu; Yueliang Yao; Song Yang; Xuhua Mo (Current Microbiology, 2026)

Subsurface soil as a hotspot for iron-bound organic carbon loss driven by moisture and microorganisms during seasonal freeze-thaw period - Yuxin Tian; Maidinuer Abulaizi; Zailei Yang; Tianle Kou; Yuanbin Jia; YunPeng Hu; Mo Chen; Hongtao Jia (Applied Soil Ecology, 2026)

Mixture of Experts neural network for calculation of gamma-ray buildup factors - Zihui Yang; Yihang Sun; Heng Zhang; Chong Chen; Ziwen Mo; Zhixing Gu; Taosheng Li; Jie Yu (Annals of Nuclear Energy, 2026)

Highly sensitive H2O2 colorimetric sensing in tumor cells via stable phospholipid-coated CsCu2I3 peroxidase-like nanoenzyme - Jiatong Wang; Yang Yu; Yawen Fan; Sihan Chen; Meiyi Mo; Shuo Yang; Yangyang Zhao; Zixu Zhang; Hongxian Han (Analytica Chimica Acta, 2026)

Physiological and transcriptomic responses of Synechococcus sp. FACHB-805 to phosphite under phosphate limitation - Ye Zheng; Xingyao Ye; Xiaojun Niu; Dongqing Zhang; Mo Wang; Yang Yu; Ling Li; Chen Wang; Xiufang Yang; Xintai Su (Algal Research, 2026)

RNA regulation in plants - Yijun Qi; Yueqin Chen; Hongwei Guo; Huishan Guo; Runlai Hang; Guifang Jia; Yan Li; Beixin Mo; Zhen Wang; Liang Wu; Yiji Xia; Xiaofei Yang; et al. (Science China Life Sciences, 2026)

CT-Based Pore Network Characterization of Coral Reef Rudstone and Its Correlation with Physico-Mechanical Properties - Yongtao Zhang; Haifeng Liu; Yang Mo; Peishuai Chen; Fuquan Ji; Ran Gao (Journal of Marine Science and Engineering, 2026)
Coral reef rudstone (CRR) exhibits distinctive fabric-controlled mechanical behavior that is strongly influenced by its internal pore structure and degree of diagenesis. This study combines petrographic observation, X-ray CT scanning, and saturated uniaxial compressive strength test to quantify the pore network characteristics and physico-mechanical properties of CRR. Three representative specimens were reconstructed in three dimensions and analyzed in terms of pore number, pore volume, throat length, and coordination number. The results show that CRR contains moderately developed pores dominated by micritic-calcite dissolution pores. Average pore radius ranges from 141.2 to 993.6 μm, the maximum pore radius reaches 5567.2 μm, and the throats are mainly short-range, with average lengths of 3705–5437 μm. Connectivity varies markedly among specimens: CRR-C contains an interconnected macropore cluster, whereas CRR-A and CRR-B are dominated by weakly connected mesopores. Dry density shows a strong nonlinear positive correlation with saturated uniaxial compressive strength, whereas porosity shows a negative correlation. Both variables demonstrate a preliminary exponential relationship with strength and are crucial factors in determining the mechanical response of CRR.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Streptochlorin from Streptomyces youssoufiensis YMF3.862 as a potential ecological fungicide for controlling Fusarium head blight on wheat - Min Chen; Chen-Xin Ma; Madjiengui Grace Dieuveille; Xiu-Min Zhang; Lu Wang; Li Ma; Yi Cao; Zi-Xiang Yang; Pei-Ji Zhao; Ming-He Mo (Pesticide Biochemistry and Physiology, 2026)

A hybrid method coupling physical process-driven model with generative deep learning for probabilistic flood forecasting - Xuesong Yang; Bin Xu; Jingwen Liu; Junliang Jin; Ran Mo; Xinrong Wang; Zichen Ren; Yao Liu; Yuchen Shi; Qisheng Zhou; Ping-an Zhong (Journal of Hydrology, 2026)

Cadmium-induced stress memory regulates Bacillus subtilis transport in porous media: Evidence from multi-scale analysis - Yijun Mo; Jialin Huang; Zihan Xiao; Miaoyue Zhang; Bo Wu; Xiaofan Yang; Meng Zhang; Jean Louis Morel; Stéphanie Ouvrard; Chao Jin; Rongliang Qiu (Journal of Hazardous Materials, 2026)

Enzymatic properties and catalytic mechanism of a novel pyraclostrobin C–N bond-hydrolyzing carboxylesterase from Priestia megaterium GXU087 - Xiaotian Cao; Jingsi Qiu; Jingxia Yang; Xiaoyun Liu; Hongxuan Mo; Tao Huang; Yanmei Liu; Huihua Tan (Journal of Hazardous Materials, 2026)

Ultrafast degradation of mineral processing collector via magnetic Fe3O4/graphene oxide activating peroxydisulfate: Performance and mechanism - Zequan Lin; Wei Mo; Yuxin Feng; Junjie Wu; Xiujuan Su; Jinlin Yang; Yuhua Huang; Jinpeng Feng; Shaojian Ma (Journal of Environmental Chemical Engineering, 2026)

A Ca-MOF@COF composite and its in situ grown gel membrane for highly efficient capture of Cd2+ - Xue-Mei Liu; Chuang-Chuang Zhang; Kun Yang; Wei-Liang Jin; Guan-Lian Mo; Rui Liu; Hong-Xin Jiang; Hao-Jie Cui; De-Ming Kong (Journal of Cleaner Production, 2026)

Decadal progress and provincial disparities: How did China's WEEE recycling fund policy refine regional resource-environmental performance? - Diya Wang; Bingyu Xu; Zhuo Yang; Xibing Wang; Mo Zhang (Journal of Cleaner Production, 2026)

Selective lithium recovery from spent NCM cathodes via starch-assisted roasting - Jianghong Xu; Mo Liu; Zhen Yao; Yang Dai; Yu Fang; Wei Liu; Wei Gong (Journal of Environmental Management, 2026)

A carboxymethyl cellulose-based hydrogel sensor that can monitor surface compressive force and blue light-activated antibacterial properties in real time, used for preserving loquats - Yuluo Zheng; Qi Mo; Xuyang Lu; Jianming Lin; Jiaxin Cai; Shuang Tian; Yingying Yang; Zehao Huang; Chongxing Huang; Lijie Huang (Food Control, 2026)

Zein-based films with γ-cyclodextrin metal organic framework/oregano essential oil for fruit preservation - Zhenbin Liu; Fengbing Yang; Liangbin Hu; Dan Xu; Guoqiang Zhang; Yumei Liao; Min Cui; Hongbo Li; Haizhen Mo (Food Packaging and Shelf Life, 2026)

Recombinant fusion subunit vaccine provides enhanced immune protection against Cryptocaryon irritans infection in grouper - Huicheng Wu; Zhengli Wei; Li Yang; Yihao Cen; Yanwei Li; Xueming Dan; Zequan Mo (Fish & Shellfish Immunology, 2026)

Atomic condensation of Na and K vapor followed by oxidation in lunar impact glass beads revealed by Chang’E-6 - Ming-Yang Li; Ying-Kui Xu; Dan Zhu; De-Liang Wang; Yi-Cao Zhou; Bing Mo; Shi-Jie Li; Yang Li; Xiong-Yao Li; Jian-Zhong Liu; Wei Du; Yun Liu (Earth and Planetary Science Letters, 2026)

Click bubbles-driven enzyme-linked immunosorbent assay for enhanced biomarkers detection - Weifeng Liu; Xifeng Mo; Binqi Wei; Yuyuan Zhang; Yuanhang Xiang; Hao Lu; Haichao Li; Xiaojie Qin; Zhanyu Xu; Jie Yang; Fan Yang (Chemical Engineering Journal, 2026)

ZnO nanoparticles enhance vernalized rapeseed yield under cadmium stress by boosting photosynthesis and antioxidant response while reducing cadmium accumulation - Zhe Jiang; Xuechan Zhang; Xiangbin Yao; Hong Yang; Wentao Yi; Zhaowen Mo; Xiangru Tang (Plant Cell Reports, 2026)

Bone transport accelerates diabetic foot ulcer healing via TGF-β1–mediated angiogenic and osteo-immune coupling - Yan Chen; Xiajie Huang; Chaoquan Yang; Xiaomei Wu; Ying Li; Yingrong Liao; Xinyun Liang; Yangzhou Mo; Caiyun Xie; Yicheng Liang; Haidong Chen; William Lu (Journal of Molecular Histology, 2026)

Phenological divergence in the rice stem borer correlates with rice domestication - Meng Wang; Xiurou Mo; Xinting Qiu; Shiqing Yuan; Yue Liu; Xichen Xiao; Meijuan Yang; Yongmo Wang (Evolutionary Ecology, 2026)

Interactive effects of forest succession and seasonal hydrology on heavy metal accumulation and ecological risk in subtropical forest soils - Wyckliffe Ayoma Ochieng; Brian Mwangi Njoroge; Vincent Ochieng Suba; Hui Mo; Emily Achieng Oluoch; Sohel Rana; Okechukwu Uzoma Iheme; Mengmeng Yang; Ekpoanwan Alfred Bassey; Ayesha Akter; Guowei Chu; Yuelin Li (Environmental Geochemistry and Health, 2026)

Environmental risk assessment of heavy metal and PAH contamination at Kalasin e-waste dumpsite and screening of native hyperaccumulators - Prayad Pokethitiyook; Pinida Joradon; Toemthip Poolpak; Maleeya Kruatrachue; Kwang Mo Yang (Environmental Geochemistry and Health, 2026)

Microbial and abiotic oxidation of phosphite (P(III)) in aquatic environments: pathways, controls, and ecosystem implications - Ye Zheng; Chen Wang; Dongqing Zhang; Xiaojun Niu; Ling Li; Mo Wang; Zhihong Zhang; Yang Yu; Yuhao Zhang; Cuiting Su; Jianeng Chen; Xingyao Ye (Reviews in Environmental Science and Bio/Technology, 2026)

Cadmium causes osteoporosis by osteogenic differentiation inhibition via miR-155/SMAD5 pathway: evidence from in vivo and in vitro studies - Lifen Mo; Lijun Mo; Youkun Hu; Siyu Wan; Meng Zhou; Wei Zhu; Guangyu Yang; Qinzhi Wei; Jia Song; Xingfen Yang (Archives of Toxicology, 2026)

Identification of Mitochondrial Dysfunction Genes as Diagnostic Biomarkers for Ischemic Stroke by Integrated Bioinformatics Analysis and Machine Learning - Dandan Wu; Xiaolan Huang; Jie Li; Dingmin Mo; Weiwei Lan; Zihan Song; Li Su; Jianxiong Long; Jialei Yang (Journal of Molecular Neuroscience, 2026)

Attenuation of antibiotics and endocrine disruptors flux along the Land-To-Sea continuum: Dominant role of terrestrial ecosystems and remediation potential of salt marsh ecosystems - Zi-Long Mo; Yi-Qin Chen; Yang Yu; Ling-Kan Su; Juan-Ying Li (Marine Pollution Bulletin, 2026)

Analysis of the removal process of residual tetrachloroethylene from simulated aquifer by a novel anionic-nonionic gemini surfactant - Xue Liang; Liyu Yang; Jun Dong; Chaoge Yang; Yanyang Mo; Jing Su (Water Research, 2026)

Toxicological effects of PM2.5-derived and PM2.5-relevant mixture of chlorinated paraffins on A549/THP-1 co-culture cells - Jing-Wen Huang; Chu Chu; Mo Yang; Henri Hakkarainen; Anna-Katharina Hensel; Nan-Xiang Jin; Marjut Roponen; Ari Leskinen; Mika Komppula; Dong Liang; Guang-Hui Dong; Pasi Jalava (Toxicology, 2026)

Relative quantitative data of cosmetics consumption: An online survey in Guangzhou, China - Junfeng Deng; Zhen Wu; Xiaodan Lu; Xiaoyu Xian; Shixiong Zheng; Yunying Mo; Tianyang Liu; Siyu Sun; Shihan Huang; Ye Hong; Xingyu Yu; Aliya Yijiati; et al. (Regulatory Toxicology and Pharmacology, 2026)

Single-cell and spatial transcriptomics identify PGK1-sensitized hypoxia macrophages as a therapeutic target to overcome PDT resistance in glioma - Xiuwei Yan; Jiahe Hu; Xuyan Han; Lei Xu; Lihui Zhou; Jiaoyan He; Fei Yang; Longgang Zhou; Yapeng Niu; Mo Geng; Wenjie Yuan; Dong Zhao; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Moisture limitation and nocturnal insulation underpin heatwave diversity in hydroclimatic transitional zones - Ruikun Gou; Xuechun Wang; Lin Zhu; Siyuan Zhu; Yanzheng Yang; Lidong Mo (Journal of Arid Environments, 2026)

Ultrasound-induced modifications of fish proteins: a comprehensive review of structural, physicochemical, functional properties, and industrial applications - Qingzhi Ding; R.A. Dilmi Anuththara Ranasinghe; Zijie Mo; Huamin Yang; Lin Luo; Haile Ma; Xiaoran Li; Chunhua Dai; Ting Zhang (Food Research International, 2026)

Synergistic modification of β-casein micelles by dextran and genipin for naringenin delivery: A systematic evaluation of physicochemical stability, digestive properities, and cellular uptake - Jingying Ye; Fan Wu; Boran Yang; Zhaoyue Zhang; Xin Wen; Yuanying Ni; Mo Li (Food Bioscience, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Upregulation of m6A writer WTAP by histone lactylation promotes inflammatory response via TLR2 in neutrophils - Bailu Du; Wenting Song; Yiming Zhang; Yan Yin; Yuanjie Zhou; Yi Pan; Ruwen Yang; Muxiu Jiang; Nan Shen; Qihua Fu; Jianye Zang; Yue Tao; et al. (Science China Life Sciences, 2026)

Identifying Salt-tolerant Andrographis paniculata Germplasms: A Comparative Study - Yan-hua Shao; Ye Liu; Xun-lang Jian; Shi-lun Mo; Quan Yang; Ming Li (Journal of Plant Growth Regulation, 2026)

Sorption and degradation of α-terpineol in soils with distinct physicochemical properties - Huan-Feng Chen; Zi-Jun Yang; Hai-Rong Chen; Hai-Ming Zhao; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Lei Xiang (Environmental Geochemistry and Health, 2026)

A novel TaqMan-based RT-qPCR assay for the detection of PEDV and discrimination of the G2c subtype - Yicong Fan; Xiang Li; Jiawen Mo; Liang Weng; Shiyu Liu; Xu Song; Rongli Guo; Wei Wang; Mi Hu; Shanshan Yang; Yongxiang Zhao; Baochao Fan; et al. (Archives of Virology, 2026)

Systematic Identification, Characterization, and Expression Analysis of Genes Encoding C2H2-Type Zinc Finger Proteins in Rice Associated with Anilofos and Bentazone Metabolism - Ying Yu Zeng; Zhi Zhong Zhou; Yang Yang Mo; Li Qing Zeng; Xiao Lu Wang; Zhi Jiang He; Lan Xin Huang; Dan Lu; Zhao Jie Chen (Tropical Plant Biology, 2026)

Effects of dietary emodin supplementation on the growth performance, serum biochemical parameters, and intestinal health of Pengze crucian carp (Carassius auratus var. Pengze) fed with high plant-protein diets - Jingen Xu; Song Zhang; Kaikai Shen; Jingjie Zhang; Luyao Xu; Shiqiang Du; Jianqin Li; Chungen Wen; Vikas Kumar; Mo Peng; Gang Yang (Frontiers in Marine Science, 2026)
Emodin supplementation could relieve the adverse impacts induced by a high plant-protein diet on intestinal health and growth performance of fish, while its application in Pengze crucian carp ( Carassius auratus var. Pengze) is lacking. Pengze crucian carp, an omnivorous fish, belongs to the freshwater Cyprinidae family. In this study, Pengze crucian carp were fed with a normal fishmeal diet (18% fishmeal, FM), a high plant-protein diet (4% fishmeal, HP), and four different emodin supplementation diets (HP diet supplemented with 25, 50, 75, and 100 mg kg −1 emodin); the feeding trial lasted 8 weeks. Compared with the FM group, the HP diet dramatically inhibited the growth performance of carp, while an appropriate addition of emodin could restore its growth performance. Emodin could improve carp morphology in terms of a higher value of the hepatosomatic index (HSI), the viserosomatic index (VSI), and the condition factor (CF), and increase the crude protein content concurrent with a lower crude lipid content in body compared with HP and FM groups. The HP diet induced the oxidative stress of carp, whereas emodin supplementation enhanced antioxidant parameters in serum and intestinal tissues together with a remarkable reduction of malondialdehyde content, thereby improving antioxidant status. The antioxidant property of emodin triggered the keap1-nrf2 signal pathway and then induced the overexpression of antioxidant genes ( cuznsod, cat , and gpx ) in intestinal tissue. Additionally, emodin attenuated the intestinal inflammation induced by the HP diet by suppressing the expression of pro-inflammatory-related factors ( tlr4, myd88, tnf-α, il-1β , and ifn-γ ) and upregulating anti-inflammatory-related factors ( tlr2, tgf-β , and il-10 ), followed by an improvement of the intestinal barrier function. Moreover, emodin supplementation could induce the transcriptional level of intestinal alkaline phosphatase ( iap ) through the pparγ-klf4 signal pathway and enhance IAP activity ultimately. In summary, a suitable amount of emodin can elevate the growth performance and improve the intestinal health of Pengze crucian carp fed a high plant-protein diet.

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Optimisation of ultrafine particle exposure in an alveolar tri-culture model at the air-liquid interface - Anna-Katharina Hensel; Henri Hakkarainen; Mo Yang; Jingwen Huang; Laura Mussalo; Claire Fayad; Katja Kanninen; Pasi Jalava (Toxicology in Vitro, 2026)

Simulation of flood processes under extreme precipitation scenarios based on an improved HEC-HMS model in a typical karst mountainous basin, southwest China - Chongxun Mo; Na Li; Keke Huang; Qizhong Liu; Qing Yang; Xingbi Lei; Jing Lu (Journal of Hydrology, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Machine learning-coupled multi-elemental fingerprinting for high-accuracy source identification of distillation residues: A novel strategy for industrial waste traceability - Yiqing Sun; Qingwei Guo; Xiubao Wang; Jianwei Yue; Xiaocheng Song; Siyuan Yang; Wei Liu; Ling Mo; Li-Cheng Wang; Lingshuai Kong; Jinhua Zhan; Zhenhui Gao (Journal of Hazardous Materials, 2026)

Silver-doped ZnMn bimetallic oxide nanostructures for enhanced photocatalytic degradation of iron(III) cyanide complexes (Fe-CNs) cyanide complexes via synergistic effects of plasmonic activation and dual-metal redox catalysis - Jing Feng; Jingyu He; Anyang Huang; Jinpeng Feng; Wei Mo; Xiujuan Su; Jinlin Yang; Dingzheng Wang; Wenhan Sun; Shaojian Ma (Journal of Environmental Chemical Engineering, 2026)

The combined exposure exacerbates the toxic effect of cadmium and uranium on rice seedlings - Jun Liu; Meihan Cai; Jiajie Zhang; Aili Mo; Shiyu Hu; Peishuang He; Menglei Jiang; Wei Zhao; Cuiying Peng; Tangjian Peng; Fei Yang (Journal of Environmental Sciences, 2026)

Occurrence, landscape impact, and risk assessments of pesticides in a major river basin of a tropical island, South China - Ling Mo; Bin Tang; Li-Ke Chen; Jun Xiang; Ming-Yang Wang; Kai-Yi Wu; Ming-Zhong Ren; Qiao Xing; Li-Cheng Wang; Jing Zheng (Environmental Pollution, 2026)

Detecting support modulus of curved railway tracks by a double-beam model using a moving test carriage - Y.B. Yang; H.J. Chen; K. Shi; X.Q. Mo (Engineering Structures, 2026)

The Spatiotemporal Evolution of Sugarcane Growth Based on Remote Sensing Monitoring and its Influence Factors Detection Regression Analysis in Guangxi, China - Yun-chuan Yang; Chang-zheng Wei; Xin-chang Xie; Li-ping Liao; Li-qing Liang; Zong-heng Li; Meng-dong He; Chong-xun Mo; Xun-gui Li; Gui-kai Sun (Sugar Tech, 2026)

Paeoniflorigenone inhibits the progression of cholangiocarcinoma via HIF1A and enhances the chemotherapy sensitivity of cisplatin - Qing Hu; Mengqin Xiang; Feicheng Yang; Wei Guo; Mengjun Mo; Zhou Yang; Yanchun Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Morphology-dependent biotoxic effects and cellular damage mechanisms of silver nanoparticles on Chlorella vulgaris and Scenedesmus obliquus - Wei Yu; Yongchang Shang; Zhenyu Wang; Yue Yang; Chenxi Zhang; Ningcan Deng; Kaixuan Wang; Ting Ma; Xiuzhen Yang; Miao Xu; Fan Mo; Haibo Li (Algal Research, 2026)

NSUN3-Mediated ROS Accumulation Promotes Hepatocellular Carcinoma Proliferation and Activates PI3K/AKT Pathway - Haodong Liu; Shijie Liang; Chunting Peng; Jiawei Yang; Zheng Yang; Wuning Mo (Biochemical Genetics, 2026)

Effects of spatial distribution of slope erosion-deposition on soil quality degradation in the Mollisol region of Northeast China - Xuesong Wang; Fenli Zheng; Rui Liang; Xinyue Yang; Shuaihao Mo; Xiaobing An (Soil and Tillage Research, 2026)

Amorphous Fe–Al binary hydroxides for enhanced Arsenic removal: Mechanistic role of stoichiometry and synergistic adsorption - Maulidiah Nani Lailil Islahah; Wei Mo; Yang Yang; Shaojian Ma; Jinlin Yang; Jinpeng Feng; Xiujuan Su (Process Safety and Environmental Protection, 2026)

Global governance priorities derived from SDG spatiotemporal dynamics and causal interactions - Yizhong Huan; Linjiang Ji; Yiming Su; Feng Kong; Yang Lan; Zhaohui Feng; Siyu Wang; Tao Liang; Mingyuan Wang; Pengpeng Mo; Jian Hu; Lingqing Wang; et al. (Gondwana Research, 2026)

Enhancing climate resilience of global dryland maize to cope with future 50-year climate warming - Jing Wang; Bao-Zhong Wang; Fei Mo; Yinglong Chen; Mohammad Ashraf; Yang Wang; Jian-Ming Li; Hai-Xia Duan; Yajie Song; Levis Kavagi; Hong-Yan Tao; You-Cai Xiong (Global Environmental Change, 2026)

An integrated “extraction-film formation” strategy using natural deep eutectic solvents for fabricating active films in fruit preservation - Haiyu Yang; Xinghai Huang; Bingyou Luo; Kunying Yu; Chaosong Lu; Jingmin Mo; Peiyuan Li; Jianhua Wei; Haiyi Zhong (Food Packaging and Shelf Life, 2026)

Carbapenem-resistant Klebsiella pneumoniae exacerbates virulence through oxidative stress, apoptosis induction and gut microbiota dysbiosis in zebrafish models - Zhining Mo; Jiajie Liu; Yunhong Yi; Mei Li; Xiaosong Yang; Gongqing Wu (Fish & Shellfish Immunology, 2026)

Coral mucus input promotes sedimentary organic matter degradation: Evidence from a typical coral reef area, northern South China Sea - Bo Yang; Bin Yang; Lei Xie; Zhenjun Kang; Xiaorong Mo; Qin Li; Jiaodi Zhou; Haifang Huang; Tingting Yan; Cheng Xu (Environmental Research, 2026)

Development of CAIX-targeted radioligand theranostic pairs for clear cell renal cell carcinoma - Yang Liu; Chunwei Mo; Ye Dong; Peipei Tang; Hongxin Li; Zexin Xu; Yongsheng Zhao; Haibo Chen; Kongzhen Hu (Chemical Engineering Journal, 2026)

Reprogramming lipid metabolism and morphology engineering in Yarrowia lipolytica for algae-free, high-titer production of esterified astaxanthin - Mo-Han Zhu; Hong-Ze Zhou; Zhijie Liu; Hong Zhu; Jun Chen; Chen Yang; Feng Liu; Qiang Hua (Chemical Engineering Journal, 2026)

Long-term study shows cyanobacterial blooms reduce ciliate functional stability by altering network complexity - Mamun Abdullah Al; Zijie Xu; Jun Zuo; Peng Xiao; Yuanyuan Xue; Shuzhen Li; Xue Yan; Yuanyuan Mo; Qingyun Yan; Henglong Xu; Markus Majaneva; Erik Jeppesen; et al. (Algal Research, 2026)

Water regime management reduces pest infestations and cadmium content in rice in paddy ecosystems - Yanlin Huang; Dexin Wei; Guizhen Mo; Qixian Fu; Di Yang; Jinlian Liang; Yuhui Peng; Yanyan Wei; Bing He; Minghua Gu; Xueli Wang (Agriculture, Ecosystems & Environment, 2026)

Synergistic optimization of field management measures for yield increase and emission reduction of Panax notoginseng based on DNDC model and NSGA-III - Qiliang Yang; Liuhui Mo; Wentao Zhang; Ling Yang; Chunhao Cao; Na Li (Agricultural Systems, 2026)

Impacts of precipitation variability on water quality in the Nakdong River Estuary: multi-year (2016–2021) data analysis - Hoon Mo Koo; Inho Yang; Jinsoon Park; Yong-Woo Lee; Yong Hwa Oh (Frontiers in Marine Science, 2026)
Physicochemical and biological parameters (temperature, salinity, pH, dissolved inorganic nutrients, and chlorophyll-a) were analyzed to evaluate the effects of precipitation variability associated with climate change on the water quality in the Nakdong River Estuary, South Korea. Multi-year monitoring data (2016–2021) were collected seasonally (February, May, August, and November) throughout the study period. Extreme rainfall events caused pronounced estuarine freshening (salinity < 1) and sharply enhanced riverine nutrient fluxes, with wet-to-dry season increases of 4–70 times for dissolved inorganic nitrogen, 4–36 times for phosphorus, and 9–740 times for silicate, showing strong positive correlations with precipitation (r² = 0.76–0.82, p < 0.001). Time-series and self-organizing map classifications revealed estuarine that the water quality was strongly controlled by seasonal precipitation and river discharge, whereas offshore waters exhibited weaker but detectable responses. Notably, extreme rainfall events altered the chlorophyll-a distribution, suppressing phytoplankton accumulation in the estuary because of dilution and flushing, while enhancing chlorophyll-a concentrations in offshore waters through nutrient-enriched river plume dispersion. These results demonstrated that extreme rainfall driven by climate change can enhance the terrestrial nutrient input into coastal waters, thereby increasing the potential for eutrophication and harmful algal blooms.

Effects of mulch drip irrigation on the coupled heat-Fe drive in root zone soils and analysis of soil Cr(Ⅵ) remediation mechanism - Mingxuan Liu; Qiang Fu; Tianxiao Li; Renjie Hou; Xiangyu Wang; Ping Xue; Xuechen Yang; Mo Li; Dong Liu; Fanying Kong (Soil and Tillage Research, 2026)

Modulation of the nanoscale chimney effect in metal–organic frameworks enables efficient guest diffusion and separation - Sha-Sha Meng; Hanxi Guan; Han Yang; Hai-Yue Wei; Mo-Han Gu; Jian Zhang; Ming Xu; Lina Wu; Zhi-Yuan Gu (Science Bulletin, 2026)

Multi-scale complementarity and integrated optimization analysis of a wind-PV-CSP hybrid system for off-grid hydrogen production - Huairong Zhou; Aoxue Guo; Dongliang Wang; Yong Yang; Siyu Yang; Wenlong Mo (Journal of Environmental Chemical Engineering, 2026)

Effectiveness of humic-acid-based composite amendments in mitigating soil cracking and erosion in cold black soil regions under climate variability - Xu Leng; Qiang Fu; Tianxiao Li; Di Wu; Xuechen Yang; Zhaoxing Xiao; Mo Li; Renjie Hou (Journal of Environmental Management, 2026)

Bisphenol exposure during pregnancy and serum total bile acid levels across trimesters: single and combined effects in pregnant women from Guangxi Zhuang, China - Jun Liang; Yu Zou; Zican Mo; Lixiang Pang; Kaiqi Yang; Peng Tang; Qian Liao; Liujuan Ou; Junshang Wen; Wanhui Li; Huishen Huang; Xiaoqiang Qiu (Environmental Pollution, 2026)

Zero-energy, capillarity-gravity self-filtration system: A sustainable and ultra-low cost solution for high-efficiency microalgae removal - Haochuan Lin; Junjie Yang; Yuqin An; Mo Dong; Zupei Wang; Yiqi Tang; Huanhuan Tang; Hong Yao; Xinyang Li; Wen Zhang (Chemical Engineering Journal, 2026)

Remote control of bacterial gene expression: Optogenetics, electrogenetics, sonogenetics and magnetogenetics - Youli Jiang; Zihao Mo; Jingchao Chen; Dingming Guo; Xiangfeng Wang; Xuchun Wan; Qianqian Yang; Haorui Niu; Junqing He; Zhiqi Zhang; Qian Xiang; Xue Tian; et al. (Chemical Engineering Journal, 2026)

Coordinated yet allometric leaf-root biogeochemical niche dynamics underlies divergent growth predictability under N addition - Xian-Meng Shi; An-Xin Liu; Yu-Xuan Mo; Sujan Balami; Jin-Hua Qi; Yang Liu; Zi-Yan Chen; Liang Song (Plant and Soil, 2026)

DaphTrack: A deep learning-based multidimensional behavior analysis system for neonatal Daphnia magna - Yang Ma; Wenping Xiao; Jinguo Wang; Rongqin Mo; Xiang Kuang; Yuncheng Lv; Xiaoming Fan (Marine Pollution Bulletin, 2026)

Group IIId ethylene responsive factor 34 as a positive modulator of ABA signal pathway in Arabidopsis - Li Zhang; Mingxin Piao; Luyao Ji; Zixun Gao; Pingping Wang; Zeng Zhou; Jinpeng Zou; Qingchi Shi; Fang Liu; Yuping Xie; Mingdi Bian; Zhenming Yang; et al. (Plant Science, 2026)

Bio-based anhydride crosslinked furan-derived vitrimeric epoxy networks with intrinsic flame retardancy, self-healing capacity and recyclability - Tian-Mo Yang; Hao-Xin Niu; Wen-Jie Zheng; Hao-Ran Jiang; Yuan Hu; Xin Wang (Journal of Cleaner Production, 2026)

An integrated assessment of β-diversity towards setting priorities for molluscan conservation in a large subtropical river - Xue Bai; Zhengfei Li; Jorge García-Girón; Yang Liu; Xin Luo; Jiali Yang; Duopeng Zhang; Yangxin Mo; Junqian Zhang; Zhicai Xie (Journal of Environmental Management, 2026)

Why does co-stewing shiitake mushrooms (Lentinula edodes) and beef synergistically enhance umami? An exploration from the perspective of umami peptides - Jiaxin Liu; Yujie Guo; Ping Yang; Hongbo Li; Haizhen Mo; Wei Jia; Zhenbing Liu; Chunhui Zhang (Food Research International, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Spatiotemporal correction of decision variables using XGBoost for multi-objective intelligent scheduling rule extraction model in reservoir-lake flood control systems - Huili Wang; Bin Xu; Xinman Qin; Xinrong Wang; Jianyun Zhang; Guoqing Wang; Fubao Yang; Ping-an Zhong; Ran Mo; Xuesong Yang (Environmental Modelling & Software, 2026)

Brine-filled MXene “Sandwich” system for synergistically enhanced electrochemical energy storage and solar desalination - Bowen Liu; Xuedong He; Yawei Yang; Yuyao Shen; Yihong Liu; Qi Zhao; Xinye Xu; Mo Zhou; Tianyi Wang; Wenxiu Que (Chemical Engineering Journal, 2026)

A monolithic Janus dural sealant with adhesive and lubricant surfaces activated by non-toxic visible light exposure - Subin Kang; Hyeseon Lee; Sijoon Lee; Keum-Yong Seong; Yeon Suk Song; Ji-Su Kong; Yeji Kang; Kyoick Koo; Hak Mo Sung; In-Soo Yoon; Kyoung Hyup Nam; Seung Yun Yang (Chemical Engineering Journal, 2026)

Carbon-regulated MnxOy catalysts from Mn-MOF-74: Synergistic effects on glucose oxidation to formic acid - Hongrui Guo; Chengjie Sun; Mo Qiu; Hejuan Wu; Zhihui Ma; Jirui Yang; Feng Shen (Biomass and Bioenergy, 2026)

Separation of meteorological and anthropogenic contributions to major ambient pollutants using an integrated explainable machine learning framework: RMT-PAS - Huabing Ke; Sunling Gong; Yaqiang Wang; Lei Zhang; Jingyue Mo; Jiayu Yang; Chao Wang; Chunhong Zhou (Atmospheric Environment, 2026)

Targeting Strategies of Stem Cell-Derived Extracellular Vesicles in the Treatment of Cardiovascular Diseases - Jiaming Fan; Liyun Yao; Jiayi Yao; Shumin Jiang; Lianbo Shao; Yunfang Mo; Ziying Yang; Zhenya Shen (Stem Cell Reviews and Reports, 2026)

Lactobacillus rhamnosus GG Supernatant Improves GLP-1 Secretion Through Attenuating L Cell Lipotoxicity and Modulating Gut Microbiota in Obesity - Xu Wang; Xinrui Lv; Yaxin Qi; Sipu Wang; Mo Yang; Bangmao Wang; Hailong Cao; Jie Zhang; Xin Xu (Probiotics and Antimicrobial Proteins, 2026)

Salvianolic Acid B Inhibits Ferroptosis Through ACSL4 Pathway Regulation in sepsis-associated encephalopathy Mice - Xingyao Li; Zhizhun Mo; Yumei Yang; Chunxia Zhao; Shuwen Zhang; Yan Lin; Yuxiang Liu; Ling Wang; Xiaolong Xu; Qingquan Liu; Kai Fan (Molecular Neurobiology, 2026)

Lowering cyclosporine trough concentration threshold effectively mitigates acute graft-versus-host disease in children with severe β-Thalassemia post hematopoietic stem cell transplantation - Zhuolin Yang; Xianggui Wang; Xiaojing Wang; Wenjiao Ding; Yiyu Zhang; Qingling Gu; Wenqing Wang; Yousi Miao; Ping Xie; Min Huang; Hua Jiang; Xiaolan Mo; et al. (European Journal of Clinical Pharmacology, 2026)

Sources of potentially toxic elements in lake sediments near an abandoned mine: understanding the combination of uranium radioisotopes - Yun-Mo Yang; Seung-Hee Hong; Hyun-Gi Jeong; Min-Hee Chae; Tae-Woo Kang; Won-Seok Lee (Environmental Geochemistry and Health, 2026)

Micro-mechanism of residual PCE removal from aquifers by in-situ microemulsion: behavior and proportion of mobilization and solubilization - Yanyang Mo; Jun Dong; Xue Liang; Weihong Zhang; Chaoge Yang (Water Research, 2025)

Incremental analytical modelling of segment lining uplift during shield tunnelling considering the dynamic tunnelling process - Longxiang Ma; Qin Yang; Yixiang Mo; Haijiang Zhu; Bo Wang; Di Meng (Tunnelling and Underground Space Technology, 2025)

Paeoniflorin attenuates hyperprolactinemia by targeting the pituitary mPRα-mediated, dopamine receptor-independent signaling in vivo and in vitro - Bingqi Lin; Yun Yi; Xiaolan Mo; Yifan Yang; Yuhao Li; Chunxia Wang; Yuanyi Wei (Toxicology and Applied Pharmacology, 2025)

Cloning and functional characterization of three cinnamate 4-hydroxylase isoforms from Marchantia polymorpha associated with UV-absorbing compounds production - Jiayi Yang; Jian Mo; Baoyun Shan; Xiaochun Qin; Haina Yu (Plant Gene, 2025)

Characteristics, prediction model and driving mechanism of multidimensional daily scale propagation from meteorological to agricultural drought in Guangxi, China - Yunchuan Yang; Zongheng Li; Jiazhen Yang; Liping Liao; Liqing Liang; Changzheng Wei; Mengdong He; Chongxun Mo; Xungui Li; Guikai Sun (Journal of Hydrology, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Fe/Mn-MOF@PDA sponges: A hydrolytically stable and facilely recoverable material for arsenic removal through polydopamine-mediated homogeneous MOF immobilization - Wei Mo; Xin Liu; Yang Yang; Chengcheng Wei; Yuhua Huang; Jinlin Yang; Aoping He; Jingni Liao; Xiujuan Su; Jingpeng Feng; Shaojian Ma (Journal of Environmental Chemical Engineering, 2025)

Multivalent copper-carbon-catalyzed persulfate/O2 system: The relation between copper valence and the species of reactive oxygen - Zehui Fan; Zhisen Li; Dan Mo; Jingyang Zhang; Shuyi Yang; Yun Li; Changlong Bi; Chong Peng; Tao E (Journal of Environmental Chemical Engineering, 2025)

Effects of static magnetic fields on the physicochemical and flavor quality of strawberry fruit during cold storage - Fan Liu; Xiaoyue Mo; Sijian Zhou; Jian Wei; Na Yang; Yamei Jin; Xueming Xu (Food Chemistry, 2025)

Disclosing occurrence of typical tire wear particle-derived chemicals in grassland soils from remote pastoral areas, north China - Guoguang Wang; Aoduo Yang; Shuaihao Liu; Mingjun Mo; Haiyue Chen; Guangzhi Rong; Haixia Wang; Yu Liu (Environmental Research, 2025)

Hydrological connection restoration may contribute more than species selection to organic carbon stock accumulation in mangrove - Qijuan Cao; Yuting Yang; Yan Lin; Lingling Zhong; Yutong Jin; Yujia Tian; Yuxi Chen; Luojian Mo; Yisheng Peng (Estuarine, Coastal and Shelf Science, 2025)

Mechanistic insights into N2O decomposition over CoFe2O4 catalysts and a dual-stage strategy for simultaneous NO and N2O removal from ammonia engine - Tianpeng Zhang; Hongyuan Xi; Song Zhou; Jie Mo; Wenming Yang (Chemical Engineering Journal, 2025)

Inorganic-organic composite electrochromic film and device based on interfacial proton transfer with HxWO3 proton source - Ai-Bo Jia; Weiran Zhang; Tong Yang; Chang Gu; Jiale He; Yutong Tang; Sean Xiao-An Zhang; Yu-Mo Zhang (Chemical Engineering Journal, 2025)

Suppression of halogen migration and defect passivation driven by electrostatic interaction for high performance quasi-2D pure-blue perovskite LED - Minfei Lan; Ruoyan Liu; Mohan Li; Zhiying Guo; Weiping Mo; Zhijun Liu; Lanlan Zhai; Qian Miao; He Huang; Guoku Chao; Yun Yang; Lijie Zhang; et al. (Chemical Engineering Journal, 2025)

Potential use of plant secondary metabolites in the treatment of allergic respiratory diseases (ARDs) - Miran Kang; Kwang Mo Yang; Christine Stanly; Alina Pant (Molecular Biology Reports, 2025)

Identification of lncRNA expression profiles associated with ovarian development and ageing process in mice - Siyuan Chen; Zixue Zhou; Jitong Mo; Xi Yang; Yuncheng Pan; Renbin Liu; Muhammed Boye Jallow; Feng Zhang; Yanhua Wu (Journal of Applied Genetics, 2025)

GSDMD deficiency mitigates intestinal damage via macrophage pyroptosis control in experimental NEC - Yihang Yang; Xinyi Yang; Yue Ma; Xinli Liu; Dandan Mo; Cuilian Ye; Qin Deng; Wenli Han; Xionghui Ding; Chunbao Guo (Inflammation Research, 2025)

Characterisation and diagnostic model of monogenic lupus - Mengyang Yang; Dan Lu; Yulu Li; Xiongbin Chen; Han Yang; Wenxiu Mo; Huawei Mao (Immunologic Research, 2025)

TFAP2A-regulated CRNDE enhances colon cancer progression and chemoresistance via RIPK3 interaction - Xin Gao; Yanming Huang; Tonghui Wei; Jingmin Xue; Filippov Iurii; Laishou Yang; Liying Wang; Hao Li; Genshen Mo; Yuze Huang; Haonan Xie; Hang Wang; et al. (Functional & Integrative Genomics, 2025)

Corrigendum to “Effects of birdwatching tourism on breeding behaviour and reproductive success of hornbills” [Appl. Anim. Behav. Sci. 292 (2025) 106763] - Shuang Yang; Xi Lu; Jiaju Liu; Shuangping Yu; Zuwei Yang; Anru Zuo; Ruixin Mo; Dong Zhu; Shilong Liu; Yubao Duan (Applied Animal Behaviour Science, 2025)

Fluorescent visualization of endoplasmic reticulum stress induced by microplastic pollution via surge of intracellular reactive oxygen species - Le Yang; Xinchao Xia; Fan Li; Qiuhong Mo; Pin Shang; Junbin Li; Yi Li; Yibo Zhou; Zhihe Qing (Analytica Chimica Acta, 2025)

Habitat and density effects on tea quality: A microclimate and nutrients perspective - Manzoor; Qian Dai; Yu-Xuan Mo; Sujan Balami; Chun-Jie Wang; Xian-Meng Shi; Yang-Jie Zheng; Liang Song (Agriculture, Ecosystems & Environment, 2025)

Coupled modeling of rice growth and quality accumulation facilitates efficient, high-quality and precision water management - Wenhao Dong; Aizheng Yang; Qiang Fu; Vijay P. Singh; Lili Zhangzhong; Pingan Zhang; Xiaofang Wang; Kun Hu; Mo Li (Agricultural Systems, 2025)

Endothelial SPRY1 deficiency associates with angiogenic-metabolic reprogramming in pulmonary arterial hypertension: a multi-omics analysis of bulk and single-cell transcriptomic profiles - Yanfei Mo; Desheng Wang; Zhenkun Deng; Pingping Zhao; Zhen Gou; Xiaoyun Sun; Yunrui Zhang; Yang Bai (Apoptosis, 2025)

Mechanism of Permeability Evolution in Coral Reef Limestone Under Variable Confined Pressure Using Nuclear Magnetic Resonance Technology - Yang Mo; Haifeng Liu; Yongtao Zhang; Shun Zhai; Peishuai Chen; Ru Qu; Fuquan Ji (Journal of Marine Science and Engineering, 2025)
The development of underground space in the South China Sea islands is an important way to enhance their protection capabilities. This study focuses on the stress loading and unloading conditions of surrounding rock during the excavation of underground caverns in island reefs. Laboratory variable confining pressure permeability tests were conducted to quantify the stress sensitivity of permeability in coral reef limestone based on Darcy’s law and the stress sensitivity index model equation for permeability. In addition, the use of nuclear magnetic resonance technology reveals the microscopic mechanism of coral reef limestone permeability evolution. The results of the experiments show that the permeability of coral reef limestone sample is mainly controlled by the advantaged permeable channels formed by large pores. During the stress loading stage, the pore structure inside the sample changes, with compression of large pores and generation of smaller pores, resulting in a decrease in effective permeable pathways and a decrease in permeability. When the stress loading reaches 4 MPa, the damage rate of the sample’s permeability is 19.6%. During the stress unloading stage, the recovery of the sample’s permeability shows a significant hysteresis effect. Due to the irreversible damage caused by the compression and collapse of the pore structure during the loading stage, the permeability of the sample cannot fully recover when unloaded to the initial stress state. Based on the experimental results, calculations show that the stress sensitivity coefficient of coral reef limestone permeability is 1.1 × 10−1 MPa−1, which is higher than that of conventional land-based rocks. The conclusions of this study can provide important design references for the stability control of surrounding rocks and geological hazard prevention during the excavation of underground chambers on the islands.

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Overview of Wear-Resistant Coatings in Marine Environments - Fengming Du; Renhao Mo; Zhen Guo; Jinlong Wang; Yuxing Yang; Shuai Zhang (Journal of Marine Science and Engineering, 2025)
Marine engineering equipment operates under extreme conditions such as high salinity, humidity, and flow velocity during marine resource exploration. These harsh environments impose strict requirements on surface performance, especially in terms of wear and corrosion resistance. Wear-resistant coatings are increasingly regarded as a crucial surface engineering approach to mitigate multi-mechanism degradation and improve the long-term reliability of marine equipment. In this review, the typical wear mechanisms in marine environments are systematically analyzed. Corresponding to different service scenarios, the main categories of coating materials, such as metal matrix composite coatings, cermet coatings, functionally graded coatings, and nanolayered coatings are summarized in terms of their structure and performance characteristics. Furthermore, mainstream fabrication techniques, including high-velocity oxy-fuel (HVOF), high-velocity air-fuel (HVAF), laser cladding, cold spray, and physical/chemical vapor deposition (PVD/CVD), are reviewed with respect to their influence on coating micro-structure and properties. Standardized evaluation methods for coating performance are also discussed. Finally, the current research challenges are identified, and future development trends are outlined, with an emphasis on multifunctional, intelligent, and environmentally friendly coating systems. This work aims to provide a systematic reference and theoretical basis for the design and application of wear-resistant coatings in marine environments.

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Caulerpin suppresses tumor-associated angiogenesis and tumor growth via Hippo signaling in cervical cancer - Guang Yang; Yan Mo; Honghong Rong; Bihui Guo; Qingbing Zha; Hanli Shuai; Minghua Wang; Ping Li (Toxicology and Applied Pharmacology, 2025)

Behavior of coupled fire induced by the interaction of hydrogen jet flame and pool flame under different pool aspect ratios and release diameters - Liang Gong; Zihang Yang; Haoyu Wang; Chenyang Li; Tianyu Mo; Yuchun Zhang (Process Safety and Environmental Protection, 2025)

Effect of apparent pore-fluid compressibility and degree of saturation with atmospheric pressure on wave-induced transient pore pressure response - Wen-Gang Qi; Pei-Qing Zhao; Li-Jing Yang; Mo-Zhen Zhou; Fu-Ping Gao; Dong-Sheng Jeng (Ocean Engineering, 2025)

Assessing the role of short-chain chlorinated paraffins in the toxicity of ambient particulate matter - Mo Yang; Chu Chu; Jing-Wen Huang; Guang-Hui Dong; Nan-Xiang Jin; Marjut Roponen; Pasi I. Jalava (Journal of Hazardous Materials, 2025)

Effects of coupled precipitation manipulation and biochar on soybean soil respiration and its temperature sensitivity in the cold black soil regions under climate change conditions - Xuechen Yang; Tianxiao Li; Qiang Fu; Fanying Kong; Renjie Hou; Wei Gao; Qize Lu; Qinglin Li; Mo Li; Dong Liu (Journal of Cleaner Production, 2025)

Vibrio parahaemolyticus outer membrane porin Vpa0810 regulates its biofilm formation and plays a vital role in its stresses tolerance - Yu Sun; Min Chu; Chenzhi Zhuhuang; Yan Wang; Qiufen Mo; Qinxue Ni; Youzuo Zhang; Menghua Yang; Guangzhi Xu (International Journal of Food Microbiology, 2025)

Smartphone-assisted Ce-POM/CuBTC peroxidase-like colorimetric detection of H2O2 and ascorbic acid in food samples - Yiyi Zhang; Haibo Zhang; Chengyuan Ma; Yihang Yang; Xuan Mo; Yuan Shi; Zhijia Yin; Hong Li; Lin Sun (Food Chemistry, 2025)

Comparative study on the structural, antioxidant and functional properties of hydrolysates from Pleurotus erynigii and Pleurotus ostreatus protein by alcalase and trypsin - Xiao-Xuan Hou; Shu-Jing Bing; Man Hao; Jie Yang; Gui-Jin Sun; Ying-Qiu Li; Chen-Ying Wang; Yan Liang; Hai-Zhen Mo (Food Bioscience, 2025)

Single brand tire wear particles promote toxin-producing of an invasive cyanobacterium - Yuanyuan Mo; Jingxiang Lin; Xi Li; Hans-Peter Grossart; Lifeng Lin; Mekiso Y. Sido; Jun Yang (Environmental Research, 2025)

Exploring absolute sustainability–informed water inequality indicators of Chinese city clusters - Mo Li; Mengyi Yang (Environmental Research, 2025)

Spatial heterogeneity of soil Cd and Pb driven by combined effects of pedogenesis and anthropogenic activities: A case study in the mountainous and hilly region of Fujian Province, China - Weikang Sheng; Qingye Hou; Zhongfang Yang; Tao Yu; Long Zhan; Ming Zhang; Mo Zhou; Guoguang Chen; Zhimin Tang; Ying Wang (Environmental Research, 2025)

Effect of microplastics on antibiotic resistome risk in composting - Yiwen Yang; Xiaoyue Tang; Pengfei Zhang; Chunhao Mo; Feng Huang; Zhiguo Wen (Environmental Research, 2025)

Exploring the potential of UAV-based thermal imagery for monitoring diurnal variations in the microscale urban thermal environment - Meng Ji; Yongming Xu; Shanyou Zhu; Yang Zhang; Yan Xin; Yaping Mo (Energy and Buildings, 2025)

Design of Alocasia-inspired biomass aerogel solar evaporator and its application in clean water self-supplying cycle - Yongjing Liu; Yifan Zhu; Dicong Yang; Yumeng Yang; Xiaoliang Mo; Bo You; Limin Wu (Chemical Engineering Journal, 2025)

Dual-strategy stabilization of zinc anodes through solvation regulation and interfacial engineering in aqueous zinc ion batteries - Weilin Yan; Yifan Wang; Lufan Liu; Feiyu Tao; Yang Huang; Zhaoqian Li; Li'e Mo; Hong Zhang; Linhua Hu (Chemical Engineering Journal, 2025)

High-performance self-powered triboelectric pressure sensor based on 3D MXene/AgNWs composite electrodes and PTFE/PDMS tribolayers - Jun Lv; Shun Li; Jiahao Yang; Yujun Liu; Jing Zhao; Jiliang Mo (Chemical Engineering Journal, 2025)

An electrochemically switchable “Cu−S” coordination of copper(II)-doped conjugated polymer for electrochromic energy-saving smart windows - Xue-Song Liu; Rui-An Liu; Baige Yang; Yuxin Qu; Weiran Zhang; Sean Xiao-An Zhang; Yu-Mo Zhang (Chemical Engineering Journal, 2025)

Evapotranspiration Spatiotemporal evolution and its driving factors contribution analysis by SGC model of improved complementary correlation principle in Guangxi, China - Yunchuan Yang; Jiaqi Yao; Weiquan Wang; Liping Liao; Zongheng Li; Tao Yan; Yuxuan Zhou; Chongxun Mo; Xungui Li; Guikai Sun (Theoretical and Applied Climatology, 2025)

Hyperbaric oxygen treatment mitigates gut dysbiosis of mice with spinal cord injury - Mo Liu; Lu Yang; Ding Nan; Linlin Ma; Jing Zhang; Fang Liang; Jing Yang; Xuehua Liu (Journal of Molecular Medicine, 2025)

Study on the characteristics of vibration acoustic signals and rupture grading for reactor pipeline leaks - Xinyu Zhao; Zhuorun Zhang; Xiangpeng Du; Yu Wang; Jinchuan Yang; Zhangjun Feng; Ruiyang Zhong; Chuang Han; Jiaxin Mo; Jinlong Wan; Zhida Yang (Annals of Nuclear Energy, 2025)

Effects of birdwatching tourism on breeding behaviour and reproductive success of hornbills - Shuang Yang; Xi Lu; Jiaju Liu; Shuangping Yu; Zuwei Yang; Anru Zuo; Ruixin Mo; Dong Zhu; Shilong Liu; Yubao Duan (Applied Animal Behaviour Science, 2025)

Optimizing soybean production and emission reduction through biogas slurry substitution and straw incorporation: A five-year field study in northeast China's black soil region - Pingan Zhang; Aizheng Yang; Xiaofang Wang; Lihong Wang; Yan Sha; Mo Li (Agriculture, Ecosystems & Environment, 2025)

Urbanization alters river multifunctionality by reducing macroinvertebrate diversity in highly human‐impacted plain river networks - Jiali Yang; Zhengfei Li; Erik Jeppesen; Dieison A. Moi; Yang Liu; Yangxin Mo; Xue Bai; Feihua Wang; Zhicai Xie; Junqian Zhang (Limnology and Oceanography, 2025)
Urbanization has dramatically destabilized crucial ecosystem functions through extensive land‐use changes, habitat fragmentation, and modified species compositions. However, the mechanisms through which urbanization affects river ecosystem multifunctionality (EMF)—the simultaneous performance of multiple ecosystem functions—remain largely unknown. This study evaluated the impact of urbanization on EMF using macroinvertebrate community data collected from 83 sampling sites across the Yangtze River Delta, China (30°47′N–32°02′N, 119°55′E–121°20′E). We investigated the pathways by which urbanization change ecosystem multifunctionality, including: (1) biotic (such as biodiversity) and abiotic (such as water quality) pathways, (2) taxonomic diversity and functional diversity, and (3) rare species compared to common species. Partial Least Squares Path Modeling revealed that urbanization negatively impacted EMF through both biotic (macroinvertebrate biodiversity) and abiotic (total dissolved solids, salinity, and conductivity) pathways, with the former playing a dominant role. Taxonomic diversity emerged as a stronger positive predictor of EMF than functional diversity. Moreover, the taxonomic diversity was positively correlated with consumer biomass and photosynthetically active radiation and negatively with nutrient concentration. We further showed stronger effects of rare than common species in maintaining EMF. Our study fills a gap in the mechanistic understanding of river ecosystem multifunctionality in plain river networks under urbanization and informs strategies for sustainable urban development. We recommend that conservation efforts in urban areas should prioritize the protection of taxonomic diversity and rare species of macroinvertebrates.

Advancements in Lactiplantibacillus plantarum : probiotic characteristics, gene editing technologies and applications - Zhiqi Zhang; Haorui Niu; Qiu Qu; Dingming Guo; Xuchun Wan; Qianqian Yang; Zihao Mo; Siyu Tan; Qian Xiang; Xue Tian; Hongju Yang; Zhi Liu (Critical Reviews in Food Science and Nutrition, 2025)

Efficient separation of impurities from pyrolusite and the enhancement of its products for improving the performance of lithium-ion batteries - Riran Zang; Houyang Chen; Shuxian Shi; Man mo; Dawei Lan; Guangliang Zhang; Yangxian Huang; Kunsong Hu; Xinghua Liang; Lingxiao Lan; Yong Yang; Junji Li; et al. (Chemosphere, 2025)

Plastic film mulching ensures maize climate resilience: A perspective of temperature suitability and optimal sowing period window - Jing Wang; Ling Zhao; Bao-Zhong Wang; Fei Mo; Ning Wang; Shu-Tong Liu; Yuan Song; Ai-Tian Ren; Fu-Jian Mei; Yang Wang; Qi Lu; You-Cai Xiong (Soil and Tillage Research, 2025)

A numerical study of surface building damage caused by natural gas explosion in underground spaces - Ruichao Wang; Li Mo; Yu Yang; Huixian Shi; Shenbin Xiao; Chao Chen (Process Safety and Environmental Protection, 2025)

Albumin mediates the association between maternal exposure to multiple metals and gestational diabetes mellitus: Findings from the Guangxi Birth Cohort Study - Hualong Qiu; Yu Bao; Shengzhu Huang; Yuen Zhong; Caitong He; Long Tian; Yu Zhang; Bangzhu Luo; Tao Liang; Baohong Pang; Mujun Li; Hong Cheng; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

Phase change nanoemulsions developed by a modified phase inversion temperature method for low-temperature thermal energy storage - Songping Mo; Wenke Cheng; Junhao Chen; Yuxuan Lin; Zicai Pan; Zhi Yang; Lisi Jia; Yanping Du; Ying Chen (International Journal of Refrigeration, 2025)

Integrated HPLC and transcriptomic analyses provide insights into soluble sugar changes during postharvest fruit ripening across 134 avocado germplasms - Hongbin Yang; Xiaoqin Mo; Yingqin Li; Siyu Li; Dingli Dong; Jun Tang; Yanxia Li; Jiali Zhang; Weihong Ma; Jiashui Wang (Food Bioscience, 2025)

Crumpled polyamide membranes templated by macroporous scaffolds for ultra-permeable nanofiltration - Hao Zhang; Fei Xie; Zhe Yang; Zhonghao Xu; Jia-Wei Mo; Xiao-Hua Ma; Zhen-Liang Xu (Desalination, 2025)

Microemulsion-assisted synthesis of Mn-TCPP@MnxOy heterostructures for enhanced photodynamic therapy via O2 self-production and GSH-activatable imaging - Chan Yang; Yanling Zhao; Yanru Qin; Zihan Yan; Ziyi He; Nan Yang; Liuting Mo; Weiying Lin (Chemical Engineering Journal, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Community-level polycyclic aromatic hydrocarbon exposure and circulating microRNAs: Exploring their origins and regulatory functions in immune cells - Yufei Wang; Wending Li; Xuedan Xu; Yaxin Wang; Qin Jiang; Yutong You; Ruochen Yuan; Xiao Zhang; Yang Xiao; Chan Kong; Tingting Mo; Huan Guo; et al. (Journal of Hazardous Materials, 2025)

Construction of a stable manganese/copper core-shell laccase-like enzyme for recyclable dye decolorization and phenolic pollutant detection - Xinyi Chen; Wenwen Tao; Ruiguang Xu; Taoling Mo; Xue Yang; Artur Cavaco-Paulo; Jing Su; Hongbo Wang (Journal of Hazardous Materials, 2025)

Effects of plastic film mulching and biochar on soil carbon sequestration and soybean yield in cold regions: Based on the pathways of photosynthetic carbon allocation and microbial functional genes regulation - Wei Gao; Tianxiao Li; Qiang Fu; Mo Li; Renjie Hou; Xuechen Yang; Mingxuan Liu; Fanying Kong (Journal of Cleaner Production, 2025)

Catalytic fast pyrolysis of waste battery separators with limited removal of the Al2O3 layer for selective aromatic hydrocarbons production over HZSM-5 catalyst - Li Zhao; Wan-zhao Huang; Shi-guan Yang; Qi Niu; Shi-yu Feng; Pu-cheng Wang; Ying Mo; Yu-han Fan; Kai Li; Qiang Lu (Journal of Environmental Management, 2025)

Spatio-temporal geomorphological evolution and driving factors of a transgressive dunefield, Qinghai Lake, northeastern Tibetan Plateau - Haokun Mo; Guangyin Hu; Linhai Yang; Zhi Zhang; Jingjing Hu; Huicong Meng; Na Gao; Zhibao Dong (Geomorphology, 2025)

Role of circular RNAs in formaldehyde-induced lung Injury: Insights into expression and regulatory pathways - Pan Ge; Xiang Zhang; Yan-qi Yang; Jia-ming Xie; Mo-qi Lv; Ying Sun; Ya-zhao Li; Yuan-yuan Geng; Jian Zhang; Dang-xia Zhou (Food and Chemical Toxicology, 2025)

Unraveling the main chemical mechanism of PM2.5 pollution caused by open burning of sugarcane straw during winter in southern China: The Pivotal Role of NOx and NH3 Oxidation-Neutralization - Xu Wei; Guiyun Liang; Jingying Mao; Junchao Yang; Yijun Mu; Chuan Nong; Dabiao Zhang; Jiahui Lu; Xishou Huang; Ying Wu; Zhaoyu Mo (Environmental Pollution, 2025)

A layered composite electrochromic film and device enabled by interfacial proton transfer - Ai-Bo Jia; Weiran Zhang; Tong Yang; Jiale He; Chang Gu; Sean Xiao-An Zhang; Yu-Mo Zhang (Chemical Engineering Journal, 2025)

A review and perspective of magnetic-controlled microbots for medical applications - Ping-an Yang; Yixuan Han; Chunyan Mo; Jiufei Luo; Mengjie Shou; Xinglong Gong; Zhihao Zhou (Chemical Engineering Journal, 2025)

Multiscale periodic macroporous tantalum oxide: Structural engineering for enhanced and stable photocatalytic hydrogen evolution - Chunmei Wu; Linsen Peng; Yihan Tong; Manxing Mo; Feng Liu; Rongbin Zhang; Junchao Wei; Aiyu Yang; Xuewen Wang (Chemical Engineering Journal, 2025)

Enhanced recovery of the anammox process under Cr(VI) stress using biochar-supported sulfidized nanoscale zero-valent iron - Aijie Mo; Yifan Yang; Jing Xu; Yue Wang; Shengyu Zhang; Qian Zhang; Linyuan Yi; Xufa Ma; Huijun Yang; Guanglong Liu; Yongchao Yuan (Chemical Engineering Journal, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Decoding the genetic links between substance use disorder and cancer vulnerability - Xin Su; Xiaoyan Mo; Jun Kan; Fan Yang; Bei Zhang; Yuanyuan Huang (Psychopharmacology, 2025)

URSE-Net: a method of extraction winter wheat planting information based on multispectral remote sensing images - Yuguang Zhou; Mingxu Ma; Guang Yang; Zeyu Wang; Youchun Lai; Haifan Liu; Li Chen; Mo Wang (International Journal of Remote Sensing, 2025)

A candidate multi-epitopes vaccine against encephalomyocarditis virus confers protection in mice - Hongshan Li; Rongrong Cheng; Pingan Dong; Yongfang Chen; Rongqian Mo; Jiayu Yue; Dianyu Li; Yanmei Yang; Amjad Ali; Xiangrong Li; Ruofei Feng (Veterinary Microbiology, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Microbial distribution patterns and driving factors related to nitrogen cycling in karst Tiankeng soil - Xiaohui WANG; Junbo YANG; Keyi WANG; Danjuan ZENG; Ling MO; Gaozhong PU (Pedosphere, 2025)

Screening and discovery of volatile allergenic components from artemisia ordosica in Yulin region of Northern China - Xiaoxue Mo; Cheng Wang; Yi Shan; Siqi Wang; Wen Yang; Zhaomin Xia; Zhanguo Qiao; Tao Zhang; Yuanyuan Ding; Rui Liu; Huaizhen He; Langchong He (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Hierarchical iron phosphides@hard carbon composite cathodes for phenol degradation by highly efficient heterogeneous electro-Fenton - Lizheng Yang; Jiayang Lin; Jiayang Mo; Yingxin Wang; Chenhao Liang; Yanbo Chen; Qilun Huang; Dongying Hu; Xiurong Li (Journal of Cleaner Production, 2025)

A framework for optimization and assessment of long-term urban stormwater management scenarios under climate change and performance challenges - Ming Liu; Zhaoli Wang; Mo Wang; Xuefang Li; Yu Zhang; Bing Yang; Chengguang Lai (Journal of Environmental Management, 2025)

Corrigendum to “Synergistic effects of polymethoxyflavonoids from citrus peel extracts on harmful compound formation and flavor quality in grilled beef patties” [Food Chemistry 481 (2025) 1–11 144089] - Zhuoming Huang; Yang Xu; Ming Jin; Zixin Jiang; Lan Mo; Maiquan Li; Aihua Lou; Yan Liu; Chaoyi Xue; Jie Luo; Qingwu Shen; Shuai Wang; et al. (Food Chemistry, 2025)

Regulation of efficient water use in paddy fields via the simulation of the water cycle in cold regions under random precipitation conditions - Mo Li; Kun Hu; Qiang Fu; Aizheng Yang; Xiaofang Wang; Pingan Zhang; Wenhao Dong; Zhenyi Sun (Environmental Modelling & Software, 2025)

Performance-based seismic design method of stacked modular steel building based on three-dimensional seismic isolation - Ze Mo; Binglin Lai; Ganping Shu; Peng Chen; T.Y. Yang (Engineering Structures, 2025)

3D connectivity calculation method for low-dip fractures in high-steep rock slopes - Peng Liang; Yufeng Wei; Hongyuan Guo; Xin Zhang; Hao Yang; Mo Zhang; Shixin Zhang (Engineering Geology, 2025)

Reorganization of antecedent rivers in response to the evolving landscape at the northeastern margin of the Tibetan Plateau - Baotian Pan; Zijuan Dong; Zhenbo Hu; David Bridgland; Qinhong Mo; Xiaohua Li; Menghao Li; Yanan Yang; Meiling Zhong; Renzhe Pan (Earth-Science Reviews, 2025)

Zero-valent Fe and MnSO4 collectively stimulate the degradation-related functionalities in the bacterial secretome affecting the efficient degradation of lignocellulose during composting - Xiaolin Lu; Qiqiang Zhang; Shangyu Lin; Rongchun Huang; Yinfeng Yang; Naiguo Mo; Shasha Liang; Guangsheng Qin; Qunliang Li (Chemical Engineering Journal, 2025)

Enhanced hemicellulose retention in lignocellulosic biomass fractionation with ethylene glycol-regulated deep eutectic solvent - Siwei Chen; Fukuan Li; Zhihui Ma; Haixin Guo; Jirui Yang; Mo Qiu; Feng Shen (Bioresource Technology, 2025)

Evaluating ripeness in post-harvest stored kiwifruit using VIS-NIR hyperspectral imaging - Jeong-Eun Lee; Min-Jee Kim; Bo-Yeong Lee; Lee Jong Hwan; Ha-Eun Yang; Moon S. Kim; In Geun Hwang; Cheon Soon Jeong; Changyeun Mo (Postharvest Biology and Technology, 2025)

Deciphering the complex roles of leucine-rich repeat receptor kinases (LRR-RKs) in plant signal transduction - Ting Tang; Ferdinand Ndikuryayo; Xue-Yan Gong; Elaheh Amirinezhadfard; Mehtab Muhammad Aslam; Mo-Xian Chen; Wen-Chao Yang (Plant Science, 2025)

Anti-sulfur poisoning and highly sensitive portable detection instrument for monitoring of hydrogen sulfide on-site - Wenjing Wang; Shenghong Li; Liumo Jiang; Xiaoju Cui; Yan Gao; Haijing Ning; Qinglian Li; Xiaolin Jiang; Mo Zhang; Dehui Deng; Yang Shu; Jianhua Wang; et al. (Journal of Hazardous Materials, 2025)

The tolerance mechanism of diarrhetic shellfish toxins mediated by the extracellular regulated protein kinase (ERK) pathway in the mussel Perna viridis - Jin-jin Lv; Yu-jie Liu; Yan-hang Mo; Li-yan Deng; Yang Liu; Hong-ye Li; Li Zhang; Wei-dong Yang (Journal of Hazardous Materials, 2025)

Synergistic effects of polymethoxyflavonoids from citrus peel extracts on harmful compound formation and flavor quality in grilled beef patties - Zhuoming Huang; Yang Xu; Ming Jin; Zixin Jiang; Lan Mo; Maiquan Li; Aihua Lou; Yan Liu; Chaoyi Xue; Jie Luo; Qingwu Shen; Shuai Wang; et al. (Food Chemistry, 2025)

Long-term effects of PM2.5 constituents on childhood attention deficit hyperactivity disorder: evidence from a large population-based study in the Pearl River Delta Region, China - Hui-Xian Zeng; Wen-Jie Meng; Qing-Guo Zeng; Jing Wei; Lu-Sheng Liu; Qi-Zhen Wu; Bin Zhao; Anna Oudin; Mo Yang; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Research, 2025)

Efficient Removal of Iodide from Medical Wastewater by D201 Resin - Enze Zhang; Chao Wang; Hezhao Yang; Fugui Mo; Libin Wei; Quan Tang (Water, Air, & Soil Pollution, 2025)

Molecular cloning, expression analysis, and functional characterization of Intelectin-1 from Chinese giant salamanders (Andrias davidianus) - Haolin Mo; Kexin Liu; Xiaoran An; Yongqing Chen; Jiajia Yu; Huixia Yu; Mingxing Yao; Weijia Song; Yang Li; Lixin Wang (Genes & Genomics, 2025)

Seismic performance probabilistic assessment of long-span single-pylon suspension bridge subject to nonstationary ground motions - Jin Zhang; Yangyang Mo; Zhenyu Yang; Xiang Liu; Xinghu Shi (Earthquake Engineering and Engineering Vibration, 2025)

Pp07886, a glycoside hydrolase family 5 protein from Pythium porphyrae, is a required virulence factor and induces host disease resistance - Huichao Yang; Zhaolan Mo; Peiwen Weng; Yongwei Yan; Lei Tang; Xiaojun Rong; Jie Li (Algal Research, 2025)

The Daily Propagation Characteristics of Short‐Duration and Long‐Duration Drought Process From Meteorology to Agriculture in Guangxi, China - Zongheng Li; Yunchuan Yang; Jiazhen Yang; Liping Liao; Liqing Liang; Changzheng Wei; Mengdong He; Chongxun Mo; Xungui Li; Guikai Sun (International Journal of Climatology, 2025)
Guangxi's widespread Karst region and arable land on low hills and slopes have caused agricultural droughts triggered by meteorological droughts to become frequent over the years. This study evaluates meteorological and agricultural droughts using the daily‐scale standardised weighted average precipitation (SWAP) and soil moisture condition index (SMCI), respectively. The objective identification technique for regional extreme events (OITREE) is applied to capture drought events and analyse their dynamics. Droughts are categorised by duration into short‐duration (SD) events (5–30 days) and long‐duration (LD) events (over 30 days). Based on these methodologies, the research reveals daily‐scale relationships of drought propagation from multiple dimensions. From 1979 to 2015, Guangxi experienced 125 meteorological droughts and 178 agricultural droughts, with 67 pairs successfully matched. Agricultural droughts on average lag meteorological droughts by 10 days. The onset lag time varies across different scenarios: seasonal (7 days), consecutive SD (3.3 days) and alternating SD and LD (6.75 days). Similarly, for daily integrated intensity peaks, the lag times in these three scenarios are 14.72, 10.25 and 14.33 days, respectively. Spatial distributions of drought indices under seasonal and alternating SD and LD droughts showed significant consistency, with mean correlation coefficients of 0.49 and 0.61, respectively. In contrast, consecutive SD droughts exhibited weaker correlations, with a mean coefficient of 0.25. The research further revealed correlations between characteristic factors of meteorological and agricultural droughts under both matched and unmatched scenarios. These findings support understanding the daily spatiotemporal evolution of meteorological–agricultural droughts in Guangxi, enabling dynamic risk prediction and early warning for drought mitigation.

Microwave-enhanced Fe/Al recovery from red mud: Mechanistic role of carbothermal reduction and alkali activation in mineral transformation - Yuhua Huang; Wei Mo; Jinpeng Feng; Chunyan He; Jinlin Yang; Shaojian Ma; Xiujuan Su (Process Safety and Environmental Protection, 2025)

Landform basis for the rise of early cities in the upper Jialu river basin, central China - Ye Li; Peng Lu; Panpan Chen; Hui Wang; Shugang Yang; Xiangli Zhao; Yinan Liao; Yan Tian; Zhen Wang; Duowen Mo (Quaternary International, 2025)

Bioassay-guided isolation of bioactive compounds from a plant-derived endophytic fungus Talaromyces funiculosus TF37 - Bo Liu; Zi-Mo Wang; Xiao-Qing Wang; Li Li; Ya-Nan Wang; Jing Yang; Yi Sun (Phytochemistry, 2025)

Validation of industrial radio frequency treatment protocols to control Lasioderma serricorne in tobacco leaves - Jinsong Zhang; Xin Ye; Zijun Mo; Gaoji Yang; Rui Li; Shaojin Wang (Journal of Stored Products Research, 2025)

Unveiling the systemic impact of airborne microplastics: Integrating breathomics and machine learning with dual-tissue transcriptomics - Siwei Chen; Longfa Fang; Teng Yang; Zhen Li; Mo Zhang; Meng Wang; Ting Lan; Jiawei Dong; Zhongbing Lu; Qirun Li; Yinwei Luo; Bo Yang (Journal of Hazardous Materials, 2025)

Ectomycorrhizal fungi and biochar promote soil recalcitrant carbon increases under arsenic stress - Xuan Zhang; Yang Liu; Xingran Mo; Zhongliang Huang; Yonghua Zhu; Hui Li; Lijuan Jiang; Zhuming Tan; Zihao Yang; Yi Zhu; Jing Huang; Baiquan Zeng; et al. (Journal of Hazardous Materials, 2025)

Optimizing visible light absorption, exciton dissociation, and charge transfer through the interaction of donor-acceptor materials to enhance xanthate photodegradation - Anyang Huang; Jingyu He; Ciyuan Huang; Jinpeng Feng; Wei Mo; Xiujuan Su; Jinlin Yang; Dingzheng Wang; Wenhan Sun; Xiurong Li; Aoping He; Bingsuo Zou; et al. (Journal of Environmental Management, 2025)

Butyl xanthate photocatalytic degradation using a highly effective, stable organic solar active layer that attaches to various silicate substrates - Jingyu He; Anyang Huang; Zhengxian Pan; Menghao Zhang; Jinpeng Feng; Shaojian Ma; Ciyuan Huang; Jinlin Yang; Wei Mo; Xiujuan Su; Wenhan Sun; Dingzheng Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

Comparative investigation of the nutritional composition and flavor characteristics of pre-breeding diploid and triploid oysters (Crassostrea gigas) after steaming - Cunxi Lu; Yanjin Li; Bingfu Yang; Gaoqin Mo; Yingcai Zhao; Lingzhao Wang; Shijie Bi (International Journal of Gastronomy and Food Science, 2025)

Quality decline of prepared dishes stored at 4 °C: Microbial regulation of nitrite and biogenic amine formation - Jiaxin Liu; Yin Wang; Ping Yang; Hongbo Li; Haizhen Mo; Prince Chisoro; Dong Han; Chunhui Zhang (Food Microbiology, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Preparation of copper mine tailings-based geopolymers as thermal storage functional backfill materials - Yuxiang Chen; Degao Xiao; Jianbiao Wei; Liwei Mo; Feng Rao; Lang Yang (Environmental Research, 2025)

Highly sensitive and wash-free human serum albumin detection based on filtration-to-enhancement compound microsphere system - Chen Yang; Xin Zhang; Minjing Mo; Guoqing He; Menglu Gao; Tao Jiang; Yihan Ma; Xiaotong Si; Rui You; Fubing Wang; Yi Yang (Chemical Engineering Journal, 2025)

Antibiotic rejection of nanofiltration elevates the level of antibiotic resistance at the membrane surface: A double-edged sword - Yinghui Mo; Cuicui Yang; Liang Wang; Jingfeng Wang; Xin Zhao (Chemical Engineering Journal, 2025)

Boosting selectivity in glucose hydrogenation to sorbitol by optimizing Fe distribution in alloys and supports - Yixin Luo; Jingnan Yang; Fu Li; Xiaomei Zhou; Tongyan Yu; Qingxin Guan; Mo Qiu; Wei Li (Chemical Engineering Journal, 2025)

Nitrogen-cycling microbial diversity and function in tiankengs at different evolutionary stages - Xiaohui Wang; Keyi Wang; Junbo Yang; Danjuan Zeng; Ling Mo; Gaozhong Pu (CATENA, 2025)

Feline gastrointestinal eosinophilic sclerosing fibroplasia in a young ragdoll cat: with surgical management - Jindong Gao; Yuning Li; Yang Xie; Md. F. Rahim; Md. F. Kulyar; Quan Mo; Jianzhong He; Mengdi Zhang; Xing Wu; Jinhua Yin (Veterinary Research Communications, 2025)

Assembly and co-occurrence pattern of microbial communities in bulk and rhizosphere soils of Pinus elliottii plantations on sandy lands in China - Haozhi Long; Si-Yi Xiong; Yang-Mei Mo; Bei-Bei Zeng; Bin-Xuan Shan; Ting Xiao; Yang Gao; Chaoyu Cui (Plant and Soil, 2025)

Magnetic field-assisted bioleaching of cathode materials from spent Li-ion batteries using Acidithiobacillus ferrooxidans - Jun-Ho Hong; Jeon Kim; Ejin Han; Seon-Mo Yang; Hee-Soo Kim; Jihwan Kim; Chong Seung Yoon (Chemosphere, 2025)

Metaviromic and metagenomic study of the pathogens in unexplained pneumonia cases in goats - Zihan Xia; Gan Luo; Lanmu-yi Gou; Wentao Zhang; Eke-gu Ji; Shenglin Li; Taichun Gao; Keha-mo Abi; Falong Yang (Veterinary Microbiology, 2025)

Highly tough and responsible ionic liquid/polyvinyl alcohol-based hydrogels for stretchable electronics - Pengcheng Zhou; Fan Mo; Zichong Ji; Jiawei Yang; Hongzhong Du; Zonglei Wang; Hossam Haick; Yan Wang (Science Bulletin, 2025)

Effects of polylactic acid microplastics on dissolved organic matter across soil types: Insights into molecular composition - Liying Chen; Hongkai Huang; Lanfang Han; Liang Chao; Xuanwei Zhang; Beibei Liu; Chenyan Luo; Weiling Mo; Yanpeng Cai; Zhifeng Yang (Journal of Hazardous Materials, 2025)

Reshaping regional carbon productivity in the Pearl River Delta megaregion: Input-output-based multi-objective optimization to explore low-carbon industrial transitions - Ya Zhou; Yin Mo; Heran Zheng; Yang Zhou; Zhenyu Wang; Sai Liang (Journal of Cleaner Production, 2025)

Microwave-assisted modification of magnetic Mg/Al/Fe-LDH hydrotalcite for efficient arsenic removal from water - Chunyan He; Wei Mo; Yang yang; Wei Guo; Yuhua Huang; Chang Yu; Xiujuan Su; Jinlin Yang; Jinpeng Feng; Aoping He; Shaojian Ma (Journal of Environmental Management, 2025)

A comparative experimental and kinetic modeling study on the oxidation chemistry of 1,2- and 1,3-dimethylcyclohexanes: Key cyclic components in sustainable biofuels and fossil fuels - Mo Yang; Yilun Liang; Juan Wang (Fuel, 2025)

Tough, antibacterial, and antioxidant chitosan-based composite films enhanced with proanthocyanidin and carvacrol essential oil for fruit preservation - Lijun Qian; Ruijing Jia; Quanling Zhao; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Shuduan Deng; Zhiyong Qin (Food Research International, 2025)

Eco-friendly and large-scale fabrication of cellulose-based membrane with wrinkled structure for efficient daytime radiative cooling - Chen Deng; Qiyu Mo; Zicheng Hu; Dongya Yang; Yuqi Li; Tao Zhang; Fengxian Qiu (Chemical Engineering Journal, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Isonardosinone attenuates osteoclastogenesis and OVX-induced bone loss via the MAPK/NF-κB pathway - Guangwei Wen; Haishan Li; Jiasheng Yang; Bin Mai; Tengpeng Zhou; GuoYe Mo; Yongxian Li; Yiyi Lai (Toxicology and Applied Pharmacology, 2025)

Corrigendum to “Controlled atmosphere storage enhances Korean melon shelf life and quality: A comparative metabolic analysis with reefer container export” [Postharvest Biol. Technol. 219, January 2025, 113238] - Woochul Ju; Ji-Hyun Lee; Eunsu Do; Da-yeong Ko; Eungu Jee; Min-Sun Chang; Hyang Lan Eum; Haejo Yang; Kang-Mo Ku (Postharvest Biology and Technology, 2025)

Biocontrol potential of Streptomyces albidoflavus SC-3 on kiwifruit soft rot caused by Botryosphaeria dothidea - Jiling Ma; Youhua Long; Weizhen Wang; Wenzhi Li; Xuetang Chen; Bingce Wang; Zhuzhu Zhang; Feixu Mo; Lu Yang; Hujun Qin; Xianhui Yin (Postharvest Biology and Technology, 2025)

Effects of tire wear particles on freshwater bacterial-fungal community dynamics and subsequent elemental cycles using microcosms - Yuanyuan Mo; Fazel Abdolahpur Monikh; Yousuf Dar Jaffer; Richard Mugani; Danny Ionescu; Guogui Chen; Jun Yang; Hans-Peter Grossart (Journal of Hazardous Materials, 2025)

Experimental and computational study on xylan pyrolysis: The effect of branch structures - Bin Hu; Wen-ming Zhang; Xue-Wen Guo; Ji-hong Li; Xiao Yang; Zhi-mo Fang; Ji Liu; Qiang Lu (Fuel, 2025)

Screening characteristic VOC species, health hazards, and odor pollutants in the grain and oilseed milling industry of China - Xia Yang; Ying Liu; Jiale Fan; Gexiang Chen; Ziwei Mo; Xiongbo Chen (Environmental Pollution, 2025)

Thermal-fluid coupled fracture behavior of fissured granite in a 3D crystal model - Heng Li; Sheng-Qi Yang; Bo-Wen Sun; Zhen Yang; Zhi-Jin Dong; Pin-Qiang Mo (Engineering Geology, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Detoxification and resource utilization of spent refractory materials via sustainable water leaching: Efficient extraction and targeted conversion of soluble fluorides - Xuewei Li; Xueyi Zhao; Zewen Mo; Jun Zhou; Qian Peng; Wei Yang; Wei Liu; Zhen Yao; Qifan Zhong (Chemical Engineering Journal, 2025)

RNA Binding Protein IGF2BP3 Rehabilitates Glycolysis of Vascular Endothelial Cells to Protect the ox-LDL-induced Cellular Injury via Stabilizing LDHA mRNA - Xing-Chun Mo; Ping Lu; Qu-Cheng Wei; Xiao-Jing Yang (Cell Biochemistry and Biophysics, 2025)

A novel optimized orthotopic mouse model for brain metastasis with sustained cerebral blood circulation and capability of multiple delivery - Zihao Liu; Huisheng Song; Zhenning Wang; Yang Hu; Xiaoxuan Zhong; Huiling Liu; Jianhao Zeng; Zhiming Ye; Wenfeng Ning; Yizhi Liang; Shengfang Yuan; Zijun Deng; et al. (Clinical & Experimental Metastasis, 2025)

Porkolor: A deep learning framework for pork color classification - Yuxian Pang; Chuchu Chen; Yuedong Yang; Delin Mo (Meat Science, 2025)

Plasticization of gelatin/chitosan films with deep eutectic solvents and addition of Flos Sophora Immaturus extracts for high antioxidant and antimicrobial - Quanling Zhao; Xi Huang; Lijun Qian; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Zhiyong Qin (Food Hydrocolloids, 2025)

Higher N2O emissions and lower rice yield within double-cropped rice systems of South China under warming - Ting Bao; Nan Zhang; Danmei Mo; Zhuoshu Liu; Taotao Yang; Bin Zhang; Ling Wang; Haoyu Qian; Yanfeng Ding; Yu Jiang (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Janus NPs@MOFs-based nanosensors for real-time visual monitoring and enhanced therapy of colon cancer - Jukun Yang; Mo Ma; Chen Zhao; Yuxuan Chen; Jingdan Sun; Ying Sun; Pinyi Ma; Shan Jiao; Daqian Song (Chemical Engineering Journal, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Hollow nanocubes of MnSe2@Cu3Se2/Cu2Se with heterostructure for ultrahigh-rate sodium storage - Kai Yang; Zhiqian Li; Wenrui Zhang; Xiaodong Geng; Hongting Ma; Jiancheng Zhang; Hao Mo; Zhouxiaolong Zhang; Tianlu Wang; Jie Xu; Nan Zhu (Chemical Engineering Journal, 2025)

The role of liver sinusoidal endothelial cells in metabolic dysfunction-associated steatotic liver diseases and liver cancer: mechanisms and potential therapies - Hanjun Mo; Pengfei Yue; Qiaoqi Li; Yinxi Tan; Xinran Yan; Xinyue Liu; Yuanwei Xu; Yingzhe Luo; Suruiya Palihati; Cheng Yi; Hua Zhang; Minlan Yuan; et al. (Angiogenesis, 2025)

Autocrine/paracrine fibroblast growth factor 1 (FGF1) enhances systemic lipid metabolism in rainbow trout fed with a high-fat diet by elevating uridine levels through the AMPK signaling pathway and activating the upp2 promoter via irf1 - Huixia Yu; Haolin Mo; Xiaoran An; Mingxing Yao; Jiuwei Gao; Jiajia Yu; Dongmei Xiong; Haixia Liu; Yang Li; Lixin Wang (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The effect of magnesium oxide on the structure of metakaolin-based geopolymer microspheres and its application in the adsorption of methylene blue dye - Huiying Mo; Leping Liu; Zhaoyu Yang; Yuanxia Lao; Yan He (Journal of Water Process Engineering, 2025)

Microplastics-exposure experience aggravates the accumulation of diarrhetic shellfish toxins (DSTs) in thick-shell mussel Mytilus coruscus through impairing detoxification processes - Kuan-Kuan Yuan; Ying-Ying Yu; Yu-Jie Liu; Xiu-Lin Yang; Yan-Hang Mo; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Journal of Hazardous Materials, 2025)

Circular RNA circ_0061183 regulates microglial polarization induced by airborne ultrafine particles in HMC3 cells via sponging miR-98-5p - Hui-Xian Zeng; Shuang-Jian Qin; Qi-Zhen Wu; Qing-Guo Zeng; Jia-Hui Li; Anna Oudin; Katja M. Kanninen; Mo Yang; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Journal of Hazardous Materials, 2025)

Influence of precipitation and temperature variability on anthropogenic nutrient inputs in a river watershed: Implications for environmental management - Shuhui Zhang; Xia Li; Ze Ren; Cheng Zhang; Le Fang; Xiaobiao Mo; Wei Yang; Xinhui Liu (Journal of Environmental Management, 2025)

Preparing of multi-metal spinel oxides for PMS activation from spent lithium-ion batteries: A non-closed-loop process - Mengqi Gong; Xueqi Ren; Junting Chen; Ran Mo; Shun Yang (Journal of Environmental Chemical Engineering, 2025)

Antibacterial activity of zinc oxide nanoparticles against Shewanella putrefaciens and its application in preservation of large yellow croaker (Pseudosciaena crocea) - Mengqing Liu; Yuhan Mo; Zheyun Dong; Huicheng Yang; Bangchu Lin; Yongyong Li; Yongjiang Lou; Shiqian Fu (Food Research International, 2025)

Dissecting spacer induced membrane deformation and fluid hydraulic behavior in reverse osmosis - Rihong Deng; Jiahao Mo; Yang Yang; Zhiqiang Pei; Xianhui Li (Desalination, 2025)

Multi-responsive circularly polarized luminescence micro-patterns with high figure of merit towards multi-dimensional data encoding - Li Wen; Peng Yang; Shunpin Mo; Di Wang; Nana Sheng; Xiangxiang Xu; Hongli Zhang; Hongbo Lu; Gang Zou (Chemical Engineering Journal, 2025)

The trojan horse strategy in T-ALL therapy by engineering T-ALL-derived exosomes for targeted delivery of Isoliquiritigenin to the bone marrow to conquer Drug-Resistant T-ALL in PDX model - Yong Liu; Lindi Li; Cheng Ouyang; Zefan Du; Su Liu; Hailin Zou; Chunmou Li; Junbin Huang; Yucai Cheng; Mengyao Tian; Tianwen Li; Jiani Mo; et al. (Chemical Engineering Journal, 2025)

LncRNA NEAT1, an Important Biomarker Involved in the Pathological and Physiological Processes of Parkinson's Disease - Runsen Chen; Yuxi Zhang; Yang Shen; Kede Wu; Xuming Mo; Zhaocong Yang (Journal of Neuroimmune Pharmacology, 2025)

Molecular characterization of MSX2 gene and its role in regulating steroidogenesis in yak (Bos grunniens) cumulus granulosa cells - Jun Ma; Gan Yang; Xuan Qin; Luoyu Mo; Xianrong Xiong; Yan Xiong; Honghong He; Daoliang Lan; Wei Fu; Jian Li; Shi Yin (Theriogenology, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

6PPD induces cerebrovascular defects by triggering oxidative stress and ferroptosis in zebrafish - Mengzhu Lv; Xiaoyu Mao; Zheng Lu; Yanzhu Yang; Jiangtao Huang; Yuqin Cheng; Chuan Ye; Zhixu He; Liping Shu; Dashuang Mo (Science of The Total Environment, 2025)

Hyperspectral classification of ancient cultural remains using machine learning - Rongji Luo; Peng Lu; Panpan Chen; Hongtao Wang; Xiaohu Zhang; Shugang Yang; Qingli Wei; Tao Wang; Yongqiang Li; Tao Liu; Deyang Jiang; Jun Du; et al. (Remote Sensing Applications: Society and Environment, 2025)

Comprehensive metabolome and transcriptome analyses shed light on the regulation of SlNF-YA3b in carotenoid biosynthesis in tomato fruit - Peiwen Wang; Siyu Ran; Yuanhang Xu; Fulei Mo; Fengshuo Li; Rui Lv; Fanyue Meng; Huixin Zhang; Yuxin Zou; Lei Yu; Tianyue Yu; Mozhen Cheng; et al. (Postharvest Biology and Technology, 2025)

Controlled atmosphere storage enhances Korean melon shelf life and quality: A comparative metabolic analysis with reefer container export - Woochul Ju; Ji-Hyun Lee; Eunsu Do; Da-yeong Ko; Eungu Jee; Min-Sun Chang; Hyang Lan Eum; Haejo Yang; Kang-Mo Ku (Postharvest Biology and Technology, 2025)

Fe/Mn-MOF-driven rapid arsenic decontamination: Mechanistic elucidation of adsorption processes and performance optimization - Yang Yang; Wei Mo; Chengcheng Wei; Maulidiah Nani Lailil Islahah; Yuhua Huang; Jinlin Yang; Jingpeng Feng; Xiujuan Su; Shaojian Ma (Journal of Water Process Engineering, 2025)

Metallogenic model of the carboniferous karst bauxites in Central Guizhou Province, Southwest China - Chaokun Luo; Ruidong Yang; Junbo Gao; Jun Chen; Hongcheng Mo (Journal of Geochemical Exploration, 2025)

An electrochemical sensor based on 2D Zn-MOFs and 2D C-Ti3C2Tx composite materials for rapid and direct detection of various foodborne pathogens - Liuhong Yang; Yifeng Ding; Yuhang Ma; Jing Wen; Jiafeng Wang; Ge Dai; Fengfeng Mo (Food Chemistry, 2025)

XR-based interactive visualization platform for real-time exploring dynamic earth science data - Xuelei Zhang; Hu Yang; Chunhua Liu; Qingqing Tong; Aijun Xiu; Lingsheng Kong; Mo Dan; Chao Gao; Meng Gao; Huizheng Che; Xin Wang; Guangjian Wu (Environmental Modelling & Software, 2025)

Enhancing seismic resilience in modular steel building through three-dimensional isolation - Ze Mo; BingLin Lai; Ganping Shu; T.Y. Yang; Carlos E. Ventura; J.Y. Richard Liew (Engineering Structures, 2025)

Construction of multi-pathway electron transfer channel: Mechanism on non-radical to radical promotion in electrocatalysis - Jingyang Zhang; Zhisen Li; Zehui Fan; Dan Mo; Shuyi Yang; Yun Li; E Tao (Chemical Engineering Journal, 2025)

Multifunctional diluent regulated flame-retardant localized high concentration electrolyte boosting Li||NCM811 batteries - Maosheng Li; Lisi Xu; Xuan Wang; Daize Mo; Yuanyuan Hu; Ning Wang; Kai Yang; Kuirong Deng (Chemical Engineering Journal, 2025)

A single-layer electrochromic device with long memory effect and ion conduction regulation based on all liquid crystal components - Yigui Xie; Weiran Zhang; Jiaheng Gao; Zhiqiang Yao; Yan Yan; Xiaochang Zou; Guojian Yang; Yu-Mo Zhang; Sean Xiao-An Zhang (Chemical Engineering Journal, 2025)

Volatile organic compounds from Stenotrophomonas geniculata J-0 as potential biofumigants manage bulb rot caused by Fusarium oxysporum in postharvest Lanzhou lily - Lijun Ling; Rui Yue; Yuanyuan Wang; Lijun Feng; Ling Yang; Yao Li; Rongxiu Mo; Wenyue Zhang; Fanjin Kong; Yijuan Jiang; Yongpeng Zhou (World Journal of Microbiology and Biotechnology, 2025)

Association between exposure to arsenic, cadmium, and lead and chronic kidney disease: evidence from four practical statistical models - Jiongli Huang; Jingying Mao; Huilin Liu; Zhongyou Li; Guiyun Liang; Dabiao Zhang; Junchao Yang; Wen Qin; Pingjing Wen; Yueming Jiang; Zhaoyu Mo (Environmental Geochemistry and Health, 2025)

Combined application of organic and inorganic fertilizers sustained rice yields and N accumulation and decreased soil-canopy system NH3 emission - Bo Shang; Tongtong Tian; Yatong Mo; Han Zhang; Kun Zhang; Evgenios Agathokleous; Yang Ji; Zhaozhong Feng (Agriculture, Ecosystems & Environment, 2025)

How Do Deep Learning Forecasting Models Perform for Surface Variables in the South China Sea Compared to Operational Oceanography Forecasting Systems? - Ziqing Zu; Jiangjiang Xia; Xueming Zhu; Marie Drevillon; Huier Mo; Xiao Lou; Qian Zhou; Yunfei Zhang; Qing Yang (Advances in Atmospheric Sciences, 2025)

Recent advances in biosynthesis mechanisms and yield enhancement strategies of erythritol - Wenli Yang; Xiangying Zhao; Mo Han; Yuchen Li; Yanjun Tian; Zhangbo Rong; Jiaxiang Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Maximizing the net economic benefits of regulating indoor air quality in China - Keqin Yang; Ningrui Liu; Charles J. Weschler; Louise B. Weschler; Jinhan Mo; Ying Xu; Jingya Wei; Yiming Wang; Zhuohui Zhao; Haidong Kan; Yinping Zhang (Sustainable Cities and Society, 2024)

Multi-scale correlation reveals the evolution of socio-natural contributions to tropospheric HCHO over China from 2005 to 2022 - Hui Xia; Dakang Wang; Gonzalo González Abad; Xiankun Yang; Lei Zhu; Dongchuan Pu; Xu Feng; Aoxing Zhang; Zhaolong Song; Yongru Mo; Jinnian Wang (Science of The Total Environment, 2024)

Removal of Cr(VI) from electroplating wastewater by CoNi-LDH@NHCS electrode and its electrocatalytic ammonia production - Hongmin Tian; Hongyan Yang; Zhenlin Mo; Wei Guo; Laiji Xu; Baojun Liu (Journal of Water Process Engineering, 2024)

Fe3O4@Mg/Al/Fe-LDH adsorption properties of As(V) and As(III) co-existing in water - Wei Mo; Chengcheng Wei; Chunyan He; Yang Yang; Maulidiah Nani Lailil Islahah; Xiujuan Su; Jinlin Yang; Yuhua Huang; Jinpeng Feng; Shaojian Ma (Journal of Water Process Engineering, 2024)

A novel carboxylesterase 2-targeted fluorescent probe with cholic acid as a recognition group for early diagnosis of drug- and environment-related liver diseases - Jingkang Li; Mo Ma; Zhimin Zhang; Lanlan Xu; Bin Yang; Quanping Diao; Pinyi Ma; Daqian Song (Journal of Hazardous Materials, 2024)

Critical role of soil-applied molybdenum dioxide composite biochar material in enhancing Cr(VI) remediation process: The driver of Fe(III)/Fe(II) redox cycle - Mingxuan Liu; Heng Li; Qiang Fu; Tianxiao Li; Renjie Hou; Ping Xue; Xuechen Yang; Mo Li; Dong Liu (Journal of Environmental Management, 2024)

Two new species of the subgenus Tipula (Emodotipula) Alexander, 1966 (Diptera, Tipulidae) from southwest China - Qi-Cheng Yang; Li-Ling Mo; Jing Wang; Xiao-Yan Liu; Ding Yang (Journal of Asia-Pacific Entomology, 2024)

Dynamic response of spherical tanks subjected to the explosion of hydrogen-blended natural gas - Li Mo; Ruichao Wang; Huai Yang; Yu Yang; Xia Wu; Wenlong Jia; Changjun Li; Chao Chen (Fuel, 2024)

Spatiotemporal distribution of the planktonic microbiome and antibiotic resistance genes in a typical urban river contaminated by macrolide antibiotics - Chuanmao Yang; Shiwei Yan; Baihuan Zhang; Xiunan Yao; Jiezhang Mo; Fozia Rehman; Jiahua Guo (Environmental Research, 2024)

Metal-organic framework-sealed heterogeneous nanoenzyme: A dual-mode core–shell sensor for sensitive determination of the chlorpyrifos residue in environment and bioaccumulation in food - Jintong Liu; Jie Tang; Yanyang Mo; Lin Zhou; Tingting Cai; Hong Yang (Chemical Engineering Journal, 2024)

Metal-ion-binding properties of glycyrrhiza polysaccharide extracted from Licorice: Structural characterization and potential application in drug delivery - Yanjun Yang; Mengli Yu; Yulin Mo; Yue Cheng; Bin Huang; Weilin Wang; Maomao Zhu; Xiaobin Jia; Liang Feng; Bing Yang (Carbohydrate Polymers, 2024)

Individual and joint exposures to PM2.5 constituents and mortality risk among the oldest-old in China - Yaqi Wang; Yang Yuan; Shaocai Mo; Fang Wang; Jing Wei; Yao Yao; Yi Zeng; Yunquan Zhang (Science China Life Sciences, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Melatonin Mediates Trade–Off in Antioxidant Responses and Nitrogen Metabolism and Benefits the Growth of Fragrant Rice Seedlings Under Light–Nitrogen Levels - Siying Deng; Jiewen Zheng; Yanhong Li; Wenjing Yang; Daitianshu Xu; Shenggang Pan; Xiangru Tang; Wu Li; Zhaowen Mo (Journal of Soil Science and Plant Nutrition, 2024)

Impaired inducibility of immune regulatory capacity of peripheral B cells of patients with recurrent pregnancy loss - Fei Ma; Xiaoyang Feng; Shiyu Feng; Jin Liu; Jia Li; Lihua Mo; Lingzhi Xu; Yulei Liu; Jiaman Wu; Pingchang Yang; Yan Ning (Immunologic Research, 2024)

Quinclorac-resistant Echinochloa spp. promoted growth and reproduction of Laodelphax striatellus (Hemiptera: Delphacidae) probably by providing more nutrients and stable environment - Yimeng Pi; Yanhui Lu; Xia Yang; Wujia Mo; Qiang Li; Zhongxian Lu; Yongfeng Li; Yipeng Xu; Hongxing Xu (Pesticide Biochemistry and Physiology, 2024)

Fluid–rock interaction controlled by integrated hydrothermal fluid and fault: Implications for reservoir development - Leilei Yang; Zhenxue Jiang; Wenjun He; Hao Ye; Dawei Wang; Xianglu Tang; Chenchen Mo; Zhiye Gao; Qiusheng Chang; Weiquan Zhao (Journal of Hydrology, 2024)

The potential of glycinin basic peptide derived from soybean as a promising candidate for the natural food additive and preservative: A review - Hou-Qi Ning; Hai-Run Fan; Chun-Ling Yang; Gui-Jin Sun; Ying-Qiu Li; Hai-Zhen Mo (Food Chemistry, 2024)

Distribution, characteristics, and ecological risks of microplastics in the Hongyingzi sorghum production base in China - Tianzhu Shi; Huajie Xu; Changbin Pan; Xiangui Wang; Yuting Jiang; Qiong Li; Ju Guo; Xinliang Mo; Pan Luo; Qilin Fang; Jing Yang (Environmental Pollution, 2024)

Parabens, bisphenols, and triclosan in coral polyps, algae, and sediments from sanya, China: Occurrence, profiles, and environmental implications - Yiming Ge; Han Zhang; Jinfeng Fu; Zhihui Guo; Qiulu Dong; Jiaxin Yu; Zhiling Mo; Yuxi Lai; Jialei Yang; Shaoyou Lu (Environmental Pollution, 2024)

Research on the coordinate regulation behavior of window opening and split air conditioners usage during summer in mixed-cooling houses in hot-humid regions - Jie Han; Zhuoying He; Zhishan Li; Nan Mo; Fuhao Xie; Wei Yang; Chen Zhang (Energy and Buildings, 2024)

Integrating DNA logic computation and Self-Replication on nanospheres for amplified detection of Dual miRNAs - Liuting Mo; Yan Hong; Rongzheng Yuan; Mingxiu Mo; Chan Yang; Weiying Lin (Chemical Engineering Journal, 2024)

Dual cation Kgu/PAM Gel polymer electrolyte with high ionic conductivity and mechanical strength for flexible All-Solid-State supercapacitors - Kaijun Xie; Xin Liu; Baichuan Mo; Tingting Li; Kai Xia; Long Fang; Yihui Zou; Dongjiang Yang; Xiaodong Zhang (Chemical Engineering Journal, 2024)

Modulating Schottky barriers and active sites of Ag-Ni bi-metallic cluster on mesoporous carbon nitride for enhanced photocatalytic hydrogen evolution - V Navakoteswara Rao; Hyunguk Kwon; M Nagaveni; P Ravi; Yonghee Lee; Seong Jae Lee; Kyeounghak Kim; M Mamatha Kumari; M V Shankar; Jung Ho Yoo; Chiwon Ahn; Sang-jae Kim; et al. (Chemical Engineering Journal, 2024)

Automated counting and classifying Daphnia magna using machine vision - Yang Ma; Wenping Xiao; Jinguo Wang; Xiang Kuang; Rongqin Mo; Yanfang He; Jianfeng Feng; Hengling Wei; Liwen Zheng; Yufei Li; Peixin Liu; Hao He; et al. (Aquatic Toxicology, 2024)

Acinetobacter corruptisaponis sp. nov., Isolated from a Spoiled Bath Lotion - Ying-Si Wang; Gang Zhou; Hong-Bing Tao; Lei Gao; Bao-Zhu Fang; Xiu-Jiang Yang; Hong Peng; Xia Wen; Xiao-Mo Huang; Jie Wang; Wen-Jun Li; Qing-Shan Shi; et al. (Current Microbiology, 2024)

Deep learning-based geological parameterization for history matching CO2 plume migration in complex aquifers - Li Feng; Shaoxing Mo; Alexander Y. Sun; Dexi Wang; Zhengmao Yang; Yuhan Chen; Haiou Wang; Jichun Wu; Xiaoqing Shi (Advances in Water Resources, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Microplastics positively mediate soil multifunctionality in dryland - Peng-Yang Wang; Ze-Ying Zhao; Kadambot H.M. Siddique; Xiao-Bin Xiong; Hong-Yan Tao; Yue Ma; Fei Mo; Yinglong Chen; Yajie Song; William R. Burch; Baoluo Ma; Song Wang; et al. (Resources, Conservation and Recycling, 2024)

Feasibility study of denitrification catalyst prepared from badam shell biochar - Bo Song; Xinyu Mo; Zhenxing Shen; Qin Peng; Hao Fan; Jian Sun; Liu Yang (Journal of Environmental Chemical Engineering, 2024)

Passivating perovskite surface defects via bidentate chelation for high-performing solar cells - Mengting Han; Li’e Mo; Zhiqian Yang; Aiqing Sun; Hong Zhang; Bolin Li; Zhaoqian Li; Xianxi Zhang; Rahim Ghadari; Yang Huang; Linhua Hu (Chemical Engineering Journal, 2024)

Sustainably sourced and DOPO-derived triols as hardeners for epoxy thermosets: A promising solution to synchronously improve flame retardancy, mechanical strength and toughness - Ze-Tao Xiao; Guan-Long Wu; Tian-Mo Yang; Yu Li; Yuan Hu; Manfred Döring; Xin Wang (Chemical Engineering Journal, 2024)

Fabrication of carbon-coated iron-based porous heterogeneous Fenton catalyst and enhanced degradation performance towards ciprofloxacin - Yufan Mo; Chunxia Che; Wei Han; Feiran Chen; Jun Guan; Feng Zhang; Bo Yang; Xiangdong Ren; Huiyu Li; Saeed Ahmed; Yongjun Feng (Chemical Engineering Journal, 2024)

Novel nano-capsule for targeted drug delivery and real-time therapeutic monitoring in osteosarcoma treatment - Chen Zhao; Mo Ma; Jukun Yang; Lin Liu; Pinyi Ma; Qiong Wu; Daqian Song (Chemical Engineering Journal, 2024)

Structure-Functional Activity of Pyrone Derivatives for Inhibition of Barnacle Settlement and Biofilm Formation - Mo Aqib Raza Khan; Bo-Wei Wang; Hsiu-Chin Lin; Yu-Liang Yang; Chih-Chuang Liaw (Marine Biotechnology, 2024)

Regulation of Tert methylation alleviates food allergy via regulating the Tert-IL10 signal pathway - Haotao Zeng; Lingzhi Xu; Jiangqi Liu; Lihua Mo; Minyao Li; Shuo Song; Xuejie Xu; Shihan Miao; Miao Zhao; Pingchang Yang (Immunologic Research, 2024)

Pharmacological Activities of Brevilin A: A Mini-Review - Heng Yang; Yan Wu; Minyi Mo; Lizhi Zhu; Duo Zheng (Current Pharmacology Reports, 2024)

Quantitative detection of Pythium porphyrae and Pythium chondricola (Oomycota), the causative agents of red rot disease in Pyropia farms in China - Jie Liu; Sudong Xia; Huichao Yang; Zhaolan Mo; Jie Li; Yongwei Yan (Algae, 2024)
Red rot disease is one of the notorious algal diseases that threaten the cultivation of Pyropia in China, and two Pythium pathogens , i.e., Pythium porphyrae and P. chondricola , have been reported as causative agents. To monitor the pathogens, a fluorescent quantitative polymerase chain reaction (PCR) method was developed to quantitatively detect their abundance. Using overlapping PCR and pathogen-specific primer pairs, two pathogen-specific fragments were concatenated to construct an internal standard plasmid, which was used for quantification. For zoospores of known numbers, the results showed that this method can detect as less as 100 and 10 zoospores mL -1 in a 200 mL solution for P. porphyrae and P. chondricola , respectively. Using monthly collected seawater at 10 sites in Haizhou Bay, a typical aquaculture farm in China, a significantly higher temperature and a significantly lower salinity were determined in December 2021. P. porphyrae was determined to be more abundant than P. chondricola , though with similar temporal distribution patterns from December 2021 to February 2022. When a red rot disease occurred in December 2021, the two pathogens were significantly more abundant at two infected sub-sites than the uninfected sub-site within both seawater and sediment, though they were all significantly more enriched in sediment than in seawater. The present method provides the capability to quantify and compare the abundance of two pathogens and also has the potential to forecast the occurrence of red rot disease, which is of much significance in managing and controlling the disease.

The composition of the zebrafish intestinal microbial community varies under Bdellivibrio treatment from larvae to juveniles and adults - Haolin Mo; Qing Li; Qingsheng Cao; Haiyong Zhao; Lixin Wang; Hui Yang (Aquaculture, 2024)

The coupling between tectonic uplift and climate change recorded by the Yellow River terraces during the Zoige basin excavation in the northeastern Tibetan Plateau - Qinhong Mo; Zhenbo Hu; David Bridgland; Menghao Li; Baotian Pan; Ningyi Li; Zijuan Dong; Xiaohua Li; Yanan Yang; Meiling Zhong; Renzhe Pan; Rob Westaway (Geomorphology, 2024)

Analytical solution for transient radial interaction between energy piles and soils: Thermo-elastic cavity expansion analysis - He Yang; Pei-Zhi Zhuang; Pin-Qiang Mo; Hai-Sui Yu; Xiaohui Chen (Geomechanics for Energy and the Environment, 2024)

Metabolic and process engineering of Clostridium tyrobutyricum for efficient hydrogen production from sugarcane molasses - Hongxin Fu; Die Yang; Xin Li; Xiaolong Guo; Yongzhang Mo; Sheng Wang; Jufang Wang (Fuel, 2024)

Inhalable explosive nanosensor for real-time visual monitoring of therapeutic effects of lung cancer - Jukun Yang; Mo Ma; Chen Zhao; Jingkang Li; Yuxuan Chen; Zhuoxin Ye; Pinyi Ma; Daqian Song (Chemical Engineering Journal, 2024)

Growth and Transcriptional Regulation of Camellia sinensis Planted in Understory Mode Revealed by Transcriptomic, Metagenomic, and Machine-Vision Analyses - Jialin Liao; Shaolei Xu; Lisha Zhong; Jiayu Liang; Jianxiu Liu; Yuxing Shi; Jiashuang Qin; Yanhua Mo; Jiangming Ma; Yang Huang; Yu Liang (Journal of Soil Science and Plant Nutrition, 2024)

Genetic analysis of Discogobio (Cypriniformes: Cyprinidae) in the Central Yunnan Basin: Effects of geological events and conservation perspectives - Xing‐Jin Che; Yuan‐Wei Zhang; An‐Li Wu; Li‐Mei Zhang; Xiao‐Fu Pan; Mo Wang; Jun‐Xing Yang; Xiao‐Ai Wang (Zoologica Scripta, 2024)
Geological events can have a major effect on the genetic structure and differentiation of fish populations. The relative importance of key geological events on the distribution and genetic structure of endemic fish of the genus Discogobio in the Yunnan–Guizhou Plateau has not yet been evaluated. Studies of the phylogeography of Discogobio fishes could provide insights into spatial and temporal changes in their population size, dispersal history, and extent of geographical isolation, and the data acquired in such studies can be used to aid their conservation. Here, we used single‐nucleotide polymorphisms (SNP) to characterize the phylogeography of Discogobio fishes. Our analysis supports the endemicity of Discogobio . However, Discogobio samples from different regions contained multiple ancestral components, including admixed and diversified genetic components. This might stem from polymorphism of the ancestors themselves or the infiltration of genes caused by hybridization between Discogobio species. We estimated that the most recent common ancestor (MRCA) of Discogobio fish in the Central Yunnan Basin was approximately 4.63–3.83 million years ago (Ma). We also inferred that the evolution of Discogobio in the Central Yunnan Basin was closely related to the expansion and contraction of the lake basin around 2.59–0.13 Ma. We proposed measures that could be implemented to conserve remaining populations and their corresponding habitats to prevent further declines and preserve the biodiversity of this unique genus.

Fish decay-accelerating factor (DAF) regulates intestinal complement pathway and immune response to bacterial challenge - Xia Zhang; Yuhan Zhang; Ting Wu; Hao He; Ran Peng; Kelan Jin; Huilan Mo; Fufa Qu; Jianzhou Tang; Yonghua Zhou; Yalin Yang; Zhigang Zhou; et al. (Fish & Shellfish Immunology, 2024)

Development of a facile one-pot synthesized fluorescent green polyesters as cooling water antiscalants for industrial application - Lijun Gao; Tianming Gao; Jiuying Feng; Shaohong Mo; Yanbei Guo; Pingping Guo; Shiyun Pan; Yuqing Cheng; Qian Yang (Desalination, 2024)

In-situ constructing ultrafine NiCo alloy confined in LDH nanoflower for efficient selective hydrogenation of furfural - Huiling Zhang; Jingnan Yang; Teng Zhao; Fujun Lan; Yixin Luo; Fei Han; Xianliang Qiao; Qingxin Guan; Mo Qiu; Wei Li (Chemical Engineering Journal, 2024)

Effects of coupled biochar and snow cover on soil carbon components and CO2 emissions in seasonally frozen soil areas under climate change conditions - Xuechen Yang; Renjie Hou; Qiang Fu; Tianxiao Li; Mo Li; Song Cui; Qinglin Li (CATENA, 2024)

Ball billing induced highly dispersed nano-MgO in biochar for glucose isomerization at low temperatures - Siyu Xu; Haixin Guo; De Li; Hejuan Wu; Mo Qiu; Jirui Yang; Feng Shen (Bioresource Technology, 2024)

Efficient one-pot conversion of corncob to formic acid using bi-functional MnCeOx/Nb2O5 catalyst - Siyu Xu; Jirui Yang; Hejuan Wu; Haixin Guo; Mo Qiu; Xiao Zhang; Feng Shen (Biomass and Bioenergy, 2024)

Evolution of ozone-precursor sensitivity in the Guangdong-Hong Kong-Macao Greater Bay Area of China under the backdrop of climate change - Yi Du; Zibing Yuan; Leifeng Yang; Jiacheng Chang; Shu Zhang; Jianbin Mo; Richao Wang (Atmospheric Environment, 2024)

Exploring the relationship between infectious agents and autoimmune diseases: a review - Zhihui Feng; Xueli Yang; Biao Zhang; Chune Mo; Chunhong Li; Xiayu Tian; Chong Zhang; Minglin Ou; Xianliang Hou (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

The sensing of circRNA with tetrahedral DNA nanostructure modified microfluidic chip - Shiliang He; Lei Chen; Zhuolang Chen; Guihao Zhang; Yongjin Huang; Huaxiao Zheng; Qing Yang; Zhuoxi Mo; Xinyi Lin; Jiancheng Wen (Analytica Chimica Acta, 2024)

Wearable solid-phase microextraction sampling for enhanced detection of volatile analytes in human ears - Wenzheng Mo; Lei Li; Bi-Cheng Yang; Xiangjie Wang; Baixue Wang; Jianfeng Zhang; Qiaoyun Huang; Zhong-Ping Yao; Dong Zhang; Bin Hu (Analytica Chimica Acta, 2024)

Long-term trend of surface wind speed in the Guangdong-Hong Kong-Macau Greater Bay Area during 1980–2020: Spatiotemporal variation and urbanization effect - Ran Wang; Ziwei Mo; Liting Yang; Ming Chang; Jian Hang (Urban Climate, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Identification and functional characterization of interleukin-22 (IL-22) in orange-spotted grouper (Epinephelus coioides) - Dapeng Yu; Guanjian Yang; Jingyi Mo; Meiling Zhang; Hongli Xia; Zhen Gan; Yishan Lu (Fish & Shellfish Immunology, 2024)

Anionic chemistry regulation boosting the reversible redox in CoSexTey@C polyhedrons for sodium storage - Wenmiao Zhao; Lishi Mo; Xiaoyuan Shi; Bo Liu; Guangmin Yang; Ting Deng (Chemical Engineering Journal, 2024)

Orbital forcing of aridity/humidity fluctuations in the Hexi Corridor and Alxa Plateau, NW China, during the last 1.8 million years - Dianbao Chen; Jiaming Yang; Junsheng Nie; Fei Wang; Qinhong Mo; Baotian Pan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Re-melting of the Neoproterozoic juvenile mafic lower crust: The origin of adakitic and non-adakitic felsic suites in the southwest margin of Yangtze Craton - Jingkai Wu; Zhidan Zhao; Xiaowei Li; Xuejing Tu; Chen Li; Hangshan Lei; Qian Ma; Zhuang Miao; Yiyun Yang; Dong Liu; Qing Wang; Di-Cheng Zhu; et al. (Lithos, 2024)

A critical review of biochar as an environmental functional material in soil ecosystems for migration and transformation mechanisms and ecological risk assessment - Xuechen Yang; Renjie Hou; Qiang Fu; Tianxiao Li; Mo Li; Song Cui; Qinglin Li; Mingxuan Liu (Journal of Environmental Management, 2024)

Physiological and genetic responses of the benthic dinoflagellate Prorocentrum lima to polystyrene microplastics - Si-Yuan Xu; Yan-Hang Mo; Yu-Jie Liu; Xiang Wang; Hong-Ye Li; Wei-Dong Yang (Harmful Algae, 2024)

Effects of Hericium erinaceus polysaccharide in porcine IPEC-J2 intestinal epithelial cells against apoptosis induced by oxidative stress - Jian Li; Jia-rong Mo; Shi-yu Hu; Xin Dong; Jia-wei Li; Li-yu Yang; Yi-jian Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Fishing gear with enhanced drapability and biodegradability: Artificial, eco-friendly fibers inspired by the mussel byssus - Yuri Hong; Ho-Sung Yang; Min Hee Lee; Sinyang Kim; Sung Bae Park; Sung Yeon Hwang; Jeyoung Park; Jun Mo Koo; Dongyeop Oh; Dong Soo Hwang (Chemical Engineering Journal, 2024)

Genome Analysis of Multiple Polysaccharide-Degrading Bacterium Microbulbifer thermotolerans HB226069: Determination of Alginate Lyase Activity - Xue Li; Miao Yang; Kunlian Mo; Yonghua Hu; Hanjie Gu; Dongmei Sun; Shixiang Bao; Huiqin Huang (Marine Biotechnology, 2024)

Indication capability for karst development elevation by knickpoints in Daba Mountain (Southwest China) - Jiasen Zhang; Qiang Zhang; Ke Li; Zixuan Qin; Yanna Yang; Mo Xu (Carbonates and Evaporites, 2024)

Investigation of the Antiviral Mechanism of Curcumin Analog EF-24 against Siniperca cachuatsi Rhabdovirus - Pei-Mo Ju; Shi-Wei Ma; Yi-Yang Li; Shi-Fan Zhang; Jun Li; Guang-Zhou Zhou (Fishes, 2024)
Siniperca chuatsi rhabdovirus (SCRV) is a major strain of viral fish virus resulting in multiple transmissions and devastating damage in aquaculture. Currently, there are no available approved therapeutics. In this study, we screened and identified a novel curcumin analog (EF-24) for evaluating its in vitro anti-SCRV properties and potential molecular mechanisms. Present results demonstrated that EF-24 could strongly delay the occurrence of cytopathic effects (CPEs) in epithelioma papulosum cyprinid cells (EPCs) and inhibit SCRV replication and viral nucleoprotein expression in the early stages of infection by the time-of-addition assay. Furthermore, flow cytometry analysis after Annexin V-FITC/PI double staining and immunofluorescence microscopy observation after JC-1 incubation showed that EF-24 downregulated cell mitochondrial apoptosis induced by SCRV. The enzymatic activities of caspase-3 and caspase-9 were also reduced after EF-24 treatment, indicating that EF-24 may protect cells from SCRV infection by decreasing mitochondrial intrinsic apoptosis in infected cells. Collectively, we demonstrated for the first time that the curcumin analog EF-24 possesses antiviral ability against SCRV, suggesting its potential for effective control of fish rhabdovirus spreading.

A universal model to predict yields of THMs and HAAs based on UV–Visible absorption spectra - Yang Deng; Shansheng Mo; Gregory V. Korshin; Mingquan Yan (Water Research, 2024)

Community stability of free-living and particle-attached bacteria in a subtropical reservoir with salinity fluctuations over 3 years - Xue Yan; Shuzhen Li; Mamun Abdullah Al; Yuanyuan Mo; Jun Zuo; Hans-Peter Grossart; Hongteng Zhang; Yigang Yang; Erik Jeppesen; Jun Yang (Water Research, 2024)

Nutrient limitation of soil organic carbon stocks under straw return - Fei Mo; Dayang Yang; Xiukang Wang; Thomas W. Crowther; Nangia Vinay; Zhongkui Luo; Kailiang Yu; Shikun Sun; Feng Zhang; Youcai Xiong; Yuncheng Liao (Soil Biology and Biochemistry, 2024)

Exposure to microplastics renders immunity of the thick-shell mussel more vulnerable to diarrhetic shellfish toxin-producing harmful algae - Kuan-Kuan Yuan; Ying-Ying Yu; Yan-Hang Mo; Yu-Jie Liu; Wei-Xia Zhang; Jin-Jin Lv; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Science of The Total Environment, 2024)

RETRACTED: Spatio-temporal microbial regulation of aggregate-associated priming effects under contrasting tillage practices - Yeye Zhang; Yunfei Ren; Shenglin Zhou; Xiaoyu Ning; Xiukang Wang; Yanming Yang; Shikun Sun; Nangia Vinay; Michael Bahn; Juan Han; Yang Liu; Youcai Xiong; et al. (Science of The Total Environment, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Red mud-based CoFe2O4 activated by ball milling as effective peroxymonosulfate activator for the degradation of lomefloxacin hydrochloride: Preparation & activation, application and degradation mechanism - Junchi Gu; Guangtao Wei; Youlian Zhu; Linye Zhang; Sen Mo; Zhiqiao Yao; Runtao Yang; Baiying Li (Chemical Engineering Journal, 2024)

Correction to: Novel FOXP2 variant associated with speech and language dysfunction in a Chinese family and literature review - Fengyu Che; Chenhao Li; Liyu Zhang; Chenxi Qian; Lidangzhi Mo; Benchang Li; Haibin Wu; Lifang Wang; Ying Yang (Journal of Applied Genetics, 2024)

Novel FOXP2 variant associated with speech and language dysfunction in a Chinese family and literature review - Fengyu Che; Chenhao Li; Liyu Zhang; Chenxi Qian; Lidangzhi Mo; Benchang Li; Haibin Wu; Lifang Wang; Ying Yang (Journal of Applied Genetics, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Single-atom Mn-embedded carbon nitride as highly efficient peroxymonosulfate catalyst for the harmful algal blooms control - Hangjun Zhang; Yunyi He; Mengfan He; Qiyue Yang; Guoyi Ding; Yuanshuai Mo; Yang Deng; Panpan Gao (Science of The Total Environment, 2024)

Variability of marine epifauna assemblages in response to the microhabitat type and thermal stress - Daniela Macias; Seokwoo Hong; Kwon Mo Yang; Junsu Kim; Jeong Ha Kim (Regional Studies in Marine Science, 2024)

Cloning and functional characterization of a cinnamate 4-hydroxylase gene from the hornwort Anthoceros angustus - Baoyun Shan; Jian Mo; Jiayi Yang; Xiaochun Qin; Haina Yu (Plant Science, 2024)

A wireless fluorescent sensing device for on-site closed-loop detection of hydrazine levels in the environment - Zihao Zhu; Ke Song; Xiaobai Li; Yu Chen; Fanwei Kong; Wanqi Mo; Zhiyong Cheng; Shilong Yang; Hongwei Ma (Journal of Hazardous Materials, 2024)

Short-, long-read metagenome and virome reveal the profile of phage-mediated ARGs in anoxic-oxic processes for swine wastewater treatment - Tao Chen; Chunhao Mo; Yilin Yuan; Shengjie Li; Yinbao Wu; Xindi Liao; Yiwen Yang (Journal of Hazardous Materials, 2024)

Ratiometric SERS quantification of SO2 vapor based on Au@Ag-Au with Raman reporter as internal standard - Yu Lu; Xiufang Mo; Geng Zhu; Yan Huang; Yingchao Wang; Zhenzhong Yang; Liqiong Gao; Guofang Shen; Yi Wang; Xiangwei Zhao (Journal of Hazardous Materials, 2024)

Solar demulsification: Towards the oil-water interface broken of solar photo-thermo-electro coupling - Chunhong Nie; Huan Du; Yupeng Zhang; Jiangrui Yang; Wenfei Wang; Rui Mo (Journal of Environmental Chemical Engineering, 2024)

Membrane–protected magnetic covalent organic framework for efficient extraction of estrogens in dairy products - Cheng Yang; Zheng–Lian Mo; Qiu–Fang Zhang; Jin–Jie Xu; Xiao–Fang Shen; Yue–Hong Pang (Food Chemistry, 2024)

LCP1-mediated cytoskeleton alterations involve in arsenite-triggered malignant phenotype of human immortalized prostate stromal cells - Yiping Yang; Menghan Zhou; Yurun Huang; Xiaotong Ye; Yingxi Mo; Yi Huang; Shan Wang (Food and Chemical Toxicology, 2024)

Covalently bonded MXene@Antimonene heterostructure anode for fast lithium-ion storage - Zheng Bo; Zhouwei Zheng; Yanzhong Huang; Pengpeng Chen; Jianhua Yan; Kefa Cen; Runwei Mo; Huachao Yang; Kostya (Ken) Ostrikov (Chemical Engineering Journal, 2024)

Soil bacteria mediate organic carbon stability during alpine wetland biogeomorphic succession in the arid region of Central Asia - Yang Hu; Mengfei Cong; Mo Chen; Maidinuer Abulaizi; Guangling Yu; Zailei Yang; Xinping Zhu; Hongtao Jia (Plant and Soil, 2024)

Population genetic diversity and connectivity of the kelp species Ecklonia cava from the Korean coast - Dong Mun Choi; Seokwoo Hong; Kwon Mo Yang; Young Wook Ko; Jeong Ha Kim (Journal of Applied Phycology, 2024)
Genetic connectivity of kelp populations can provide essential information for estimating their dispersal capability and related perspectives on persistence. We examined population genetic variability to identify connectivity and potential drivers shaping population genetic clusters of Ecklonia cava , a foundation kelp species in the northwest Pacific region. Using microsatellite markers, we analyzed 11 local populations along the Korean coastline from Jeju Island to Ulleungdo. We found that entire study populations were segregated into two genetic groups, inner (south coast populations) and outer (Jeju Island and Ulleungdo) coastal regions, in accordance with current patterns around South Korea and geographical topography. Genetic similarity between the furthest populations (Jeju Island and Ulleungdo) suggest that the dispersal range of E. cava could be largely expanded by the prevalent current. Inter-population genetic structure in the perspectives of isolation-by-distance (IBD) and isolation-by-environment (IBE) revealed that distance and turbidity gradient were both contributors to the gene flow of E. cava . However, different results appeared for a few populations, suggesting that effects of these factors could vary depending on geographic range of populations and surrounding oceanographic conditions. This study suggests that gene flow of E. cava could be driven by multiple seascape factors (ocean currents, coastal topography, distance and sediments) and the interplay among them at a regional scale, which is applicable to other kelp species with diverse scales.

Effect of use of NSAIDs or steroids during the acute phase of pain on the incidence of chronic pain: a systematic review and meta-analysis of randomised trials - Luyao Huo; Gang Liu; Bowen Deng; Lin Xu; Yanjun Mo; Shengyuan Jiang; Jingwei Tao; Huizhong Bai; Li Wang; Xiaoxiao Yang; Jizhou Yang; Xiaohong Mu (Inflammopharmacology, 2024)
Background This study is the first to summarize the evidence on how the use of anti-inflammatory drugs during acute pain has an impact on the development of chronic pain. Methods Randomized controlled trials retrieved from nine databases included anti-inflammatory drugs (NSAIDs or steroids) versus non-anti-inflammatory drugs in patients with acute pain and reported the incidence of chronic pain. No specified date, age, sex, or language restrictions. Subgroup analyses were performed according to pain classification, follow-up time, and medication. The GRADE method was used to evaluate quality of evidence. Results A total of 29 trials (5220 patients) were included. Steroids or NSAIDs did not reduce the incidence of chronic nociceptive pain. Steroid use in acute phase significantly reduced the incidence of chronic neuropathic pain. In subgroup analysis, benefits were observed for methylprednisolone and dexamethasone, with some adverse effects. Steroids or NSAIDs were statistically significant in reducing pain intensity over 1 year, but the effect size was too small, and whether the long-term effect is clinically relevant needs to be further studied. Conclusion Quality of the evidence was low to moderate. No drug can be recommended to prevent chronic nociceptive pain. Injections of steroids (methylprednisolone or dexamethasone) during the acute phase reduce the incidence of chronic neuropathic pain, but most included studies also used local anesthetics. The results are indirect and need to be interpreted with caution. The pooled data effect sizes for pain intensity were small, so the clinical relevance was unclear. Study registration PROSPERO (CRD42022367030).

A holistic approach to projecting streamflow and analyzing changes in ecologically relevant hydrological indicators under climate and land use/cover change - Yang Liu; Feng Liu; Cheng Chen; Qiuwen Chen; Jianyun Zhang; Kangle Mo; Qinghu Jiang; Siyang Yao (Journal of Hydrology, 2024)

Root-associated bacteria strengthen their community stability against disturbance of antibiotics on structure and functions - Yu-Hong Huang; Yu-Jie Yang; Jie-Yu Li; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2024)

Differences in responses to a fluctuating temperature/humidity environment between two related species of rice leaffolders based on a comparison in a constant environment - Yajun Yang; Qiuju Liao; Xiaorong Mo; Hongxing Xu; Xin Xie; Chenglin Peng; Yinghong Liu; Zhongxian Lu (Journal of Asia-Pacific Entomology, 2024)

Investigation on wave-induced responses of heterogeneous seabed around a buried pipeline based on nonstationary random field model - Bin Zhu; Qing Yang; Tao Wang; Mengmeng Lu; Pinqiang Mo; Tetsuya Hiraishi; Hajime Mase (Computers and Geotechnics, 2024)

Shaping the succession patterns of different soil nutrients, enzyme stoichiometry, and microbial communities through rotation systems - Dan Liu; Yang Liu; Junjie Li; Qin Mo; Junyan Tang; Wenhan Liu; Maksat Batyrbek; Tiening Liu; Xudong Zhang; Qingfang Han (CATENA, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Selenium attenuated food borne cadmium-induced intestinal inflammation in red swamp crayfish (Procambarus clarkii) via regulating PI3K/Akt/NF-κB pathway - Huijun Yang; Aijie Mo; Linyuan Yi; Jianghua Wang; Xugang He; Yongchao Yuan (Chemosphere, 2024)

Mechanisms and targeted reversion/prevention of hepatic fibrosis caused by the non-hereditary toxicity of benzo(a)pyrene - Xinru Du; Ming Jin; Ruzhi Li; Fei Zhou; Yuanze Sun; Qinliang Mo; Sisi Song; Na Dong; Shuoke Duan; Maoxuan Li; Ming Lu; Chi Zhang; et al. (Science of The Total Environment, 2024)

A modified Xin'anjiang model and its application for considering the regulatory and storage effects of small-scale water storage structures - Yiwen Wang; Ping-an Zhong; Feilin Zhu; Chengjing Xu; Ran Mo; Sunyu Xu; Luhua Yang; Sen Wang (Journal of Hydrology, 2024)

Evaluation of the fate of wastewater effluent organic matter in receiving water: Effect of sequential photochemical and biological processes - Lei Zheng; Feng Xiao; Xinyi Zhang; Yang Deng; Shansheng Mo; Zhongli Liu; Xin Gu; Norbert Hertkorn; Gregory V. Korshin; Mingquan Yan (Journal of Hazardous Materials, 2024)

Reductive roasting of red mud with carbon and sulfuric acid dissolution of iron and aluminum: Transformation phases and leaching characteristics - Yuhua Huang; Wei Mo; Jinpeng Feng; Rulong Ren; Wei Guo; Xiujuan Su; Jinlin Yang; Chunyan He (Hydrometallurgy, 2024)

Molecular and geochemical characteristics of lignite in different plant sources evaluated using unsupervised analyses - Yang-Yang Xu; Xing Fan; Feng-Yun Ma; Wen-Long Mo; Xiang Bai; Xian-Yong Wei; Peter N Kuznetsov (Fuel, 2024)

Structure-activity relationship study of high entropy oxides catalysts for oxygen evolution reaction - Yuanxia Lao; Xiaoqing Huang; Leping Liu; Xiangli Mo; Jiali Huang; Yating Qin; Qianqian Mo; Xinfeng Hui; Zheng Yang; Wei Jiang (Chemical Engineering Journal, 2024)

Efficient adsorption of Cu2+ and Cd2+ from groundwater by MgO-modified sludge biochar in single and binary systems - Yan Wang; Xianrong Meng; Shanhu Wang; Yuanye Mo; Wei Xu; Yang Liu; Weilin Shi (Environmental Science and Pollution Research, 2024)

Effects of Different Protein Sources on Growth Performance, Muscle Flavor Substances and Quality Structure in Triploid Crucian Carp - Liquan Yang; Chenglin Yi; Yujian Mo; Zhimin He; Zhehua Xu; Yimiao He; Yongkang Ouyang; Zhuangwen Mao; Fufa Qu; Jianzhou Tang; Zhen Liu; Zhijia Fang; et al. (Fishes, 2024)
A 56-day feeding trial was conducted to evaluate the effect of different dietary protein sources on the growth performance, muscle flavor substances, and quality structure of Triploid Crucian Carp. Three isonitrogenous (32.00%), isolipidic (8.00%), and isoenergetic (18.00 MJ kg−1) practical diets were formulated. These diets consisted of fishmeal as the animal-derived protein source (AP), a combination of soybean meal and rapeseed meal as the plant-derived protein source (PP), and a mixture of fishmeal, soybean meal, and rapeseed meal as the mixed protein source (MP). Each diet was randomly assigned to triplicate tanks of fish and each tank was stocked with 25 fish (11.5 ± 0.4 g). The fish were fed until apparent satiation twice a day. The results showed a significant enhancement in the growth performance of Triploid Crucian Carp in the AP group compared with both the MP and PP groups (p

Landscape patterns and quantified attribution to runoff changes based on the Budyko framework in Nanning, China - Jiaoyin Wei; Yunchuan Yang; Junpei Wei; Liping Liao; Qianyun Li; Haixiang Liao; Miaoqing Liu; Shanqi Huang; Chongxun Mo; Guikai Sun; Xungui Li (Hydrological Sciences Journal, 2024)

Application and evaluation of probiotics against red rot disease in Pyropia - Peiwen Weng; Huichao Yang; Zhaolan Mo; Wenbin Zhang; Yongwei Yan; Xiaojun Rong; Jie Li (Aquaculture, 2024)

Characteristics of microplastic-derived dissolved organic matter and its binding with pharmaceuticals unveiled by fluorescence spectroscopy and two-dimensional correlation spectroscopy - Caixia Yan; Xiao Wang; Minghua Nie; Xiting Mo; Mingjun Ding; Jie Chen; Yi Yang (Science of The Total Environment, 2024)

Improved prediction of global gold prices: An innovative Hurst-reconfiguration-based machine learning approach - Mo Yang; Ruotong Wang; Zixun Zeng; Peizhi Li (Resources Policy, 2024)

Basin-scale reconstruction of late Pleistocene-Holocene fluvial landform evolution and its mechanisms in transitional areas between Taihang Mountain and North China Plain - Yan Tian; Panpan Chen; Peng Lu; Ye Li; Hui Wang; Liang Zhou; Xiaohu Zhang; Shugang Yang; Xingguo Zhang; Xiaoyu Chai; Haiguo Zhai; Min Liu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Adaptive responses and metabolic strategies of Novosphingobium sp. ES2-1–17β-estradiol analyzed through integration of genomic and proteomic approaches - Shunyao Li; Wei Yang; Jingjing Mo; Yubing Wang; Chao Lu; Yanzheng Gao; Yucheng Li; Kai Sun (Journal of Hazardous Materials, 2024)

Size and concentration effects of polythene plastic residues on soil physiochemical traits and maize productivity: A three-year appraisal - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Momena Irum; Fei Mo; Jing Cao; Ning Wang; Hong-Yan Tao; Meng Hao; Song Wang; Kai-Wen Xiao; Fang-Kun Yang; et al. (Journal of Cleaner Production, 2024)

Detoxification of deoxynivalenol and its derivatives in Fusarium contaminated wheat through soaking and germination - Chong Xie; Shufang Wang; Kehui Cao; Xiaosong Mo; Pei Wang; Runqiang Yang (Food Control, 2024)

Bearing capacity of lunar soil ground under extraterrestrial environmental effects - Banglu Xi; Mingjing Jiang; Pinqiang Mo; Jiaqiang Yang; Zhenhua Zhang (Computers and Geotechnics, 2024)

Hirudin ameliorates myocardial ischemia–reperfusion injury in a rat model of hemorrhagic shock and resuscitation: roles of NLRP3-signaling pathway - Yang Bai; Jing Bai; Peng Lu; Yu-Mo Jing; Wei-Chao Zheng; Lu-Ying Wang; Jian-Hua Wang; Feng Wang (Molecular and Cellular Biochemistry, 2024)

Responses of wheat nitrogen uptake and utilization, rhizosphere bacterial composition and nitrogen-cycling functional genes to nitrogen application rate, planting density and their interactions - Zimeng Liang; Jiayu Li; Xidan Cao; Yangyang Tang; Fei Mo; Vinay Nangia; Yang Liu (Applied Soil Ecology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Release of chromium from Cr(III)- and Ni(II)-substituted goethite in presence of organic acids: Role of pH in the formation of colloids and complexes - Shengsheng Sun; Tenghaobo Deng; Ming Ao; Yijun Mo; Jingjing Li; Ting Liu; Wenjun Yang; Chao Jin; Rongliang Qiu; Yetao Tang (Science of The Total Environment, 2023)

Importance of secondary decomposition in the accurate prediction of daily-scale ozone pollution by machine learning - Xinyue Du; Zibing Yuan; Daojian Huang; Wei Ma; Jun Yang; Jianbin Mo (Science of The Total Environment, 2023)

Strontium alleviated the growth inhibition and toxicity caused by cadmium in rice seedlings - Jun Liu; Xinting Fan; Yuanyuan Jiang; Juan Ni; Aili Mo; Meihan Cai; Tong Li; Yaqi Wang; Peishuang He; Shiyu Hu; Tangjian Peng; Cuiying Peng; et al. (Science of The Total Environment, 2023)

Deciphering the dual role of bacterial communities in stabilizing rhizosphere priming effect under intra-annual change of growing seasons - Chao He; Jean Damascene Harindintwali; Hao Cui; Yongxing Cui; Pengfei Chen; Chaoyang Mo; Qingyang Zhu; Weiwei Zheng; Daniel S. Alessi; Fang Wang; Zhenhui Jiang; Jingping Yang (Science of The Total Environment, 2023)

Enhanced CO2 adsorption performance by crystal defect method of multi-level pore Mg-MOF-74 using organic acids - Guanhua Zhang; Shaocong Mo; Hongtao Xu; Xiaoyu Yan; Binlin Dou; Guomin Cui; Qiguo Yang; Wei Lu (Gas Science and Engineering, 2023)

Preparation of curcumin-chitosan composite film with high antioxidant and antibacterial capacity: Improving the solubility of curcumin by encapsulation of biopolymers - Han Li; Yanling Jiang; Jisheng Yang; Rui Pang; Yanan Chen; Liuting Mo; Qiong Jiang; Zhiyong Qin (Food Hydrocolloids, 2023)

Polyampholyte saturated with simulated-body-fluid as a flexible, stretchable and self-healing gel electrolyte for biocompatible energy storages and capacitive circuit elements - Hyungi Kim; Seung Mo Kong; Jin A Kim; Gyujin Yoon; Yang Ho Na; Seong K. Kim (Chemical Engineering Journal, 2023)

Green and efficient utilization of beech sawdust waste for sorbitol production: Direct conversion residue via Ru2P/OMC derived from separated lignin - Longxin Liu; Mo Qiu; Huiling Zhang; Jingnan Yang; Feng Shen; Haixin Guo; Jirui Yang; Qingxin Guan; Wei Li (Chemical Engineering Journal, 2023)

Thermal insulation performance of rock wool reinforced kaolinite-based porous geopolymer - Huixing Dai; Huan Gao; Pan Yang; Jinzong Mo; Haomin Zhang; Shengjun Lei; Ling Wang (Applied Clay Science, 2023)

Influencing factors of selenium transformation in a soil–rice system and prediction of selenium content in rice seeds: a case study in Ninghua County, Fujian Province - Ying Wang; Zhongfang Yang; Guoguang Chen; Long Zhan; Ming Zhang; Mo Zhou; Weikang Sheng (Environmental Science and Pollution Research, 2023)

A Global-Ocean-Data Assimilation for Operational Oceanography - Yinghao Qin; Qinglong Yu; Liying Wan; Yang Liu; Huier Mo; Yi Wang; Sujing Meng; Xiangyu Wu; Dandan Sui; Jiping Xie (Journal of Marine Science and Engineering, 2023)
In this study, a global-ocean-data-assimilation system based on the three-dimensional variational (3DVAR) scheme is built for operational oceanography. The available observations include satellite altimetry; the satellite-measured sea-surface temperature (SST); and T/S profiles from Argo floats, which are assimilated to provide the initial condition of the global-ocean forecasting. The statistical analysis methods are designed to assess the performance of the data-assimilation scheme, and the results show that the analysis SST fields agree well with OSTIA and MGDSST, and the corresponding root-mean-square errors are, respectively, 0.523 and 0.548 °C. Moreover, the analysis sea-surface-height fields are well represented at the middle and low latitudes and have a slightly greater difference in the regions with strong mesoscale eddies. The variations in the vertical distribution of the forecasting temperature profiles resemble those of the GTS buoy observation. The forecasting salinity profiles correspond well to GTS observations, except with a weaker cold bias between the depths 100 and 200 m (about 0.2 PSU) at buoy station 2901494. Overall, our 3DVAR assimilation system plays a significant role in improving the accuracy of analysis and forecasting fields for operational oceanography.

Coupling the recovery of spent lithium-ion batteries and the treatment of phenol wastewater: A “treating waste with waste” strategy - Siyuan Luo; Xuhui Zhu; Mengqi Gong; Ran Mo; Shun Yang (Chemosphere, 2023)

Cadmium affects the growth, antioxidant capacity, chlorophyll content, and homeostasis of essential elements in soybean plants - Jun Liu; Juan Ni; Aili Mo; Xinting Fan; Yuanyuan Jiang; Hongyan Xie; Jingsong Hu; Yunhua Zhu; Cuiying Peng; Fei Yang (South African Journal of Botany, 2023)

Flame behavior and temperature distribution of coupled fire induced by the interaction of hydrogen jet flame and pool flame - Liang Gong; Tianyu Mo; Xianwen Zheng; Yifei Han; Haoyu Wang; Xufeng Yang; Yuchun Zhang (Process Safety and Environmental Protection, 2023)

Identification and whole-genome sequencing of a bacterial strain isolated from healthy rice plants antagonistic to Magnaporthe oryzae - Hu Zhou; Xiao-jun Chen; Hai-di Liang; Mo-xiong Liu; Xue Zu; Yao-xiong Lu; Jia Zhou; Shun-ming Yang; Lian-fang Yu; Er-ming Liu; Zuo-hua Ren (Physiological and Molecular Plant Pathology, 2023)

Phylotranscriptomic analyses reveal deep gene tree discordance in Camellia (Theaceae) - Qiong Zhang; Ryan A. Folk; Zhi-Qiong Mo; Hang Ye; Zhao-Yuan Zhang; Hua Peng; Jian-Li Zhao; Shi-Xiong Yang; Xiang-Qin Yu (Molecular Phylogenetics and Evolution, 2023)

Sustainable management of water, nitrogen and biochar resources for soybean growth considering economic, environmental and resource use efficiency aspects: An integrated modeling approach - Pingan Zhang; Lu Li; Qiang Fu; Zhonglili Zhang; Haiyan Li; Li Zhao; Wuyuan Liu; Yijia Wang; Mo Li; Aizheng Yang (Journal of Cleaner Production, 2023)

Short-term effects of fine particulate matter constituents on myocardial infarction death - Shaocai Mo; Jianlin Hu; Chuanhua Yu; Junzhe Bao; Zhihao Shi; Peixuan Zhou; Zhiming Yang; Siqi Luo; Zhouxin Yin; Yunquan Zhang (Journal of Environmental Sciences, 2023)

Freezing enhances the killing of S. aureus by thymol via a unique bactericidal mechanism in cold chain food - Hongyan Zhang; Zhen Yang; Zhen Wang; Hongbo Li; Haizhen Mo; Shangchao Ma; Liangbin Hu; Xiaohui Zhou (Food Control, 2023)

Regulation of respiratory rate and storage quality of postharvest cauliflower based on gas permeability modification using gas barrier (GB) - gas conductor (GC) blending packaging - Gang Wu; Lifen Mo; Yuehua Fang; Hao Dong; Jian Peng; Weiling Wu; Xingfen Yang; Qi He (Food Packaging and Shelf Life, 2023)

Exploring the mechanism by which quercetin re-sensitizes breast cancer to paclitaxel: network pharmacology, molecular docking, and experimental verification - Ye Yang; Jiaoyan Yan; Jian Huang; Xiangyi Wu; Yan Yuan; Yan Yuan; Shu Zhang; Fei Mo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Divergent response of leaf unfolding to climate warming in subtropical and temperate zones - Haiying Yu; Lilin Yang; Zuhua Wang; Liang Guo; Changhui Peng; Qifu Yao; Zhongmei Mo; Tinghong Tan (Agricultural and Forest Meteorology, 2023)

Does the setting of local government economic growth targets promote or hinder urban carbon emission performance? Evidence from China - Mo Chen; Jijian Zhang; Zhe Xu; Xuhua Hu; Dianxi Hu; Guang Yang (Environmental Science and Pollution Research, 2023)

Dark background–surface enhanced Raman spectroscopic detection of nanoplastics: Thermofluidic strategy - Changmin Park; Dohyun Lim; Seung Mo Kong; Nam-Il Won; Yang Ho Na; Dongha Shin (Water Research, 2023)

Blockage effect and ground effect on oscillating hydrofoil - Hao Yang; Guanghua He; Weihao Mao; Weijie Mo; Hassan Ghassemi (Ocean Engineering, 2023)

Construction of cubic CaTiO3 perovskite modified by highly-dispersed cobalt for efficient catalytic degradation of psychoactive pharmaceuticals - Hangjun Zhang; Yunyi He; Mengfan He; Qiyue Yang; Guoyi Ding; Yuanshuai Mo; Zhiquan Liu; Panpan Gao (Journal of Hazardous Materials, 2023)

Excellent adsorption properties of Mg/Al/Fe LDOs for Cr(VI) in water - Wei Mo; Yang Yang; Chunyan He; Yuhua Huang; Jinpeng Feng (Journal of Environmental Chemical Engineering, 2023)

Application of super-cooled storage of aquatic products: A review - Xin-Yu Liu; Xue-Lai Zhang; Guan-Bang Wang; Fan-Yang Mo; Xin-Rong Zhang (International Journal of Refrigeration, 2023)

Photochemical transformation of terrestrial dissolved organic matter derived from multiple sources in tropical plantations - Gege Yin; Peng Zhang; Yinghui Wang; Bilal Aftab; Penghui Du; Qiang Zhang; Guoping Chen; Mengke Wang; Biwei Yang; Senhao Wang; Jiangming Mo; Wei Zhang; et al. (Geochimica et Cosmochimica Acta, 2023)

Rapid detection of foodborne pathogens in diverse foodstuffs by universal electrochemical aptasensor based on UiO-66 and methylene blue composites - Ge Dai; Handong Yao; Liuhong Yang; Yifeng Ding; Shuxin Du; Hui Shen; Fengfeng Mo (Food Chemistry, 2023)

An aqueous extract of Prunella vulgaris L. ameliorates cadmium-induced bone loss by promoting osteogenic differentiation in female rats - Lijun Mo; Linquan Chen; Yu Wan; Haibin Huang; Lifen Mo; Wei Zhu; Guangyu Yang; Ziyin Li; Qinzhi Wei; Jia Song; Xingfen Yang (Food and Chemical Toxicology, 2023)

Leaf senescence, nitrogen remobilization, and productivity of maize in two semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Fei Mo; Aziz Khan; Asfa Batool; Wei Zhang; Jun-Sheng Lu; Ying Zhu; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; et al. (European Journal of Agronomy, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

Tough, multifunctional, and green double-network binary solvent eutectogel with in-situ generation of lignin nanoparticles based on one-step dual phase separations for wearable flexible strain sensors - Jisheng Yang; Yawen Feng; Bingzhen Wang; Jianshuo Miao; Shihai Wei; Han Li; Liuting Mo; Zhiyong Qin (Chemical Engineering Journal, 2023)

Effect of dispersed species heterogeneity in carbon-based catalysts for near-infrared light-responsive synergistic antibacterial therapy - Yang Yang; Shudi Mo; Ze Zhang; Jingyu Sun; Jinghong Wen; Qilin Yu; Mingyang Liu (Chemical Engineering Journal, 2023)

Engineering chitin deacetylase AsCDA for improving the catalytic efficiency towards crystalline chitin - Guang Yang; Zhihong Hu; Yuhan Wang; Hongjuan Mo; Shu Liu; Xiaoyue Hou; Xudong Wu; Hong Jiang; Yaowei Fang (Carbohydrate Polymers, 2023)

Forest degradation caused by dwarf bamboo overabundance reduces soil C, N and P stocks in giant panda habitat - Li Mo; Hao Yang; Rong Hou; Wei Wu; Xinqiang Song; Hong Yang; Zhisong Yang; Weichao Zheng; Dunwu Qi (CATENA, 2023)

Grazing and reclamation-induced microbiome alterations drive organic carbon stability within soil aggregates in alpine steppes - Yang Hu; Guangling Yu; Jianqin Zhou; Kaihui Li; Mo Chen; Maidinuer Abulaizi; Mengfei Cong; Zailei Yang; Xinping Zhu; Hongtao Jia (CATENA, 2023)

Mitigation of N2O emissions via enhanced denitrification in a biological landfill leachate treatment using external carbon from fermented sludge - Kyeong Hwan Kang; Minseok Yang; Shahbaz Raza; Heejong Son; Young-Kwon Park; Jinhua Wang; Young Mo Kim (Chemosphere, 2023)

Marine debris ingestion by adults and fledglings of Swinhoe's storm petrels in the Republic of Korea - Miran Kim; Mi-jin Hong; Ki-baek Nam; Yang-mo Kim; Chang-uk Park; Youngsoo Kwon (Marine Pollution Bulletin, 2023)

Physical enrichment for improving welfare in fish aquaculture and fitness of stocking fish: A review of fundamentals, mechanisms and applications - Zonghang Zhang; Wuhan Lin; Yunqi Li; Xianyu Yuan; Xianqing He; Hancheng Zhao; Jiezhang Mo; Jianqing Lin; Liangliang Yang; Bo Liang; Xiumei Zhang; Wenhua Liu (Aquaculture, 2023)

Molecular cloning and characterization of STC1 gene and its functional analyses in yak (Bos grunniens) cumulus granulosa cells - Xue Yang; Jun Ma; Luoyu Mo; Yan Xiong; Xianrong Xiong; Daoliang Lan; Wei Fu; Shi Yin (Theriogenology, 2023)

Toxicity of exhaust emissions from high aromatic and non-aromatic diesel fuels using in vitro ALI exposure system - Henri Hakkarainen; Anssi Järvinen; Teemu Lepistö; Laura Salo; Niina Kuittinen; Elmeri Laakkonen; Mo Yang; Maria-Viola Martikainen; Sanna Saarikoski; Minna Aurela; Luis Barreira; Kimmo Teinilä; et al. (Science of The Total Environment, 2023)

Early Paleozoic subduction imprints of the Proto-Tethys Ocean: Evidence from the Appinite–Diorite–Granodiorite complex in East Kunlun, Northern Tibet - Yang-Ming Hu; Xiao-Wei Li; Xuan-Xue Mo; Lin Li; Kai Wang; Bing-Zhang Wang; Xiao-Ping Gong; Guo-Chen Dong; Yan-Bin Liu (Lithos, 2023)

Spatial variation in the community structure and response of benthic macroinvertebrates to multiple environmental factors in mountain rivers - Zaoli Yang; Shufeng He; Tao Feng; Yuqing Lin; Mo Chen; Qinyuan Li; Qiuwen Chen (Journal of Environmental Management, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Immobilization of Bacillus Thuringiensis and applicability in removal of sulfamethazine from soil - Shengfang Wen; Hunan Liu; Rui Yang; Lanjun Wang; Lusheng Zhu; Jun Wang; Young Mo Kim; Jinhua Wang (Environmental Pollution, 2023)

Study on the protective effect of RNA-binding motif protein 3 in mild hypothermia oxygen-glucose deprivation/reoxygenation cell model - Zhixuan Zhang; Xiaoxu Liu; Zhaocong Yang; Xuming Mo (Cryobiology, 2023)

Effect of intrinsic and extrinsic activity of electrocatalysts on anion exchange membrane water electrolyzer - Yoo Sei Park; Youngtae Park; Myeong Je Jang; Jooyoung Lee; Chiho Kim; Moon Gyu Park; Juchan Yang; Jungwoo Choi; Hyuck Mo Lee; Sung Mook Choi (Chemical Engineering Journal, 2023)

One-pot platform for the collection and detection of nanoparticles: Flexible surface-enhanced Raman scattering (SERS) substrates with nano-pore structure - Seung Mo Kong; Dongha Shin; Jeong-Wook Oh; Hyungseok Park; Jea Seung Lee; Nam-Il Won; Yang Ho Na (Chemical Engineering Journal, 2023)

Synergistic integration of MXene nanosheets with CdS@TiO2 core@shell S-scheme photocatalyst for augmented hydrogen generation - Vempuluru Navakoteswara Rao; Hyunguk Kwon; Yonghee Lee; Parnapalli Ravi; Chi Won Ahn; Kyeounghak Kim; Jun- Mo Yang (Chemical Engineering Journal, 2023)

Chinese “Scholars’ Stones”: a Potential Heritage Stone Resource Under Strong Anthropogenic Pressure - Weilun Kong; Yunhuai Li; Kongliang Li; Mo Chen; Yan Peng; Degao Wang; Lijun Chen; Linghong Ge; Pei Yang; Huiju Wu; Jifei Hu (Geoheritage, 2023)

Impact of rhizosphere priming on soil organic carbon dynamics: Insights from the perspective of carbon fractions - Hao Cui; Chaoyang Mo; Pengfei Chen; Rui Lan; Chao He; Jingdong Lin; Zhenhui Jiang; Jingping Yang (Applied Soil Ecology, 2023)

Characterization of the transcriptional responses of Armillaria gallica 012m to GA3 - Guolei Cai; Yapu Cao; Menghua Tian; Haiying Mo; Xin Chen; Zhihao Li; Qiaolin Ji; Kaixiang He; Gang Du; Haiying Yang (Archives of Microbiology, 2023)

Concatenating wide-parallax satellite orthoimages for simplified regional mapping via utilizing line-point consistency - Ziming Tu; Xiubin Yang; Zongqiang Fu; Suining Gao; Ge Yang; Li Jiang; Mo Wu; Shaoen Wang (International Journal of Remote Sensing, 2023)

The temporal and spatial variation of chlorophyll a concentration in the China Seas and its impact on marine fisheries - Kunlong Zhang; Xunbo Zhao; Jing Xue; Danqi Mo; Dongyu Zhang; Zhongyong Xiao; Wei Yang; Yingxu Wu; Yingfeng Chen (Frontiers in Marine Science, 2023)
Marine chlorophyll a is a key molecule for photosynthesis of marine plants and some plankton, which is important in marine ecosystems. This study utilized the chlorophyll a concentration data product observed by the MODIS sensor (MODerate resolution Imaging Spectroradiometer) to construct a long-term sequence of chlorophyll a concentration dataset by processing the raw data. Based on this, the multi-time-scale chlorophyll a concentration data was synthesized, and it was used to analyze the spatial and temporal variation characteristics of chlorophyll a concentration in China Seas. In addition, several oceanographic variables, including sea surface temperature, nutrients (phosphate, nitrate, silicate), partial pressure of seawater carbon dioxide, net primary productivity of the ocean, physical dynamics of seawater processes (mixed layer), were analyzed to ascertain their potential influence on chlorophyll a concentration. Finally, we analyzed the effects of changes in chlorophyll a concentration on marine fisheries. The result showed that: The average value of chlorophyll a concentration in China Seas from 2002 to 2022 was 0.874 mg/m 3 , with the highest concentration observed in the Bohai Sea area (4.547 mg/m 3 ) and the lowest in the South China Sea area (0.288 mg/m 3 ). The spatial variation of chlorophyll a concentration revealed an overall decrease of 0.0095 mg/m 3 in China Seas from 2002 to 2022. From the perspective of time changes, the concentration of chlorophyll a in China’s Bohai Sea area showed a downward trend from 2002 to 2022, while the Yellow Sea area showed an upward trend. The concentration remained relatively stable in the East China Sea area, whereas a significant declining trend was observed in the South China Sea area. The relationship between temperature and chlorophyll a concentration was non-linear, and chlorophyll a concentration showed some fluctuation or threshold effect with the change of seawater temperature. The three nutrient salts studied have a promoting effect on chlorophyll a, among which phosphate has the most obvious promoting effect on chlorophyll a. Chlorophyll a was negatively correlated with pCO 2 and positively correlated with ocean net primary productivity. Seasonal changes in the mixed layer had a significant effect on changes in the upper marine nutrients, which in turn affected changes in chlorophyll a concentration. Six of the eight types of algae studied show a trend toward deeper sea depths, which may have implications for the food availability of marine fish at different levels and pose new challenges for marine fisheries development.

Seasonal variation of inorganic carbon parameters and air–sea exchange of CO2 in Marian Cove, King George Island, Western Antarctic Peninsula - Ahra Mo; Keyhong Park; Eun Jin Yang; Jisoo Park; Tae-Wook Kim (Marine Pollution Bulletin, 2023)

Sex disparity in cognitive aging related to later-life exposure to ambient air pollution - Shaocai Mo; Yaqi Wang; Minjin Peng; Qun Wang; Hao Zheng; Yu Zhan; Zongwei Ma; Zhiming Yang; Linjiong Liu; Kejia Hu; Jian Cheng; Yao Yao; et al. (Science of The Total Environment, 2023)

Geochemistry of syntaxial calcite veins in ultra-deep sandstone reservoirs from the Kuqa depression, western China - Shunyu Wang; Keyu Liu; Jian Wang; Yong Li; Zhenkun Li; Haijun Yang; Tao Mo (Journal of Structural Geology, 2023)

Functionalized waterworks sludge particles as column packing materials for simultaneous Cr (Ⅵ) removal and oil separation - Yuhui Jiang; Qiong Tian; Hanlin Zhang; Qiyu Mo; Dongya Yang; Fengxian Qiu; Tao Zhang (Journal of Cleaner Production, 2023)

CdS/TiO2 nano hybrid heterostructured materials for superior hydrogen production and gas sensor applications - Vempuluru Navakoteswara Rao; Pasupuleti Kedhareswara Sairam; Moon-Deock Kim; Mashallah Rezakazemi; Tejraj M. Aminabhavi; Chi Won Ahn; Jun-Mo Yang (Journal of Environmental Management, 2023)

Flotation separation of coal dust from foundry dust enhanced by pre-soaking assisted mechanical stirring - Xiaolong Gong; Shengli Hu; Xinwang Liu; Mo Yang; Wenming Jiang; Zitian Fan (Journal of Environmental Management, 2023)

Assembly of understory woody communities during the close-to-nature restoration of a Pinus massoniana lamb. plantation in the southern subtropical region of China: From environmental filtering to competitive exclusion - Liuxin Huang; Xiaomei Pan; Jiangming Ma; Rui Jian; Hui Zhang; Kundong Bai; Yanhua Mo; Qiwei Zhang; Zhangqi Yang (Forest Ecology and Management, 2023)

Incorporation of spring maize into paddy fields increased nitrogen uptake in late rice by enhancing soil nitrogen supply: Field 15N tracer studies - Zhenhui Jiang; Hao Cui; Jingdong Lin; Chaoyang Mo; Yizhen Liu; Yongfu Li; Jingping Yang (Field Crops Research, 2023)

Thickness effects of polyethylene and biodegradable film residuals on soil properties and dryland maize productivity - Aimee Grace Uzamurera; Ze-Ying Zhao; Peng-Yang Wang; Yong-Xian Wei; Fei Mo; Rui Zhou; Wen-Li Wang; Fazal Ullah; Aziz Khan; Xiao-Bin Xiong; Meng-Ying Li; Kiprotich Wesly; et al. (Chemosphere, 2023)

Petrogenesis and dynamic significance of Miocene-Holocene alkali basalts in the southeastern Tibetan Plateau - Jingkai Wu; Hangshan Lei; Qian Ma; Zhidan Zhao; Fang-Zhen Teng; Shuangquan Zhang; Brian Cousens; Zhuang Miao; Yiyun Yang; Dong Liu; Qing Wang; Di-Cheng Zhu; et al. (Lithos, 2023)

Antibiotic resistance genes are closely linked with bacterial functions during anoxic-oxic treatment process of pig wastewater - Feng Huang; Chunhao Mo; Ze Cao; Yanli Pang; Yiwen Yang; Xindi Liao (Journal of Water Process Engineering, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Detection and counting of banana bunches by integrating deep learning and classic image-processing algorithms - Fengyun Wu; Zhou Yang; Xingkang Mo; Zihao Wu; Wei Tang; Jieli Duan; Xiangjun Zou (Computers and Electronics in Agriculture, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Channel migration in the northeastern margin of the Tibetan Plateau and its implication for fluvial response to the interaction between rapid tectonic activity, climatic fluctuation and human influence - Baotian Pan; Xiaohua Li; Zhenbo Hu; David Bridgland; Qinhong Mo; Zijuan Dong; Menghao Li; Yanan Yang; Rob Westaway; Guanghui Dong; Shanjia Zhang; Meiling Zhong (Quaternary Science Reviews, 2023)

Ocean ambient noise on the Chukchi Plateau and its environmental correlates - Xuejing Mo; Hongtao Wen; Yanming Yang; Hongtao Zhou; Jingwei Yin; Xiao Han; Hongxia Chen; Hailin Ruan (Marine Environmental Research, 2023)

Mineralogy and geochemistry of the Zedong Late Cretaceous (∼94 Ma) biotite granodiorite in the Southern Lhasa Terrane: Implications for the tectonic setting and Cu-Au mineralization - Weice Zhang; Zhidan Zhao; Dong Liu; Kunfeng Qiu; Qing Wang; Di-Cheng Zhu; Tiannan Yang; Yingchao Liu; Rui Wang; Zengqian Hou; Xuanxue Mo (Lithos, 2023)

Alkanolamines-activated steel slag for stabilization/solidification of heavy metal contaminated soil - Bin Zeng; Zhi Zhang; Shuo Yang; Liwu Mo; Fei Jin (Journal of Environmental Chemical Engineering, 2023)

Theoretical calculation guided molecularly imprinted polymer for selective adsorption of phloroglucinol - Ximin Chen; Long Jiang; Yaojie Liu; Lulu Zhang; Debin Yang; Xiaomeng Su; Zongjiang Yu; Mo Xian; Chao Xu (Journal of Environmental Chemical Engineering, 2023)

Bimetallic ordered mesoporous carbon from lignin for catalytic selective hydrogenation of levulinic acid to γ-valerolactone - Xiaoqi Wang; Xinhua Qi; Mo Qiu; Feng Shen; Jirui Yang; Boxiong Shen (Fuel, 2023)

An ultra-sensitive and selective electrochemical sensor based on GOCS composite and ion imprinted polymer for the rapid detection of Cd2+ in food samples - Fengqin Yin; Yeling Mo; Xueting Liu; Hongzhi Yang; Dianli Zhou; Hui Cao; Tai Ye; Fei Xu (Food Chemistry, 2023)

Chlorogenic acid alleviates oxidative damage in hepatocytes by regulating miR-199a-5p/GRP78 axis - Jiaxin Li; Hengju Ge; Yang Xu; Jiahong Xie; Naymul Karim; Fujie Yan; Jianling Mo; Wei Chen (Food Bioscience, 2023)

Ameliorative effect of Fructus Gardeniae against lipotoxicity associated hepatocytes injury through activating Nrf2 signaling pathway - Hengju Ge; Jiaxin Li; Yang Xu; Jiahong Xie; Naymul Karim; Fujie Yan; Jianling Mo; Wei Chen (Food Bioscience, 2023)

Curcumin alleviates lipid deposition in hepatocytes through miR-3666/AMPK axis regulation - Hengju Ge; Jiaxin Li; Yang Xu; Jiahong Xie; Naymul Karim; Fujie Yan; Jianling Mo; Wei Chen (Food Bioscience, 2023)

Achieving ultrahigh energy density and ultrahigh efficiency simultaneously via characteristic regulation of polar nanoregions - Leiyang Zhang; Mo Zhao; Yule Yang; Yang Li; Mingyang Tang; Dong Wang; Xiaoyong Wei; Gang Liu; Yan Yan; Li Jin (Chemical Engineering Journal, 2023)

Effect of Tyrosol Acyl Esters on the Antioxidant Status of Mussel ( Mytilus edulis ) Oil During Accelerated Oxidative Storage - Qian Wang; Mo-Tong Zhang; Xin-Miao Wang; Guan-Hua Zhao; Yuan-Yuan Hu; Fa-Wen Yin; Hui-Lin Liu; Xiao-Yang Liu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2023)

Research on the policy effect and mechanism of green finance to reduce environmental pollution: micro evidence from 285 cities in China - Xuehui Yang; Mo Wei; Yan Li; Yiming Jiang (Environmental Science and Pollution Research, 2023)

Evaluation of in vitro toxicity information for zebrafish as a promising alternative for chemical hazard and risk assessment - Jing Yang; Yolina Yu Lin Wang; Syed Shabi Ul Hassan Kazmi; Jiezhang Mo; Hailin Fan; Yuwen Wang; Wenhua Liu; Zhen Wang (Science of The Total Environment, 2023)

Deciphering mantle heterogeneity associated with ancient subduction-related metasomatism: Insights from Mg-K isotopes in potassic alkaline rocks - Zhuang Miao; Xiaoqiang Li; Zhidan Zhao; Yaoling Niu; Bo Xu; Hangshan Lei; Jingkai Wu; Yiyun Yang; Qian Ma; Dong Liu; Qing Wang; Di-Cheng Zhu; et al. (Geochimica et Cosmochimica Acta, 2023)

Upcycling of nickel iron slags to hierarchical self-assembled flower-like photocatalysts for highly efficient degradation of high-concentration tetracycline - Zhen Wu; Mengye Wang; Yang Bai; Han Song; Jiaxin Lv; Xiaofeng Mo; Xiaoqin Li; Zhang Lin (Chemical Engineering Journal, 2023)

Inhibiting N2O emissions and improving environmental benefits by integrating garlic growing in grain production systems - Dan Liu; Hongwei Dong; Chi Ma; Qin Mo; Bo Liu; Ahmad Irshad; Hui Li; Baoping Yang; RuiXia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (Agriculture, Ecosystems & Environment, 2023)

Endothelial hyperactivation of mutant MAP3K3 induces cerebral cavernous malformation enhanced by PIK3CA GOF mutation - Ran Huo; Yingxi Yang; Yingfan Sun; Qiuxia Zhou; Shaozhi Zhao; Zongchao Mo; Hongyuan Xu; Jie Wang; Jiancong Weng; Yuming Jiao; Junze Zhang; Qiheng He; et al. (Angiogenesis, 2023)

Multidimensional identification of single and regional meteorological drought considering flash‐season synthesis employed daily standardized effective precipitation and drought index in Guangxi, China - Yang Yun‐chuan; Yang Jia‐zhen; Tian Yi; Liao Li‐ping; Gan Ru‐min; Wang Wei‐quan; Wang Ting‐yan; Mo Chong‐xun; Li Xun‐gui; Sun Gui‐kai (International Journal of Climatology, 2023)
The frequent occurrence of extreme drought events in Guangxi has caused huge losses to human beings and economy in the region for many years. Therefore, this study adopted run theory and the objective identification method of regional extreme events (OITREE) and then carried out the comprehensive feature identification of multidimensional elements such as intensity, duration and area of meteorological drought events based on the daily standardized effective precipitation and drought index (SWAP) sequence of Guangxi from 1979 to 2018a. By comparing the evolutionary characteristics of drought elements identified by grid SWAP statistical analysis and OITREE, an integrated optimization scheme combining the accuracy of grid analysis and area identification is formed in this study. It was confirmed that the above two analysis methods had good correlation and consistency in revealing the evolution process of multidimensional elements of drought events. In terms of the frequency of drought events over a long period of time and the comprehensive characteristics of each element, the identification results of the OITREE method can better reveal the comprehensive characteristics of drought in Guangxi. Furthermore, the study found that flash droughts and seasonal droughts occurred alternately and were superimposed concurrently in Guangxi, and there were significant differences in the multidimensional spatial and temporal characteristics of these two types of droughts. Specifically, the frequency of flash drought was 1.60–4.00 times·(a) −1 , the duration varied from 20 to 60 days·(a) −1 and the concentration point of drought had a region‐wide dispersion; while the frequency of seasonal drought was 0.82–1.65 times·(a) −1 , the duration varied from 40–105 days·(a) −1 and the concentration point of drought had a local concentration. The research results can provide effective scientific support for operational drought refined forecast and early warning, and smart regulation of drought disaster risk.

Exposure to benzalkonium chloride disinfectants promotes antibiotic resistance in sewage sludge microbiomes - Kai Yang; Mo-Lian Chen; Dong Zhu (Science of The Total Environment, 2023)

An inorganic-organic-polymeric nanovehicle for targeting delivery of doxorubicin: Rational assembly, pH-stimulus release, and dual hyperthermia/chemotherapy of hepatocellular carcinoma - Jianying Yang; Zhao Wang; Chunhong Mo; Haikun Luo; Shuting Li; Qian Mo; You Qin; Fan Yang; Xinchun Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Characteristics and environmental and health impacts of volatile organic compounds in furniture manufacturing with different coating types in the Pearl River Delta - Yang Liu; Chunling Zeng; Meiyuan Wang; Xia Shao; Yijuan Yao; Guangqi Wang; Yinsong Li; Mo Hou; Liya Fan; Daiqi Ye (Journal of Cleaner Production, 2023)

The simulation, regulation capacity assessment and coping strategy of rainstorm runoff waterlogging in Zhu pai-chong Basin of Nanning, China - Qianyun Li; Yunchuan Yang; Haixiang Liao; Miaoqing Liu; Liping Liao; Shanqi Huang; Guikai Sun; Chongxun Mo; Xungui Li (Journal of Environmental Management, 2023)

A comprehensive assessment of runoff dynamics in response to climate change and human activities in a typical karst watershed, southwest China - Chongxun Mo; Shufeng Lai; Qing Yang; Keke Huang; Xingbi Lei; Lufeng Yang; Zhiwei Yan; Changhao Jiang (Journal of Environmental Management, 2023)

High-efficiency removal of Cs (I) by vermiculite/zinc hexacyanoferrate (II) composite from aqueous solutions - Tianya Dai; Jinpeng Feng; Jiann-Yang Hwang; Yangyang Bao; Chenhui Gao; Zeping Wang; Wei Mo; Xiujuan Su; Hongfei Lin (Journal of Environmental Chemical Engineering, 2023)

Development and characterization of EST-SSR markers in pecan (Carya illinoinensis) - Wenrui Lou; Yunzhou Lyu; Longjiao Hu; Xufeng Yang; Min Zhai; Jiping Xuan; Zhenghai Mo (Trees, 2023)

How the Wild Sugarcane Resource Miscanthus floridulus Responds to Low-Temperature Stress: A Physiological and Transcriptomic Analysis - Hong-Li Yang; Zhi-Jun Guo; Lu Jiang; Jun-Jun He; Qing Liu; Mo Chen; Xing-Hua Yu; Xian-Hong Wang; Qing-Hui Yang (Sugar Tech, 2023)

Regulation of Growth and Physiological Properties of Fragrant Rice Seedlings by Hydrogen-Rich Water (HRW) Under Nitrogen-Deficient Conditions - Ye Jiang; Qiuyi Ye; Lin Ma; Xiaojuan Yang; Jianwen Zhang; Zhaowen Mo (Journal of Plant Growth Regulation, 2023)

Nitrogen Modulates Grain Yield, Nitrogen Metabolism, and Antioxidant Response in Different Rice Genotypes - Gaoxin Liao; Yihan Yang; Wuming Xiao; Zhaowen Mo (Journal of Plant Growth Regulation, 2023)

Digestion and utilization of plant-based diets by transgenic pigs secreting β-glucanase, xylanase, and phytase in their salivary glands - Shanxin Yang; Tingting Liu; Jianxin Mo; Huaqiang Yang; Haoqiang Wang; Guangyan Huang; Gengyuan Cai; Zhenfang Wu; Xianwei Zhang (Transgenic Research, 2023)

Glycoside hydrolase family 5 gene Pp07886 in Pythium porphyrae: Identification, characterization, expression pattern, and activation of the host immunity - Huichao Yang; Peiwen Weng; Zaiduo Liu; Yongwei Yan; Lei Tang; Jie Li; Yunxiang Mao; Zhaolan Mo (Algal Research, 2023)

Elevated ozone enhances the network stability of rhizospheric bacteria rather than fungi - Zhengsheng Yu; Xin Chen; Feng Hua Zhai; Qun Gao; Xun Wen Chen; Xue Guo; Yansen Xu; Meng Ying Gao; Cehui Mo; Zhaozhong Feng; Yunfeng Yang; Hui Li (Agriculture, Ecosystems & Environment, 2023)

Freshwater crustacean exposed to active pharmaceutical ingredients: ecotoxicological effects and mechanisms - Jiahua Guo; Jingya Ren; Chao Chang; Qiannan Duan; Jun Li; Mirella Kanerva; Fangshe Yang; Jiezhang Mo (Environmental Science and Pollution Research, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Possible sites for a Chinese International Lunar Research Station in the Lunar South Polar Region - Teng Hu; Ze Yang; Mo Li; Carolyn H. van der Bogert; Zhizhong Kang; Xiaojian Xu; Harald Hiesinger (Planetary and Space Science, 2023)

Characterization of high amylose corn starch-cinnamaldehyde inclusion films for food packaging - Shoumei Wan; Qun Liu; Danmin Yang; Panjie Guo; Yahui Gao; Renli Mo; Yucang Zhang (Food Chemistry, 2023)

Cadmium contributes to atherosclerosis by affecting macrophage polarization - Yu Wan; Lijun Mo; Haibin Huang; Lifen Mo; Wei Zhu; Wenxue Li; Guangyu Yang; Linquan Chen; Yongning Wu; Jia Song; Xingfen Yang (Food and Chemical Toxicology, 2023)

Correction to: Systematic single-cell dissecting reveals heterogeneous oncofetal reprogramming in the tumor microenvironment of gastric cancer - Shaocong Mo; Xin Shen; Yulin Wang; YunPeng Liu; Takehito Sugasawa; ZongCheng Yang; Wenchao Gu; Takahito Nakajima (Human Cell, 2023)

Soil tillage rather than crop rotation determines assembly of the wheat rhizobacterial communities - Tong Li; Huanxin Xie; Zhangheng Ren; Yuting Hou; Deqiang Zhao; Weiyan Wang; Ziting Wang; Yang Liu; Xiaoxia Wen; Juan Han; Fei Mo; Yuncheng Liao (Soil and Tillage Research, 2023)

Research on health risk assessment of heavy metals in soil based on multi-factor source apportionment: A case study in Guangdong Province, China - Jiahui Liang; Zhaoyue Liu; Yiqi Tian; Huading Shi; Yang Fei; Jingxian Qi; Li Mo (Science of The Total Environment, 2023)

A quantitative model and controlling factors of secondary pore development for tight sandstone reservoirs in the carboniferous Benxi Formation, Ordos Basin, China - Jingyi Wang; Fujie Jiang; Qinhong Hu; Chunlin Zhang; Xiaoguang Yang; Wuling Mo; Xirong Wang; Zhenguo Qi (Marine and Petroleum Geology, 2023)

Adaptation of bacterial community in maize rhizosphere for enhancing dissipation of phthalic acid esters in agricultural soil - Yu-Hong Huang; Yu-Jie Yang; Xiaolian Wu; Cui-Lan Zhu; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2023)

Changes in Desulfovibrio desulfuricans sub sp EPS components and adsorption performance under exogenous sulfur induction and its mediation role in the biosynthesis of ZnS QDs - Yu Gan; Shuangnian Ma; Wencan Dai; Weifeng Song; Zeyang Lian; Xiangwu Huang; Rengao Yang; Zhihua Mo (Journal of Environmental Chemical Engineering, 2023)

Metabolomic profiles in a green alga (Raphidocelis subcapitata) following erythromycin treatment: ABC transporters and energy metabolism - Jiezhang Mo; Zhihua Ma; Shiwei Yan; Napo KM Cheung; Fangshe Yang; Xiunan Yao; Jiahua Guo (Journal of Environmental Sciences, 2023)

Microbiological analysis and characterization of Salmonella and ciprofloxacin-resistant Escherichia coli isolates recovered from retail fresh vegetables in Shaanxi Province, China - Chenyang Cao; Wenxing Zhao; Zexun Lü; Yixin Mo; Wei Hu; Shengyuan Sun; Huabin Cheng; Jiaqi Ma; Sirui Xiong; Xiaorong Jin; Hui Yang; Li Bai; et al. (International Journal of Food Microbiology, 2023)

Pyrolytic stage evolution mechanism of Zhundong coal based on reaction consistency analysis of mono/multi molecular models - Haihui Xin; Banghao Zhou; Wenjiang Tian; Xu-yao Qi; Mo Zheng; Wei Lu; He Yang; Xiaoxing Zhong; Deming Wang (Fuel, 2023)

Terpenoids from the roots of Chloranthus henryi Hemsl. var. hupehensis (Pamp.) K. F. Wu and their chemotaxonomic significance - Shuai Liu; Zi-Mo Zhang; Hui Yang; Yun-He Zou; Ning Wang; Peng-Yu Zhuang; Xiao-Xia Wang; Hang Liu (Biochemical Systematics and Ecology, 2023)

Microbial contribution to organic carbon accumulation in volcanic ash soils - Hye In Yang; Nuri Baek; Jin-Hyeob Kwak; Sang-Sun Lim; Young-Han Lee; Sang-Mo Lee; Woo-Jung Choi (Journal of Soils and Sediments, 2023)

Evaluation of reference genes for quantitative real-time PCR normalization in the Neopyropia (Pyropia) oomycete pathogen Pythium porphyrae - Huichao Yang; Yongwei Yan; Peiwen Weng; Congcong Sun; Jiaxing Yu; Lei Tang; Jie Li; Zhaolan Mo (Journal of Applied Phycology, 2023)

Molecular cloning and functional characterization of melanocortin-3 receptor in grass carp (Ctenopharyngodon idella) - Haolin Mo; Huixia Yu; Yang Li; Timothy P. C. Ezeorba; Zhihao Zhang; Mingxin Yao; Jiajia Yu; Dongmei Xiong; Haixia Liu; Lixin Wang (Fish Physiology and Biochemistry, 2023)

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

Divergence of epibacterial community assemblage correlates with malformation disease severity in Saccharina japonica seedlings - Yongwei Yan; Shanshan Wang; Kuimei Liu; Zhaolan Mo; Huichao Yang; Xiaojun Rong; Jie Li (Frontiers in Marine Science, 2023)
Malformation disease (MD) is one of the major constraints in the mariculture of the commercially important seaweed Saccharina japonica , which can cause severe losses of the kelp seedlings in the production process. However, the pathogenesis of MD remains largely undetermined. In this study, using cultivation experiments under laboratory conditions, MD severity was estimated for the young sporophytes of S. japonica , which were separately cultivated under different treatment conditions, including light intensity, duration of light exposure, and maturity level of the parent kelp. The associations between MD severity and epibacterial community divergence and assembly patterns were characterized. Higher MD severity significantly correlated with longer light exposure, and with both unmatured and overmatured parent kelp. The bacterial classes γ-Proteobacteria and α-Proteobacteria dominated all samples, but different MD severities were associated with different epibacterial communities. Comparisons of predicted functions for epibacterial communities revealed that longer light exposure led to a depletion in development and regeneration, while overmatured parent kelp resulted in a depletion in glycan biosynthesis and metabolism. Functional comparisons of the epibacterial communities between normal and unmatured parent kelp-generated seedlings revealed significantly different categories related to metabolism, environmental information processing, cellular processes, drug resistance, and bacterial infection. The significantly different pathways between groups, notably those related to bacterial infection and cellular processes, were partly consistent with the differences in bacterial compositions. The assembly of epiphytic bacterial communities was predominately governed by deterministic processes, and less impact was determined when there was significantly higher MD severity except when using overmatured parent kelp. Co-occurrence networks of the epibacterial communities associated with higher MD severity contained fewer nodes and exhibited lower modularity, but had higher graph density and degrees compared with those of seedlings with lower MD severity, indicating more complicated interactions. Nesterenkonia , Glycocaulis , Halomonas , Pseudoalteromonas , Pseudomonas , Loktanella , and Cobetia were frequently determined keystone taxa in communities associated with higher MD severity. The present study enhances our understanding of the factors significantly associated with MD severity and the potential roles of epimicrobiome in determining the disease severity, which will be useful for disease management in the future.

Systematic single-cell dissecting reveals heterogeneous oncofetal reprogramming in the tumor microenvironment of gastric cancer - Shaocong Mo; Xin Shen; Yulin Wang; YunPeng Liu; Takehito Sugasawa; ZongCheng Yang; Wenchao Gu; Takahito Nakajima (Human Cell, 2023)

Ecological function zoning based on ecosystem service bundles and trade-offs: a study of Dongjiang Lake Basin, China - Wenbo Mo; Yunlin Zhao; Nan Yang; Zhenggang Xu (Environmental Science and Pollution Research, 2023)

Co-exposure to phenols and phthalates during pregnancy with the difference of body size in twins at one month old - Hong Mei; Langjing Deng; Jinying Xie; Xiaojie Li; Nanxin Wu; Liqin Hu; Guangtong Huang; Fanyu Mo; Da Chen; Han Xiao; Pan Yang (Chemosphere, 2023)

Microbial one‑carbon and nitrogen metabolisms are beneficial to the reservoir recovery after cyanobacterial bloom - Zheng Yu; Xuan Peng; Lemian Liu; Jun R. Yang; Xingyu Zhai; Yuanyuan Xue; Yuanyuan Mo; Jun Yang (Science of The Total Environment, 2023)

Transcriptome analysis reveals the molecular mechanisms of Phragmites australis tolerance to CuO-nanoparticles and/or flood stress induced by arbuscular mycorrhizal fungi - Yihui Ban; Jiayuan Tan; Yang Xiong; Xiantong Mo; Yinghe Jiang; Zhouying Xu (Journal of Hazardous Materials, 2023)

Numerical study on the shock evolution and the spontaneous ignition of high-pressure hydrogen during its sudden release into the tubes with different angles - Liang Gong; Xianwen Zheng; Shengnan Yang; Yongzheng Yao; Yongliang Xie; Tianyu Mo; Yuchun Zhang (Fuel, 2023)

Porous Cobalt-nickel phosphides prepared from Al-doped NiCo-LDH precursors for supercapacitor and electrocatalysis applications - Ruonan Liu; Lulu Chen; Fei Mo; Haiyan Song; Guang Yang; Chunxia Chen; Xiaoliang Wu; Yichao Huang; Zhuangjun Fan (Chemical Engineering Journal, 2023)

Carbonate nanophase guided by terminally functionalized polyisoprene leading to a super tough, recyclable and transparent rubber - Mo-Kun Chen; Yi-Hai Zhao; Rong Zhang; Ying Yang; Jian Cao; Mao-Zhu Tang; Guangsu Huang; Yun-Xiang Xu (Chemical Engineering Journal, 2023)

Seeking and identifying time window of antibiotic treatment under in vivo guidance of PbS QDs clustered microspheres based NIR-II fluorescence imaging - Sijia Feng; Mo Chen; Yuzhou Chen; Liman Sai; Shixian Dong; Huizhu Li; Yimeng Yang; Jian Zhang; Xing Yang; Xiaogang Xu; Yuefeng Hao; Amr Mohamed Khair Hussein Abdou; et al. (Chemical Engineering Journal, 2023)

A cation-anion synergetic additive achieving long-term stability of lithium metal anode - Zhipeng Jiang; Chen Li; Jisheng Mo; Hanxu Yang; Hai-Wen Li; Qingan Zhang; Yongtao Li (Chemical Engineering Journal, 2023)

Highly exposed active sites of Au nanoclusters for photocatalytic CO2 reduction - Jianfeng Tian; Kang Zhong; Xingwang Zhu; Jinman Yang; Zhao Mo; Jinyuan Liu; Jiachao Dai; Yuanbin She; Yanhua Song; Huaming Li; Hui Xu (Chemical Engineering Journal, 2023)

A novel defined risk signature of endoplasmic reticulum stress-related genes for predicting the prognosis and immune infiltration status of ovarian cancer - Jiahang Mo; Shunyi Ruan; Baicai Yang; Yunfeng Jin; Keyi Liu; Xukai Luo; Hua Jiang (Journal of Zhejiang University-SCIENCE B, 2023)

Water-in-zircon: a discriminant between S- and I-type granitoid - Jing Mo; Xiao-Ping Xia; Peng-Fei Li; Christopher J. Spencer; Chun-Kit Lai; Jian Xu; Qing Yang; Ming-Dao Sun; Yang Yu; Luke Milan (Contributions to Mineralogy and Petrology, 2023)

Functionalized photosensitive metal-organic framework as a theranostic nanoplatform for turn-on detection of MicroRNA and photodynamic therapy - Chan Yang; Kun Wang; Shuo Tian; Liuting Mo; Weiying Lin (Analytica Chimica Acta, 2023)

Study on damage evolution and radon exhalation of uranium-bearing granite under high temperature - Yuying Hao; Fuliang Jiang; Biao Tan; Chao Zhang; Mian Zhang; Haoyu Li; Xiaotong Yang; Yixiang Mo; Tao Hu; Shiyan Li; Huiting He (Environmental Science and Pollution Research, 2022)

Design and Evaluation of a Machine Integrating Ridge-Breaking, Fertilizing, and Ridging for Ratoon Sugarcane Without Intertillage - Shang-Ping Li; Jia-Feng Pan; Jia-Qin Zhong; Wei Li; De-Quan Yang; Qing-Gui Mo (Sugar Tech, 2022)

Short-term exposure to fine particulate matter constituents and mortality: case-crossover evidence from 32 counties in China - Peixuan Zhou; Jianlin Hu; Chuanhua Yu; Junzhe Bao; Siqi Luo; Zhihao Shi; Yang Yuan; Shaocai Mo; Zhouxin Yin; Yunquan Zhang (Science China Life Sciences, 2022)

Gender-specific effects of prenatal mixed exposure to serum phthalates on neurodevelopment of children aged 2–3 years:the Guangxi Birth Cohort Study - Yuan Zheng; Longman Li; Hong Cheng; Shengzhu Huang; Xiuming Feng; Lulu Huang; Luyun Wei; Dehao Cao; Sida Wang; Long Tian; Weijun Tang; Caitong He; et al. (Environmental Science and Pollution Research, 2022)

Cerebral Small Vessel Disease: A Bibliometric Analysis - Wei Ma; Yi-Bao Yang; Ting-Ting Xie; Yi Xu; Na Liu; Xue-Ni Mo (Journal of Molecular Neuroscience, 2022)
Cerebral small vessel disease is a common neurological disease, and its incidence is increasing year by year worldwide. In recent years, research on cerebral small vessel disease has gained more and more attention. Our research aims to visualize publications to identify the hotspots and frontiers of cerebral small vessel disease research, and to provide reference and guidance for further research. Publications related to cerebral small vessel disease were searched from the Web of Science Core Collection and screened according to inclusion criteria. CiteSpace 5.8.R3 was used to evaluate and visualize results, including generating web maps and analyzing annual publications, countries, institutions, bibliographic and co-cited references, and keywords; in this article, we use CiteSpace and VOSviewer for the 2012 Cerebral small vessel disease and bibliometric analysis from January 1, 2022 to April 30, 2022. A total of 3037 papers related to cerebral small vessel disease were retrieved, and the number of published papers showed a steady upward trend. Among them, Neuroimaging standards for research into small vessel disease and its contribution to ageing and neurodegeneration, the most symbolic references in the field of cerebral small vessel disease have been cited a total of 438 times. Stroke is the most active journal (227 articles) and USA publishes up to 800 articles. Harvard Med SchUniv Edinburgh (133 papers) and Charidimou (85 papers) are the institutions and authors who have made the most contributions in this field, respectively. Among the keywords, most of them are related to the pathogenesis of cerebral small vessel disease. After 2018, gut-brain axis and cortex are the keywords with the strongest number of cited outbreaks. There is increasing evidence that cerebral small vessel disease is a research frontier and may remain a research hotspot in the future.

Regional water pollution management pathways and effects under strengthened policy constraints: the case of Tianjin, China - Yujia Wang; Mo Zhang; Chonggang Yang; Yan He; Meiting Ju (Environmental Science and Pollution Research, 2022)

Vasorin contributes to lung injury via FABP4-mediated inflammation - Xiaoping Guo; Junming Sun; Jinning Liang; Siran Zhu; Mingyuan Zhang; Lichao Yang; Xuejing Huang; Kangning Xue; Zhongxiang Mo; Sha Wen; Bing Hu; Jiajuan Liu; et al. (Molecular Biology Reports, 2022)

The responses and detoxification mechanisms of dark septate endophytes (DSE), Exophiala salmonis, to CuO nanoparticles - Yihui Ban; Jiayuan Tan; Yang Xiong; Xiantong Mo; Wenxuan Li; Chenyue Jia; Yiwen Ding; Zhouying Xu (Environmental Science and Pollution Research, 2022)

Effects of CYP24A1 polymorphisms on premature ejaculation: a case–control study - Fei Wang; Defan Luo; Jianxiang Chen; Cuiqing Pan; Zhongyao Wang; Housheng Fu; Jiangbing Xu; Meng Yang; Shaowei Mo; Liying Zhuang; Weifu Wang (Journal of Genetics, 2022)

Ectopic Expression of Erigeron breviscapus JAZ1 Affects JA-Induced Development Processes in Transgenic Arabidopsis - Mo Chen; Wei Zhang; Mi Yan; Simei He; Yingchun Lu; Guanghui Zhang; Bing Hao; Wei Fan; Yanru Hu; Shengchao Yang (Plant Molecular Biology Reporter, 2022)

Causal Effect of Genetically Determined Blood Copper Concentrations on Multiple Diseases: A Mendelian Randomization and Phenome-Wide Association Study - Xiuming Feng; Wenjun Yang; Lulu Huang; Hong Cheng; Xiaoting Ge; Gaohui Zan; Yanli Tan; Lili Xiao; Chaoqun Liu; Xing Chen; Zengnan Mo; Longman Li; et al. (Phenomics, 2022)

Removal of polybrominated diphenyl ethers in high impact polystyrene (HIPS) from waste TV sets - Xinran Guo; Shaohong Peng; Liwang Jiang; Xiaoning Mo; Yunhong Zhu; Yang Liu; Kaihan Cai; Qingbin Song (Environmental Science and Pollution Research, 2022)

The global biogeography of soil priming effect intensity - Chengjie Ren; Fei Mo; Zhenghu Zhou; Felipe Bastida; Manuel Delgado‐Baquerizo; Jieying Wang; Xinyi Zhang; Yiqi Luo; Timothy J. Griffis; Xinhui Han; Gehong Wei; Jun Wang; et al. (Global Ecology and Biogeography, 2022)
Aim Fresh carbon (C) inputs to the soil can have important consequences for the decomposition rates of soil organic matter (priming effect), thereby impacting the delicate global C balance at the soil–atmosphere interface. Yet, the environmental factors that control soil priming effect intensity remain poorly understood at a global scale. Location Global. Time period 1980–2020. Major taxa studied Soil priming effect intensity. Methods We conducted a global dataset of CO 2 effluxes in 711 pairwise soils with 13 C or 14 C simple C sources inputs and without C inputs from incubation experiments in which isotope‐labelled C was used to quantify fresh C‐induced rather than exudate‐induced priming. Results Soil priming effect intensity is predominantly positive. Soil texture and C content were identified as the most important factors associated with priming effects, with sandy soils from tropical and mid‐latitudes supporting the highest soil priming effect intensity, and soils with greater C content and fine textures from high latitudes maintaining the lowest soil priming effects. The negative association between C content and soil priming effect intensity was also indirectly driven by changing mean annual temperature, net primary productivity, and fungi : bacteria ratio. Using this information, we generated a global map of soil priming effect intensity, and found that the priming was lower at high latitudes and higher at lower latitudes. Main conclusions Global patterns of soil priming effect intensity can be predicted using environmental data, with soil texture and C content playing a predominant role in explaining in priming effects. These effects were also indirectly driven by climate, vegetation and soil microbial properties. We present the first global atlas of soil priming effect intensity and advance our knowledge on the potential mechanisms underlying soil priming effect intensity, which are integral to improving the climate change and soil C dynamics components of Earth System models.

Secular trends in global burden of diabetes attributable to particulate matter pollution from 1990 to 2019 - Kai Wang; Yunquan Zhang; Yaqi Wang; Jiaxin Liu; Peixuan Zhou; Yang Yuan; Zhouxin Yin; Shaocai Mo; Yong Yu; Minjin Peng (Environmental Science and Pollution Research, 2022)

Chaperone-mediated Autophagy Regulates Cell Growth by Targeting SMAD3 in Glioma - Hanqun Liu; Yuxuan Yong; Xingjian Li; Panghai Ye; Kai Tao; Guoyou Peng; Mingshu Mo; Wenyuan Guo; Xiang Chen; Yangfu Luo; Yuwan Lin; Jiewen Qiu; et al. (Neuroscience Bulletin, 2022)

Emergence and Seedling Establishment of Rice Varieties at Different Sowing Depths - Wenjing Yang; Daitianshu Xu; Shuying Li; Xiangru Tang; Shenggang Pan; Xiongfei Chen; Zhaowen Mo (Journal of Plant Growth Regulation, 2022)

The level of endogenous JA is critical for activation of SA- and JA-defensive signaling pathway in japonica rice cultivar Ziyu44 upon Magnaporthe oryzae infection - Xingyu An; Hui Zhang; Jinlu Li; Rui Yang; Qianchun Zeng; Mo Wang; Qiong Luo (Journal of Plant Pathology, 2022)

First report of postharvest anthracnose of mango fruit caused by Colletotrichum plurivorum in China - Mengmeng Lu; Zhini Yang; Li’an Ma; Qili Li; Suiping Huang; Lihua Tang; Tangxun Guo; Jianyou Mo; Tom Hsiang (Journal of Plant Pathology, 2022)

Exogenous ABA promotes aroma biosynthesis of postharvest kiwifruit after low-temperature storage - Xueyuan Han; Xiaoyu Wang; Chi Shen; Yiwei Mo; Rungang Tian; Linchun Mao; Zisheng Luo; Huanyi Yang (Planta, 2022)

Molecular and functional characterization of the retinol-binding protein 4 (RBP4) in hepatocytes of Schizothorax prenanti in response to palmitic acid - Yan Wang; Peng Zhu; Jiahui Ni; Qilang Mo; Wei Luo; Zongjun Du; Jun Jiang; Song Yang; Liulan Zhao; Quan Gong (Fish Physiology and Biochemistry, 2022)

The stress and deformation of stone column-improved soft clay by discrete element modelling - Meixiang Gu; Jie Cui; Jie Yuan; Yang Wu; Yadong Li; Haizhao Mo (European Journal of Environmental and Civil Engineering, 2022)

Comparison of the Variability of Small Extracellular Vesicles Derived from Human Liver Cancer Tissues and Cultured from the Tissue Explants Based on a Simple Enrichment Method - Jie Chen; Zhigang Jiao; Jianwen Mo; Defa Huang; Zhengzhe Li; Wenjuan Zhang; Tong Yang; Minghong Zhao; Fangfang Xie; Die Hu; Xiaoxing Wang; Xiaomei Yi; et al. (Stem Cell Reviews and Reports, 2022)
A potential use of small extracellular vesicles (sEVs) for diagnostic and therapeutic purposes has recently generated a great interest. sEVs, when purified directly from various tissues with proper procedures, can reflect the physiological and pathological state of the organism. However, the quality of sEV is affected by many factors during isolation, including separation of sEV from cell and tissues debris, the use of enzymes for tissue digestion, and the storage state of tissues. In the present study, we established an assay for the isolation and purification of liver cancer tissues-derived sEVs (tdsEVs) and cultured explants-derived sEVs (cedsEVs) by comparing the quality of sEVs derived from different concentration of digestion enzyme and incubation time. The nano-flow cytometry (NanoFCM) showed that the isolated tdsEVs by our method are purer than those obtained from differential ultracentrifugation. Our study thus establishes a simple and effective approach for isolation of high-quality sEVs that can be used for analysis of their constituents. Graphical abstract

Complete nucleotide sequence of a novel mycovirus infecting Rhizoctonia fumigata AG-Ba isolate C-314 Baishi - Yanqiong Li; Ping Xu; Lifang Zhang; Wurong Chen; Zhen Ren; Genhua Yang; Xiaohan Mo (Archives of Virology, 2022)

Complete nucleotide sequence of a novel alphapartitivirus from Rhizoctonia solani AG-4 HG III isolate SM03 - Yanqiong Li; Wurong Chen; Yanfen Niu; Ping Xu; Lifang Zhang; Shuhui Yu; Genhua Yang; Xiaohan Mo (Archives of Virology, 2022)

Impact of Sea Ice Melting on Summer Air-Sea CO2 Exchange in the East Siberian Sea - Ahra Mo; Eun Jin Yang; Sung-Ho Kang; Dongseon Kim; Kitack Lee; Young Ho Ko; Kitae Kim; Tae-Wook Kim (Frontiers in Marine Science, 2022)
The role of sea ice melting on the air-sea CO 2 flux was investigated at two ice camps in the East Siberian Sea of the Arctic Ocean. On average, sea ice samples from the two ice camps had a total alkalinity (TA) of ∼108 and ∼31 μmol kg –1 and a corresponding salinity of 1.39 and 0.36, respectively. A portion (18–23% as an average) of these sea ice TA values was estimated to exist in the sea ice with zero salinity, which indicates the excess TA was likely attributed to chemical (CaCO 3 formation and dissolution) and biological processes in the sea ice. The dilution by sea ice melting could increase the oceanic CO 2 uptake to 11–12 mmol m –2 d –1 over the next 21 days if the mixed layer depth and sea ice thickness were assumed to be 18.5 and 1.5 m, respectively. This role can be further enhanced by adding TA (including excess TA) from sea ice melting, but a simultaneous release of dissolved inorganic carbon (DIC) counteracts the effect of TA supply. In our study region, the additional impact of sea ice melting with close to unity TA:DIC ratio on air-sea CO 2 exchange was not significant.

Transcriptome analyses reveal the expression profile of genes related to lignan biosynthesis in Anthriscus sylvestris L. Hoffm. Gen - Chunmiao Shan; Liqiang Zhao; Yuanyuan Shi; Shengxiang Zhang; Huan Wu; Mo Yang; Qingshan Yang; Jiawen Wu (Physiology and Molecular Biology of Plants, 2022)

Land use types with different fertilization management affected isotope ratios of bulk and water-extractable C and N of soils in an intensive agricultural area - Young-Jae Jeong; Hyun-Jin Park; Byeong-Jun Jeon; Bo-Seong Seo; Nuri Baek; Hye In Yang; Jin-Hyeob Kwak; Sang-Mo Lee; Woo-Jung Choi (Journal of Soils and Sediments, 2022)

Functional characterization of melanocortin-3 receptor in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; Wei-Jia Song; Hui Wang; Hao-Lin Mo; Qiao Liu; Xin-Miao Zhang; Ze-Bin Jiang; Li-Xin Wang (Fish Physiology and Biochemistry, 2022)

Increased serum levels of cadmium are associated with an elevated risk of cardiovascular disease in adults - Siyu Ma; Jie Zhang; Cheng Xu; Min Da; Yang Xu; Yong Chen; Xuming Mo (Environmental Science and Pollution Research, 2022)

Complete genome sequence of a novel mitovirus from binucleate Rhizoctonia AG-K strain FAS2909W - Yanqiong Li; Yang Sun; Lei Yu; Wurong Chen; He Liu; Lifang Yin; Yingxia Guang; Genhua Yang; Xiaohan Mo (Archives of Virology, 2022)

A novel alphapartitivirus from binucleate Rhizoctonia fumigata AG-Ba isolate C-314 Baishi - Yanqiong Li; Yang Sun; Ping Xu; Lifang Zhang; Zebin Chen; Yanfen Niu; Genhua Yang; Xiaohan Mo (Archives of Virology, 2022)

Investigation of factors influencing the release of chloropropanols (3-MCPD and 1,3-DCP) from food contact paper - Huai-ning Zhong; Ying Zeng; Dao-yuan Yang; Ze-chun Wu; Dan Li; Hai-xia Sui; Jie Gao; Yan-fen Chen; Ce-Hui Mo (Food Additives & Contaminants: Part A, 2021)

A new glucopyranoside from the leaves of Microsorium fortunei - Mengqi Yan; Qin Luo; Xianli Zhou; Qinghu Mo; Caifeng Peng; Xiaoya Xian; Xiao Huang; Xinping Yang; Xu Chen; Chengqin Liang (Natural Product Research, 2021)

Application of hydrogen-rich water modulates physio-biochemical functions and early growth of fragrant rice under Cd and Pb stress - Lin Ma; Leilei Kong; Runfei Gui; Xiaojuan Yang; Jianwen Zhang; Qi Gong; Dejun Qin; Maosen Zhuang; Umair Ashraf; Zhaowen Mo (Environmental Science and Pollution Research, 2021)

Cadmium induces renal inflammation by activating the NLRP3 inflammasome through ROS/MAPK/NF-κB pathway in vitro and in vivo - Ziyin Li; Huiqin Chi; Wei Zhu; Guangyu Yang; Jia Song; Lijun Mo; Yitian Zhang; Yudi Deng; Feifei Xu; Jiani Yang; Zhini He; Xingfen Yang (Archives of Toxicology, 2021)

Effects of organic acids on the chemotaxis profiles and biocontrol traits of antagonistic bacterial endophytes against root-rot disease in Panax notoginseng - Li Ma; Wu-Qin Wang; Rui Shi; Xue-Mei Zhang; Xin Li; Yu-Sen Yang; Ming He Mo (Antonie van Leeuwenhoek, 2021)

Cytochalasins from endophytic Diaporthe sp. GDG-118 - Xishan Huang; Dexiong Zhou; Yan Liang; Xiaobo Liu; Fei Cao; Yuyue Qin; Tuxiang Mo; Zhaolong Xu; Jun Li; Ruiyun Yang (Natural Product Research, 2021)

Causal Relationship Between Complement C3, C4, and Nonalcoholic Fatty Liver Disease: Bidirectional Mendelian Randomization Analysis - Longman Li; Lulu Huang; Aimin Yang; Xiuming Feng; Zengnan Mo; Haiying Zhang; Xiaobo Yang (Phenomics, 2021)

Nuclear-localized eukaryotic translation initiation factor 1A is involved in mouse preimplantation embryo development - Yue Liu; Jiandong Sun; Yang Su; Jianmin Lin; Chengyu Lv; Kaien Mo; Songhua Xu; Shie Wang (Journal of Molecular Histology, 2021)

Seed Priming with Multiwall Carbon Nanotubes (MWCNTs) Modulates Seed Germination and Early Growth of Maize Under Cadmium (Cd) Toxicity - Jiale Chen; Xiaoyan Zeng; Wenjing Yang; Huijia Xie; Umair Ashraf; Zhaowen Mo; Jianhua Liu; Gaoke Li; Wu Li (Journal of Soil Science and Plant Nutrition, 2021)

N-3-(oxododecanoyl)-l-homoserine lactone suppresses dendritic cell maturation by upregulating the long noncoding RNA NRIR - Xuan Zhang; Yang Liu; Yang Lu; Song Li; Jianping Liu; Yunyan Zhang; Lina Wang; Mo Li; Yanfen Luo; Weizheng Zhang; Cha Chen; Youqiang Li (Journal of Biosciences, 2021)

Distribution and Exposure Risk Assessment of Perfluorinated Alkyl Substances in Aquatic Products along the Coastal Region of the South China Sea - Xu-Feng Wang; Meng-Song Mo; Hai-Gang Chen; Qiang Wang; Jin-Lan Yang; Dong-Hao Zhao (Exposure and Health, 2021)

Community structure of environmental microorganisms associated with COVID-19 affected patients - Weihua Zhang; Guoxin Mo; Jie Yang; Xingshuo Hu; Hujie Huang; Jing Zhu; Pei Zhang; Han Xia; Lixin Xie (Aerobiologia, 2021)
To clarify the characteristics and distribution of hospital environmental microbiome associated with confirmed COVID-19 patients. Environmental samples with varying degrees of contamination which were associated with confirmed COVID-19 patients were collected, including 13 aerosol samples collected near eight patients in different wards, five swabs from one patient’s skin and his personal belongings, and two swabs from the surface of positive pressure respiratory protective hood and the face shield from a physician who had close contact with one patient. Metagenomic next-generation sequencing (mNGS) was used to analyze the composition of the microbiome. One of the aerosol samples (near patient 4) was detected positive for COVID-19, and others were all negative. The environmental samples collected in different wards possessed protean compositions and community structures, the dominant genera including Pseudomonas , Corynebacterium , Neisseria , Staphylococcus , Acinetobacter , and Cutibacterium . Top 10 of genera accounted for more than 76.72%. Genera abundance and proportion of human microbes and pathogens radiated outward from the patient, while the percentage of environmental microbes increased. The abundance of the pathogenic microorganism of medical supplies is significantly higher than other surface samples. The microbial compositions of the aerosol collected samples nearby the patients were mostly similar to those from the surfaces of the patient's skin and personal belongings, but the abundance varied greatly. The positive rate of COVID-19 RNA detected from aerosol around patients in general wards was quite low. The ward environment was predominantly inhabited by species closely related to admitted patients. The spread of hospital microorganisms via aerosol was influenced by the patients’ activity.

Synthesis and biological evaluation of novel 1,3-diphenylurea quinoxaline derivatives as potent anticancer agents - Gui-Zhen Li; Xi-Lin Ouyang; Zu-Yu Mo; Yao Gu; Xiao-Lin Cao; Li Yang; Hai-Tao Tang; Ying-Ming Pan (Medicinal Chemistry Research, 2021)

A new triterpenoid from the leaves of Rhodomyrtus tomentosa (Ait.) Hassk - Qinghu Mo; Xianli Zhou; Sixin Huang; Yun Zhou; Junfei Mou; Qin Luo; Xiao Huang; Xinping Yang; Xu Chen; Chengqin Liang (Natural Product Research, 2021)

Associations Between Serum Multiple Metals Exposures and Metabolic Syndrome: a Longitudinal Cohort Study - Xiuming Feng; Longman Li; Lulu Huang; Haiying Zhang; Zengnan Mo; Xiaobo Yang (Biological Trace Element Research, 2021)

Off-the-Shelf, Immune-Compatible Human Embryonic Stem Cells Generated Via CRISPR-Mediated Genome Editing - Annie Kim; Kun-Gu Lee; Yeongbeen Kwon; Kang-In Lee; Heung-Mo Yang; Omer Habib; Jihun Kim; Sang-Tae Kim; Sung Joo Kim; Jin-Soo Kim; Dong-Youn Hwang (Stem Cell Reviews and Reports, 2021)
Human embryonic stem cells (hESCs) hold promise in regenerative medicine but allogeneic immune rejections caused by highly polymorphic human leukocyte antigens (HLAs) remain a barrier to their clinical applications. Here, we used a CRISPR/Cas9-mediated HLA-editing strategy to generate a variety of HLA homozygous-like hESC lines from pre-established hESC lines. We edited four pre-established HLA-heterozygous hESC lines and created a mini library of 14 HLA-edited hESC lines in which single HLA-A and HLA-B alleles and both HLA-DR alleles are disrupted. The HLA-edited hESC derivatives elicited both low T cell- and low NK cell-mediated immune responses. Our library would cover about 40% of the Asian-Pacific population. We estimate that HLA-editing of only 19 pre-established hESC lines would give rise to 46 different hESC lines to cover 90% of the Asian-Pacific population. This study offers an opportunity to generate an off-the-shelf HLA-compatible hESC bank, available for immune-compatible cell transplantation, without embryo destruction.

Programmed sequential cutting endows Cas9 versatile base substitution capability in plants - Wei Yang; Wei Qi; Yucai Li; Jiyao Wang; Yanmin Luo; Dehui Ding; Sudong Mo; Bo Chen; Yu Lu; Huarong Li; Linjian Jiang (Science China Life Sciences, 2021)

A New Approach to Embed Complex Fracture Network in Tight Oil Reservoir and Well Productivity Analysis - Jiaxiang Xu; Lifeng Yang; Zhe Liu; Yunhong Ding; Rui Gao; Zhen Wang; Shaoyuan Mo (Natural Resources Research, 2021)

Research advances in bioactive components and health benefits of jujube (Ziziphus jujuba Mill.) fruit - Yang Lu; Tao Bao; Jianling Mo; Jingdan Ni; Wei Chen (Journal of Zhejiang University-SCIENCE B, 2021)

Melatonin and Nitrogen Applications Modulate Early Growth and Related Physio-biochemical Attributes in Maize Under Cd Stress - Lin Ma; Zhuoli Huang; Shuying Li; Umair Ashraf; Wenjing Yang; Hecheng Liu; Daitianshu Xu; Wu Li; Zhaowen Mo (Journal of Soil Science and Plant Nutrition, 2021)

LINC00152 mediates CD8+ T-cell infiltration in gastric cancer through binding to EZH2 and regulating the CXCL9, 10/CXCR3 axis - Jinqing Ou; Pingguang Lei; Zhenling Yang; Man Yang; Lingmin Luo; Hongdan Mo; Guijin Luo; Junhui He (Journal of Molecular Histology, 2021)

Development and evaluation of a serological test for diagnosis of COVID-19 with selected recombinant spike proteins - Pingping Zhang; Qi Gao; Tang Wang; Yuehua Ke; Fei Mo; Ruizhong Jia; Wanbing Liu; Lei Liu; Shangen Zheng; Yuzhen Liu; Luping Li; Yao Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Generation of Hepatic Progenitor Cells from the Primary Hepatocytes of Nonhuman Primates Using Small Molecules - Da Hee Hong; Changhee Lee; Yohan Kim; Seung Bum Lee; Su-Cheol Han; Sung Joo Kim; Heung-Mo Yang; Dongho Choi; Jaemin Jeong; Kiyoung Ryu (Tissue Engineering and Regenerative Medicine, 2021)

Enhanced cerebro-cerebellar functional connectivity reverses cognitive impairment following electroconvulsive therapy in major depressive disorder - Qiang Wei; Yang Ji; Tongjian Bai; Meidan Zu; Yuanyuan Guo; Yuting Mo; Gongjun Ji; Kai Wang; Yanghua Tian (Brain Imaging and Behavior, 2021)

Microbial carbon-use efficiency and straw-induced priming effect within soil aggregates are regulated by tillage history and balanced nutrient supply - Fei Mo; Ye-Ye Zhang; Yang Liu; Yun-Cheng Liao (Biology and Fertility of Soils, 2021)

Natural polyketide 6-pentyl-2 H -pyrone-2-one and its synthetic analogues efficiently prevent marine biofouling - Mo Aqib Raza Khan; Bo-Wei Wang; Yih-Yu Chen; Ting-Hsuan Lin; Hsiu-Chin Lin; Yu-Liang Yang; Ka-Lai Pang; Chih-Chuang Liaw (Biofouling, 2021)

Feeding behaviors of a sea urchin, Mesocentrotus nudus, on six common seaweeds from the east coast of Korea - Kwon Mo Yang; Byung Hee Jeon; Hyung Geun Kim; Jeong Ha Kim (Algae, 2021)

Biogeography and co‐occurrence patterns of bacterial generalists and specialists in three subtropical marine bays - Yuanyuan Mo; Wenjing Zhang; David M. Wilkinson; Zheng Yu; Peng Xiao; Jun Yang (Limnology and Oceanography, 2021)
Recent research has greatly expanded our understanding of microbial metacommunities in aquatic ecosystems. However, patterns at the mesoscale are still poorly understood. We present the first simultaneous analyses of the biogeography and co‐occurrence patterns of generalists and specialists marine bacteria from three subtropical bays of China and test for signals of ecological processes (i.e., stochastic and deterministic processes) in biogeography and community assembly. Results showed that compared to specialists, bacterial generalists were less diverse, and were more widely dispersed in the three subtropical bays. Network analysis indicated that both habitat generalists and specialists showed non‐random co‐occurrence patterns, and specialists had a more complex co‐occurrence pattern than generalists. Further, specialists co‐occurrence network exhibited distinct robust structure compared to generalists, indicating that the both taxa showed different network stability. Our null models indicated that the generalists and specialists were primarily shaped by deterministic processes ‐ such as variable selection. However, deterministic processes played a greater role in the community variation of specialists (84%) than generalists (56%). The study has broadened our understanding of generalists and specialists distribution in the bacterioplankton; further revealing the dominant roles of similar ecological mechanisms (deterministic processes) in shaping the community assembly. The differences in complex and stable co‐occurrence pattern between generalists and specialists could be driven by deterministic processes. By considering the roles of species traits and ecological processes, we provide a deeper mechanistic understanding of bacterial biogeographical and co‐existence patterns.

Two new phthalide derivatives from the endophytic fungus Penicillium vulpinum isolated from Sophora tonkinensis - Yuyue Qin; Xiaobo Liu; Jing Lin; Jingying Huang; Xiaofei Jiang; Tuxiang Mo; Zhaolong Xu; Jun Li; Ruiyun Yang (Natural Product Research, 2021)

miR-19a mitigates hypoxia/reoxygenation-induced injury by depressing CCL20 and inactivating MAPK pathway in human embryonic cardiomyocytes - Qiang Fu; Tao-Ran Mo; Xiao-Yang Hu; Yin Fu; Ji Li (Biotechnology Letters, 2021)

Structural characteristics of central depression belt in deep-water area of the Qiongdongnan Basin and the hydrocarbon discovery of Songnan low bulge - Mo Ji; Qingbo Zeng; Haizhang Yang; Shuai Guo; Kai Zhong (Acta Oceanologica Sinica, 2021)

Complete Genome of Nocamycin-Producing Strain Saccharothrix syringae NRRL B-16468 Reveals the Biosynthetic Potential for Secondary Metabolites - Xuhua Mo; Song Yang (Current Microbiology, 2021)

Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Porphyry mineralization in the Tethyan orogen - Rui Wang; Dicheng Zhu; Qing Wang; Zengqian Hou; Zhiming Yang; Zhidan Zhao; Xuanxue Mo (Science China Earth Sciences, 2020)

Nitrogen Regulates the Grain Yield, Antioxidant Attributes, and Nitrogen Metabolism in Fragrant Rice Grown Under Lead-Contaminated Soil - Huoyi Feng; Yuzhan Li; Yangfan Yan; Xinhang Wei; Yihan Yang; Long Zhang; Lin Ma; Wu Li; Xiangru Tang; Zhaowen Mo (Journal of Soil Science and Plant Nutrition, 2020)

Evaluation and hydrological impact of land-use changes in the Longtan basin - Guiyan Mo; Yongxiang Zhang; Ya Huang; Chongxun Mo; Qing Yang (Journal of Earth System Science, 2020)

The Draft Genome Sequence and Analysis of an Efficiently Chitinolytic Bacterium Chitinibacter sp. Strain GC72 - Alei Zhang; Xiaofang Mo; Guoguang Wei; Ning Zhou; Sai Yang; Jie Chen; Yingying Wang; Kequan Chen; Pingkai Ouyang (Current Microbiology, 2020)

Molecular Cloning and Polymorphism Analysis of PmFGF18 from Pinctada fucata martensii - Ruijuan Hao; Chuchu Mo; Linda Adzigbli; Chuangye Yang; Yuewen Deng; Qingheng Wang (Journal of Marine Science and Engineering, 2020)
Fibroblast growth factor 18 (FGF18) plays an important functional role in skeletal growth and development. The FGF18 gene was characterized in pearl oyster Pinctada fucata martensii (PmFGF18) with the full-length sequence containing an open reading frame of 714 bp encoding 237 amino acids. The domain analysis of PmFGF18 showed a distinctive FGF domain, with a high similarity to FGF18 protein sequences from Crassostrea gigas (43.35%) and C. virginica (37.43%). PmFGF18 expression was revealed in all analyzed tissues with a significantly higher expression level in the fast-growing group than the slow-growing group. The analysis of PmFGF18 polymorphism demonstrated 33 SNPs (single nucleotide polymorphisms) in the CDS and promoter region of PmFGF18 sequence. Association analysis revealed 19 SNPs (2 SNPs from CDS and 17 SNPs from the promoter region) associating significantly with growth traits. Among the associated SNPs, one SNP g.50918198 A > C was verified in the other breeding line. Therefore, PmFGF18 can be utilized as a candidate gene for growth, and its related SNPs could be used in selective breeding of P. f. martensii for the improvement of growth traits.

Competition between fulvic acid and phosphate-mediated surface properties and transport of titanium dioxide nanoparticles in sand porous media - Shiqi Wang; Duo Li; Mo Zhang; Ming Chen; Nan Xu; Li Yang; Jianping Chen (Journal of Soils and Sediments, 2020)

Biomass, chemical composition, and microbial decomposability of rice root and straw produced under co-elevated CO2 and temperature - Hyun-Jin Park; Sang-Sun Lim; Jin-Hyeob Kwak; Kwang-Seung Lee; Hye In Yang; Han-Yong Kim; Sang-Mo Lee; Woo-Jung Choi (Biology and Fertility of Soils, 2020)

Safflower Yellow Improves Synaptic Plasticity in APP/PS1 Mice by Regulating Microglia Activation Phenotypes and BDNF/TrkB/ERK Signaling Pathway - Jie Pang; Jiawei Hou; Zhangjiuzhi Zhou; Mengqiao Ren; Yuyan Mo; Guang Yang; Zuwei Qu; Yanli Hu (NeuroMolecular Medicine, 2020)

Land-use type, and land management and disturbance affect soil δ15N: a review - Woo-Jung Choi; Jin-Hyeob Kwak; Hyun-Jin Park; Hye In Yang; Se-In Park; Zhihong Xu; Sang-Mo Lee; Sang-Sun Lim; Scott X. Chang (Journal of Soils and Sediments, 2020)

Soshiho-tang protects LPS-induced acute liver injury by attenuating inflammatory response - Seong Chul Jin; Mi Hye Kim; Si Yeon Jo; La Yoon Choi; Haesu Lee; Woong Mo Yang (Journal of Natural Medicines, 2020)

Genetic analysis and fine mapping of the gall midge resistance gene Gm5 in rice (Oryza sativa L.) - Hailian Zhou; Xinyi Wang; Yi Mo; Yang Li; Liuhui Yan; Zhihua Li; Wan Shu; Ling Cheng; Fengkuan Huang; Yongfu Qiu (Theoretical and Applied Genetics, 2020)

Characteristics and causes of the landslide on July 23, 2019 in Shuicheng, Guizhou Province, China - Siyuan Ma; Chong Xu; Xiwei Xu; Xiangli He; Haitao Qian; Qisong Jiao; Wei Gao; Huaining Yang; Yulong Cui; Pengfei Zhang; Kai Li; Hongrong Mo; et al. (Landslides, 2020)

Inhibitory effects of msFGFR2c on the epithelial-to-mesenchymal transition of AE2 cells in pulmonary fibrosis - Guo Jieming; Chuan Liu; Yin Yang; Shanyi Mo; Xuesong Yang; Ju Wang (Biotechnology Letters, 2020)
In interstitial fibrosis, alveolar epithelial type II (AE2) cells fail to repair damaged epithelium. However, whether this dysfunction is related to fibroblast growth factor (FGF) signal pathway and how it affects the fibrotic process remains unclear. In our study, the medium of the human foetal lung fibroblast cell line MRC-5 (Med) can induce epithelial-to-mesenchymal transition (EMT) in AE2 cells, we also found that TGF-β in Med can induce FGF-2 and CTGF expression in AE2 cells. TGF-β or CTGF exposure trigger a FGFR2 subtype b to c transition which can be supressed by siRNA-CTGF. All together, since FGFR2IIIc have the highest affinity with FGF-2 in all of the FGFRs, we indicate the activation of FGF2 signal pathway was induced by TGF-β, which is the key component of Med Here, we also find the inhibitory effect of msFGFR2c (S252W mutant of soluble FGFR2IIIc extracellular domain) on EMT of mouse primary AE2 cells in pulmonary fibrotic process. In a bleomycin-induced mouse pulmonary fibrosis model, msFGFR2c alleviate pulmonary fibrosis and suppress the decrease in pro-SPC levels. Thus, msFGFR2c can inhibit EMT-induced fibrosis of AE2 cells via FGF-2 signal and AE2 cells is suggested to play an important role in the lung fibrotic process.

Detail description of Lithophyllum okamurae (Lithophylloideae, Corallinales), a widely distributed crustose coralline alga in marine ecosystems - Qunju Hu; Fangfang Yang; Zhangliang Wei; Jiahao Mo; Chao Long; Xinpeng Tian; Lijuan Long (Acta Oceanologica Sinica, 2020)

Anti-clogging performance optimization for dentiform labyrinth emitters - Bin Yang; Jiandong Wang; Yanqun Zhang; Haitao Wang; Xiaopeng Ma; Yan Mo (Irrigation Science, 2020)

A cytokinin-activation enzyme-like gene improves grain yield under various field conditions in rice - Changgui Wang; Guokui Wang; Yang Gao; Guihua Lu; Jeffrey E. Habben; Guanfan Mao; Guangwu Chen; Jiantao Wang; Fan Yang; Xiaoqiang Zhao; Jing Zhang; Hua Mo; et al. (Plant Molecular Biology, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Characterization and application of a gall midge resistance gene (Gm6) from Oryza sativa ‘Kangwenqingzhan’ - Yang Li; Yi Mo; Zhihua Li; Meng Yang; Lihua Tang; Ling Cheng; Yongfu Qiu (Theoretical and Applied Genetics, 2020)

Analysis of Cerebrospinal Fluid Soluble TREM2 and Polymorphisms in Sporadic Parkinson’s Disease in a Chinese Population - Guoyou Peng; Jiewen Qiu; Hanqun Liu; Miaomiao Zhou; Shuxuan Huang; Wenyuan Guo; Yuwan Lin; Xiang Chen; Zhe Li; Guihua Li; Wenlong Zhang; Yunlong Zhang; et al. (Journal of Molecular Neuroscience, 2020)

Precise editing of myostatin signal peptide by CRISPR/Cas9 increases the muscle mass of Liang Guang Small Spotted pigs - Ruiqiang Li; Wu Zeng; Miao Ma; Zixuan Wei; Hongbo Liu; Xiaofeng Liu; Min Wang; Xuan Shi; Jianhua Zeng; Linfang Yang; Delin Mo; Xiaohong Liu; et al. (Transgenic Research, 2020)

Physiological performance of three calcifying green macroalgae Halimeda species in response to altered seawater temperatures - Zhangliang Wei; Jiahao Mo; Ruiping Huang; Qunju Hu; Chao Long; Dewen Ding; Fangfang Yang; Lijuan Long (Acta Oceanologica Sinica, 2020)

Comprehensive transcriptome analysis of faba bean in response to vernalization - Bei Gao; Xiao-Chun Bian; Feng Yang; Mo-Xian Chen; Debatosh Das; Xiu-Ru Zhu; Yong Jiang; Jianhua Zhang; Yun-Ying Cao; Chun-Fang Wu (Planta, 2020)

Compound C attenuates NLRP3 inflammasome despite AMPK knockdown in LPS plus palmitate-induced THP-1 cells - Yuxing Liu; Honghui He; Liangliang Fan; Jingjing Yuan; Hao Huang; Wenjun Yang; Linghao Wang; Zhaohui Mo; Fang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Development of a PCR method for detection of Pseudoalteromonas marina associated with green spot disease in Pyropia yezoensis - Huichao Yang; Yongwei Yan; Jie Li; Lei Tang; Yunxiang Mao; Zhaolan Mo (Journal of Oceanology and Limnology, 2020)

Numerical simulation and field experiment study on onboard dust removal technology based on airflow–dust pollution dispersion characteristics - Jinming Mo; Junlei Yang; Wei Ma; Fang Chen; Sheji Zhang (Environmental Science and Pollution Research, 2020)

Concurrent amygdalar and ventromedial prefrontal cortical responses during emotion processing: a meta-analysis of the effects of valence of emotion and passive exposure versus active regulation - Mo Yang; Shang-Jui Tsai; Chiang-Shan R. Li (Brain Structure and Function, 2020)

Moult and plumage patterns of the critically endangered Yellow-breasted Bunting (Emberiza aureola) at a stopover site in Korea - Jong-Gil Park; Chang-Uk Park; Kyoung-Soon Jin; Yang-Mo Kim; Hee-Young Kim; Si-Yun Jeong; Dongh-Ha Nam (Journal of Ornithology, 2020)

Fighting against fall armyworm by using multiple genes pyramiding and silencing (MGPS) technology - Maozhi Ren; Muhammad Mubashar Zafar; Huijuan Mo; Zhaoen Yang; Fuguang Li (Science China Life Sciences, 2019)

The Rpf84 gene, encoding a ribosomal large subunit protein, RPL22, regulates symbiotic nodulation in Robinia pseudoacacia - Zhao Feng; Lu Zhang; Yuanyuan Wu; Li Wang; Mingying Xu; Mo Yang; Yajuan Li; Gehong Wei; Minxia Chou (Planta, 2019)

Structural control, seismic expression, and types of reefs of rifting margins in the late Permian Changxing Age, Sichuan Basin, China - Mo Wuling; Su Nan; Wei Guoqi; Yang Wei; Liu Mancang; Xing Fengcun (Arabian Journal of Geosciences, 2019)

In Vivo Measurement of Plantar Tissue Characteristics and Its Indication for Foot Modeling - Fuhao Mo; Junjie Li; Zurong Yang; Shuangyuan Zhou; Michel Behr (Annals of Biomedical Engineering, 2019)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

First report of sheath rot caused by Fusarium proliferatum on Pisang Awak Banana (Musa ABB) in China - Sui-Ping Huang; Ji-Guang Wei; Tang-Xun Guo; Qi-Li Li; Li-Hua Tang; Jian-You Mo; Ji-Feng Wei; Xiao-Bing Yang (Journal of Plant Pathology, 2019)

Ginsenoside compound K ameliorates Alzheimer’s disease in HT22 cells by adjusting energy metabolism - Xijun Chen; Hui Li; Qing Yang; Xingcheng Lan; Jifeng Wang; Zhanhong Cao; Xiaozheng Shi; Jing Li; Mo Kan; Xiaobo Qu; Na Li (Molecular Biology Reports, 2019)

Occurrence and formation of halobenzoquinones in indoor and outdoor swimming pool waters of Nanning City, Southwest China - Huan Wu; Kunling Long; Du Lu; Yan Mo; Qiyuan Yang; Xiao Wei (Environmental Science and Pollution Research, 2019)

Associations between mercury exposure and the risk of nonalcoholic fatty liver disease (NAFLD) in US adolescents - Runsen Chen; Yang Xu; Cheng Xu; Yaqin Shu; Siyu Ma; Changgui Lu; Xuming Mo (Environmental Science and Pollution Research, 2019)

Occurrence of Bryde's whales, Balaenoptera edeni , in the northern Beibu Gulf, China - Mo Chen; Shiang‐Lin Huang; Haiping Wu; Zhigang Mei; Yiwen Chen; Jingsong Zheng; Wen Cheng; Keshun Deng; Chengteng Yang; Mao Chen; Chun‐Chieh Wang; Derun Lin; et al. (Marine Mammal Science, 2019)

Long‐term nitrogen addition modifies microbial composition and functions for slow carbon cycling and increased sequestration in tropical forest soil - Jing Tian; Jennifer A. J. Dungait; Xiankai Lu; Yunfeng Yang; Iain P. Hartley; Wei Zhang; Jiangming Mo; Guirui Yu; Jizhong Zhou; Yakov Kuzyakov (Global Change Biology, 2019)
Nitrogen (N) deposition is a component of global change that has considerable impact on belowground carbon (C) dynamics. Plant growth stimulation and alterations of fungal community composition and functions are the main mechanisms driving soil C gains following N deposition in N‐limited temperate forests. In N‐rich tropical forests, however, N deposition generally has minor effects on plant growth; consequently, C storage in soil may strongly depend on the microbial processes that drive litter and soil organic matter decomposition. Here, we investigated how microbial functions in old‐growth tropical forest soil responded to 13 years of N addition at four rates: 0 (Control), 50 (Low‐N), 100 (Medium‐N), and 150 (High‐N) kg N ha −1 year −1 . Soil organic carbon (SOC) content increased under High‐N, corresponding to a 33% decrease in CO 2 efflux, and reductions in relative abundances of bacteria as well as genes responsible for cellulose and chitin degradation. A 113% increase in N 2 O emission was positively correlated with soil acidification and an increase in the relative abundances of denitrification genes ( narG and norB ). Soil acidification induced by N addition decreased available P concentrations, and was associated with reductions in the relative abundance of phytase. The decreased relative abundance of bacteria and key functional gene groups for C degradation were related to slower SOC decomposition, indicating the key mechanisms driving SOC accumulation in the tropical forest soil subjected to High‐N addition. However, changes in microbial functional groups associated with N and P cycling led to coincidentally large increases in N 2 O emissions, and exacerbated soil P deficiency. These two factors partially offset the perceived beneficial effects of N addition on SOC storage in tropical forest soils. These findings suggest a potential to incorporate microbial community and functions into Earth system models considering their effects on greenhouse gas emission, biogeochemical processes, and biodiversity of tropical ecosystems.

Decision Support System Based on Queuing Theory to Optimize Canal Management - Gaiqiang Yang; Mo Li; Lijuan Huo (Water Resources Management, 2019)

Effect of an incremental change in external water pressure on tunnel lining: a case study from the Tongxi karst tunnel - Yang Liu; Yongneng Feng; Mo Xu; Yunhui Zhang; Haitao Long; Haiming Zhu (Natural Hazards, 2019)

Identification, evolution and alternative splicing profile analysis of the splicing factor 30 (SPF30) in plant species - Di Zhang; Jing-Fang Yang; Bei Gao; Tie-Yuan Liu; Ge-Fei Hao; Guang-Fu Yang; Li-Jun Fu; Mo-Xian Chen; Jianhua Zhang (Planta, 2019)

Molecular cloning and expression analysis of SRLK1 gene in self-incompatible Asteraceae species Erigeron breviscapus - Wei Zhang; Mo Chen; Heng-ling Meng; Jin Yang; Xiang Wei; Sheng-chao Yang (Molecular Biology Reports, 2019)

Safflower yellow attenuates learning and memory deficits in amyloid β-induced Alzheimer’s disease rats by inhibiting neuroglia cell activation and inflammatory signaling pathways - Lu Zhang; Zhangjiuzhi Zhou; Wei Zhai; Jie Pang; Yuyan Mo; Guang Yang; Zuwei Qu; Yanli Hu (Metabolic Brain Disease, 2019)

Acetone adsorption capacity of sulfur-doped microporous activated carbons prepared from polythiophene - Junchao Zhu; Ruofei Chen; Zheng Zeng; Changqing Su; Ke Zhou; Yamian Mo; Yang Guo; Fan Zhou; Jie Gao; Liqing Li (Environmental Science and Pollution Research, 2019)

Acidosis promotes tumorigenesis by activating AKT/NF-κB signaling - Liu Yang; Xiaoge Hu; Yin-Yuan Mo (Cancer and Metastasis Reviews, 2019)

Geochronology, geochemistry and Sr-Nd-Pb-Hf isotopes of the Early Paleogene gabbro and granite from Central Lhasa, southern Tibet: petrogenesis and tectonic implications - Yun-hui Zhang; Hua-wen Cao; Steven P. Hollis; Li Tang; Mo Xu; Jun-sheng Jiang; Shun-bao Gao; Yang-shuang Wang (International Geology Review, 2019)

Phycocyanin fluorescent probe from Arthrospira platensis: preparation and application in LED-CCD fluorescence density strip qualitative detection system - Yunquan Zheng; Liuda Mo; Wenyi Zhang; Yunjian Duan; Jiandong Huang; Chengqun Chen; Yueming Gao; Xianai Shi; Feng Li; Jianmin Yang; Yanghao Guo (Journal of Applied Phycology, 2019)

Quantitative Vulnerability Model of Earth Dam Overtopping and its Application - Chong-Xun Mo; Gui-Yan Mo; Liu Peng; Qing Yang; Xin-Rong Zhu; Qing-Ling Jiang; Ju-Liang Jin (Water Resources Management, 2019)

Assessing Changes of Habitat Quality for Shorebirds in Stopover Sites: a Case Study in Yellow River Delta, China - Xiaowei Li; Xiyong Hou; Yang Song; Kai Shan; Shuyu Zhu; Xiubo Yu; Xunqiang Mo (Wetlands, 2019)

Composition and antioxidant and antibacterial activities of essential oils from three yellow Camellia species - Li Ge; Binghui Lin; Jianguang Mo; Qiuhong Chen; Lin Su; Yuejuan Li; Kedi Yang (Trees, 2019)

Genome-wide identification and functional analysis of the splicing component SYF2/NTC31/p29 across different plant species - Yuan Tian; Mo-Xian Chen; Jing-Fang Yang; H. H. K. Achala; Bei Gao; Ge-Fei Hao; Guang-Fu Yang; Zhi-Yong Dian; Qi-Juan Hu; Di Zhang; Jianhua Zhang; Ying-Gao Liu (Planta, 2019)

Sorption of Pb in chemical and particle-size fractions of soils with different physico-chemical properties - Hyun-Jung Park; Hyun-Jin Park; Hye In Yang; Se-In Park; Sang-Sun Lim; Jin-Hyeob Kwak; Goon-Taek Lee; Sang-Mo Lee; Man Park; Woo-Jung Choi (Journal of Soils and Sediments, 2019)

Ginsenoside Compound K Regulates Amyloid β via the Nrf2/Keap1 Signaling Pathway in Mice with Scopolamine Hydrobromide-Induced Memory Impairments - Qing Yang; Jianan Lin; Huiyuan Zhang; Yingna Liu; Mo Kan; Zhiru Xiu; Xijun Chen; Xingcheng Lan; Xiaohua Li; Xiaozheng Shi; Na Li; Xiaobo Qu (Journal of Molecular Neuroscience, 2019)

Geraniin promotes osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) via activating β-catenin: a comparative study between BMSCs from normal and osteoporotic rats - Jiao Mo; Renhua Yang; Fan Li; Bo He; Xiaochao Zhang; Yuqin Zhao; Zhiqiang Shen; Peng Chen (Journal of Natural Medicines, 2019)

Genetic diversity, population structure and identification of Dendrobium cultivars with high polysaccharide contents using SCoT, SCAR and nested PCR markers - Qingguo Li; Jianmei Mo; Wenru Wu; Juan Yang; Jinjin Li; Tianxing Lai; Zhanlun Ou; Zhenwen Qiu; Shixia Guan; Junjie Liao (Genetic Resources and Crop Evolution, 2019)

Nitrogen-doped porous carbon derived from chitosan for the enhanced dehydrochlorination of lindane under mild conditions - Jirui Yang; Feng Shen; Mo Qiu; Xinhua Qi (Environmental Science and Pollution Research, 2018)

Efficient generation of functional cardiomyocytes from human umbilical cord-derived virus-free induced pluripotent stem cells - Kai Hong Wu; Su Yun Wang; Qian Ru Xiao; Yu Yang; Ning Ping Huang; Xu Ming Mo; Jian Sun (Cell and Tissue Research, 2018)

Exposure to intermittent hypoxia impairs learning and memory ability in rats - Feng Zhang; Zhuo Tian; Sufen Peng; Jie Li; Xiang Yang; Hailan Mo; Jian Tan; Hongbing Yao; Bing Li (Sleep and Biological Rhythms, 2018)

Effect of nicotine from tobacco root exudates on chemotaxis, growth, biocontrol efficiency, and colonization by Pseudomonas aeruginosa NXHG29 - Li Ma; Shuai Chao Zheng; Ti Kun Zhang; Zi Yi Liu; Xue Jian Wang; Xing Kui Zhou; Cheng Gang Yang; Jin Ling Duo; Ming He Mo (Antonie van Leeuwenhoek, 2018)

Evaluation of the protective effect of a prime-boost strategy with plasmid DNA followed by recombinant adenovirus expressing BmAMA1 as vaccines against Babesia microti infection in hamster - Guanbo Wang; Longzheng Yu; Artemis Efstratiou; Paul Franck Adjou Moumouni; Mingming Liu; Huanping Guo; Yang Gao; Shinuo Cao; Mo Zhou; Jixu Li; Aaron Edmond Ringo; Xuenan Xuan (Acta Parasitologica, 2018)
In the present study, we have investigated the protective effect of a heterologous prime-boost strategy with priming plasmid DNA followed by recombinant adenovirus, both expressing BmAMA1, against Babesia microti infection. Four groups consisting of 3 hamsters per group were immunized with pBmAMA1/Ad5BmAMA1, pNull/Ad5BmAMA1, pBmAMA1/Ad5Null and pNull/Ad5Null, followed by challenge infection with B . microti . Our results showed that hamsters immunized with plasmid and adenovirus expressing BmAMA1 developed a robust IgG and IgG2a antibody response against BmAMA1, suggesting the DNA vaccine or viral vector vaccine tend to induce a Th1-biased response. Compared to the control hamsters, the hamsters vaccinated either with the prime-boost strategy or one of the two “vaccines” exhibited no significant protection against B . microti challenge. Although a slight difference in terms of parasitemia and hematocrit values at days 14–16 post challenge infection was observed, no other statistical difference was detected. Our results indicate that the prime-boost vaccination strategy of injection of plasmid and adenovirus expressing BmAMA1 is not efficient in protecting against B . microti infection.

Variation in accumulation, transport, and distribution of phthalic acid esters (PAEs) in soil columns grown with low- and high-PAE accumulating rice cultivars - Yang Wu; Xue-Xue Chen; Ting-Kai Zhu; Xing Li; Xiao-Hong Chen; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Postnatal Subacute Benzo(a)Pyrene Exposure Caused Neurobehavioral Impairment and Metabolomic Changes of Cerebellum in the Early Adulthood Period of Sprague-Dawley Rats - Chunlin Li; Jing Wang; Qiuping Su; Kai Yang; Chengzhi Chen; XueJun Jiang; Tingli Han; Shuqun Cheng; Tingting Mo; Ruiyuan Zhang; Bin Peng; Yuming Guo; et al. (Neurotoxicity Research, 2018)

The application of unmanned aircraft systems to plant protection in China - Shulin Yang; Xiaobing Yang; Jianyou Mo (Precision Agriculture, 2018)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

The development and evolution of landform based on neotectonic movement: The Sancha river catchment in the southwestern China - Lingmin Zhong; Mo Xu; Yanna Yang; Xingbing Wang (Journal of Earth System Science, 2018)

Modification of chitosan/calcium alginate/Fe3O4 hydrogel microsphere for enhancement of Cu(II) adsorption - Xiaofeng Yi; Meixia Yang; Liuda Mo; Wenkai Xu; Shuai Wang; Jiarui He; Junjie Gu; Minrui Ou; Xiaoping Xu (Environmental Science and Pollution Research, 2018)

Tectono-thermal evolution of the Liwan Sag, deepwater area in the Zhujiang River Mouth Basin, northern South China Sea - Xiaoyin Tang; Shaopeng Huang; Shuchun Yang; Guangzheng Jiang; Mo Ji; Shengbiao Hu (Acta Oceanologica Sinica, 2018)

Effects of disturbance timing on community recovery in an intertidal habitat of a Korean rocky shore - Hyun Hee Kim; Young Wook Ko; Kwon Mo Yang; Gunhee Sung; Jeong Ha Kim (Algae, 2017)

Peripheral Lymphocyte Subsets as a Marker of Parkinson’s Disease in a Chinese Population - Luan Cen; Chaohao Yang; Shuxuan Huang; Miaomiao Zhou; Xiaolu Tang; Kaiping Li; Wenyuan Guo; Zhuohua Wu; Mingshu Mo; Yousheng Xiao; Xiang Chen; Xinling Yang; et al. (Neuroscience Bulletin, 2017)

Comparative transcriptomes and reciprocal best hit analysis revealed potential pigment genes in two color forms of Tetranychus urticae - Yi-Dan Mo; Si-Xia Yang; Jing-Yu Zhao; Peng-Yu Jin; Xiao-Yue Hong (Experimental and Applied Acarology, 2017)

Bacillus zanthoxyli sp. nov., a novel nematicidal bacterium isolated from Chinese red pepper (Zanthoxylum bungeanum Maxim) leaves in China - Ma Li; Cao Yong Hong; Wang Xiao Yan; Zheng Shuai Chao; Yang Cheng Gang; Duo Jin Ling; Zhou Xing Kui; Xi Jia Qin; Zhu Ming Liang; Mo Ming He (Antonie van Leeuwenhoek, 2017)

Single Nucleotide Polymorphisms in SLC19A1 and SLC25A9 Are Associated with Childhood Autism Spectrum Disorder in the Chinese Han Population - Jun Liu; Weiming Mo; Zengyu Zhang; Hong Yu; Aiping Yang; Fei Qu; Pingfang Hu; Zhuo Liu; Shihu Wang (Journal of Molecular Neuroscience, 2017)

Effect of CD40/CD40L signaling on IL-10-producing regulatory B cells in Chinese children with Henoch-Schönlein purpura nephritis - Baohui Yang; Xiongjun Tan; Xiao Xiong; Daoqi Wu; Gaofu Zhang; Mo Wang; Shifang Dong; Wei Liu; Haiping Yang; Qiu Li (Immunologic Research, 2017)

An R version of FPTest for testing differences in allelic count - Mo-Hua Yang; Yong-Bi Fu (Conservation Genetics Resources, 2017)

Modeling of Coal Fine Migration During CBM Production in High-Rank Coal - Su-Yang Zhu; Xiao-Long Peng; Zhi-Min Du; Chao-Wen Wang; Peng Deng; Fei Mo; Yu Lei; Mingwei Wang (Transport in Porous Media, 2017)

MiRNA-145 suppresses lung adenocarcinoma cell invasion and migration by targeting N-cadherin - Dongping Mo; Daheng Yang; Xuelian Xiao; Ruihong Sun; Lei Huang; Jian Xu (Biotechnology Letters, 2017)

Purification and sequence characterization of chondroitin sulfate and dermatan sulfate from fishes - Na Lin; Xiaoli Mo; Yang Yang; Hong Zhang (Glycoconjugate Journal, 2017)

Sodium P-Aminosalicylic Acid Improved Manganese-Induced Learning and Memory Dysfunction via Restoring the Ultrastructural Alterations and γ-Aminobutyric Acid Metabolism Imbalance in the Basal Ganglia - Chao-Yan Ou; Yi-Ni Luo; Sheng-Nan He; Xiang-Fa Deng; Hai-Lan Luo; Zong-Xiang Yuan; Hao-Yang Meng; Yu-Huan Mo; Shao-Jun Li; Yue-Ming Jiang (Biological Trace Element Research, 2017)

Patterns of SSR variation in bread wheat (Triticum aestivum L.) seeds under ex situ genebank storage and accelerated ageing - Yong-Bi Fu; Mo-Hua Yang; Carolee Horbach; Dallas Kessler; Axel Diederichsen; Frank M. You; Hong Wang (Genetic Resources and Crop Evolution, 2017)

Effects of different ratios of glucose to acetate on phosphorus removal and microbial community of enhanced biological phosphorus removal (EBPR) system - Ting Xie; Chuangrong Mo; Xiaoming Li; Jian Zhang; Hongxue An; Qi Yang; Dongbo Wang; Jianwei Zhao; Yu Zhong; Guangming Zeng (Environmental Science and Pollution Research, 2017)

A PCR survey of vector-borne pathogens in different dog populations from Turkey - Huanping Guo; Ferda Sevinc; Onur Ceylan; Mutlu Sevinc; Ege Ince; Yang Gao; Paul Franck Adjou Moumouni; Mingming Liu; Artemis Efstratiou; Guanbo Wang; Shinuo Cao; Mo Zhou; et al. (Acta Parasitologica, 2017)
In the present study, a total of 192 blood samples were collected from pet dogs, kennel dogs and shepherd dogs in Konya district, Turkey, and tested by specific PCR for the presence of vector-borne pathogens. Several pathogens were identified, most of which can cause substantial morbidity in dogs. PCR results revealed that 54 (28.1%) dogs were infected with one or more pathogens. Positive results were obtained for

Polygonatum stenophyllum improves menopausal obesity via regulation of lipolysis-related enzymes - Ji Eun Lee; Eun-Jung Kim; Mi Hye Kim; Jongki Hong; Woong Mo Yang (Journal of Natural Medicines, 2016)

Expression, secretion and bactericidal activity of type VI secretion system in Vibrio anguillarum - Lei Tang; Shu Yue; Gui-Yang Li; Jie Li; Xiao-Ran Wang; Shu-Fang Li; Zhao-Lan Mo (Archives of Microbiology, 2016)

Nitrogen-Fixing and Plant Growth-Promoting Ability of Two Endophytic Bacterial Strains Isolated from Sugarcane Stalks - Yong-Xiu Xing; Chun-Yan Wei; Yao Mo; Li-Tao Yang; Si-Liang Huang; Yang-Rui Li (Sugar Tech, 2016)

Inhibitory effects of Leonurus sibiricus on weight gain after menopause in ovariectomized and high-fat diet-fed mice - Jangseon Kim; Mi Hye Kim; You Yeon Choi; Jongki Hong; Woong Mo Yang (Journal of Natural Medicines, 2016)

Induction of 2n pollen with colchicine during microsporogenesis in Eucalyptus - Jun Yang; Pengqiang Yao; Yun Li; Jiyou Mo; Jianzhong Wang; Xiangyang Kang (Euphytica, 2016)

News sentiment to market impact and its feedback effect - Sheung Yin Kevin Mo; Anqi Liu; Steve Y. Yang (Environment Systems and Decisions, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Molecular characterization and alternative splicing of a MYB transcription factor gene in tumourous stem mustard and its response to abiotic stresses - Weina Wang; Quan Sun; Chaowei Cai; Can Yang; Xin Liu; Xiaohong He; Huaizhong Jiang; Jianchuan Mo; Yingfan Cai (Biologia, 2016)

Age polyethism drives community structure of the bacterial gut microbiota in the fungus‐cultivating termite O dontotermes formosanus - Hongjie Li; Carsten Dietrich; Na Zhu; Aram Mikaelyan; Bin Ma; Ruoxi Pi; Yu Liu; Mengyi Yang; Andreas Brune; Jianchu Mo (Environmental Microbiology, 2016)
Summary Fungus‐cultivating termites ( M acrotermitinae) possess an elaborate strategy of lignocellulose digestion. It involves a lignocellulose‐degrading fungal symbiont (genus T ermitomyces ), a diverse gut microbiota and a characteristic labour division in food processing. In this study, using pyrotag sequencing and electron microscopy, we analysed the bacterial microbiota in the hindgut of O dontotermes formosanus and its fungus comb to investigate the spatial organization, establishment and temporal succession of the bacterial communities colonizing specific microhabitats. Our results document strong differences between the communities at the hindgut epithelium and the luminal fluid of newly moulted, young and old worker termites. The differences in community structure were consistent with the density, morphology and spatial distribution of bacterial cells and the pools of microbial metabolites in the hindgut compartment, underlining that both gut development and the age‐specific changes in diet affect the composition and functional role of their gut microbiota. These findings provide strong support for the concept that changes in diet and gut environment are important determinants of community structure because they create new niches for microbial symbionts.

ADH and PDC genes involved in tannins coagulation leading to natural de-astringency in Chinese pollination constant and non-astringency persimmon (Diospyros kaki Thunb.) - Rongli Mo; Sichao Yang; Yanmei Huang; Wenxing Chen; Qinglin Zhang; Zhengrong Luo (Tree Genetics & Genomes, 2016)

Cotton S-adenosylmethionine decarboxylase-mediated spermine biosynthesis is required for salicylic acid- and leucine-correlated signaling in the defense response to Verticillium dahliae - Hui-Juan Mo; Yan-Xiang Sun; Xiao-Li Zhu; Xing-Fen Wang; Yan Zhang; Jun Yang; Gui-Jun Yan; Zhi-Ying Ma (Planta, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Effects of dietary rhubarb, Bacillus cereus, yeast polysaccharide, and florfenicol supplementation on growth, intestinal morphology, and immune responses of sea cucumber (Apostichopus japonicus) - Gang Yang; Xiangli Tian; Shuanglin Dong; Mo Peng; Dongdong Wang; Kai Zhang (Aquaculture International, 2016)

GOLPH3 Mediated Golgi Stress Response in Modulating N2A Cell Death upon Oxygen-Glucose Deprivation and Reoxygenation Injury - Ting Li; Hong You; Xiaoye Mo; Wenfang He; Xiangqi Tang; Zheng Jiang; Shiyu Chen; Yang Chen; Jie Zhang; Zhiping Hu (Molecular Neurobiology, 2016)

An Improved Solving Approach for Interval-Parameter Programming and Application to an Optimal Allocation of Irrigation Water Problem - Gaiqiang Yang; Ping Guo; Mo Li; Shiqi Fang; Liudong Zhang (Water Resources Management, 2016)

Removal efficiency of particulate matters at different underlying surfaces in Beijing - Jiakai Liu; Lichun Mo; Lijuan Zhu; Yilian Yang; Jiatong Liu; Dongdong Qiu; Zhenming Zhang; Jinglan Liu (Environmental Science and Pollution Research, 2016)

Mechanism and Regulation of Autophagy and Its Role in Neuronal Diseases - Zhiping Hu; Binbin Yang; Xiaoye Mo; Han Xiao (Molecular Neurobiology, 2015)

Spatial distribution of heavy metal accumulation in the sediments after dam construction - Moo Joon Shim; Yun Mo Yang; Da Yeon Oh; Soo Hyung Lee; Yi Yong Yoon (Environmental Monitoring and Assessment, 2015)

Cotton ACAULIS5 is involved in stem elongation and the plant defense response to Verticillium dahliae through thermospermine alteration - Huijuan Mo; Xingfen Wang; Yan Zhang; Jun Yang; Zhiying Ma (Plant Cell Reports, 2015)

Associations of hypoxia inducible factor-1α gene polymorphisms with susceptibility to digestive tract cancers: a case–control study and meta-analysis - Zhi-Hai Ni; Xian-Jun Liang; Jing-Gang Mo; Yi Zhang; Jian-Hua Liang; Yu-Sha Yang; Yong Zhou; Zhao-Hua Li; Jian-Liang Zhang; Yin-Lu Ding; Peng Zhang; Jin-Qing Wang (Genes & Genomics, 2015)

Characterization of the nuclear import and export signals of pseudorabies virus UL31 - Meili Li; Si Jiang; Jinlin Wang; Chuncong Mo; Zhancheng Zeng; Yanjia Yang; Chunke Chen; Xiaowei Li; Wei Cui; Jinlu Huang; Tao Peng; Mingsheng Cai (Archives of Virology, 2015)

Molecular characterization of a novel mycovirus from Rhizoctonia fumigata AG-Ba isolate C-314 Baishi - Yanqiong Li; Ping Xu; Lifang Zhang; Zhenyuan Xia; Xiyun Qin; Genhua Yang; Xiaohan Mo (Archives of Virology, 2015)

Duration-dependent regulation of autophagy by isoflurane exposure in aged rats - Zheng-Qian Li; Lun-Xu Li; Na Mo; Yi-Yun Cao; Bolati Kuerban; Yao-Xian Liang; Dong-Sheng Fan; De-Hua Chui; Xiang-Yang Guo (Neuroscience Bulletin, 2015)

Evaluation of 1-G Similitude Law in Predicting Behavior of a Pile-Soil Model - Jung-In Choi; Min-Taek Yoo; Eui-Kyu Yang; Jin-Tae Han; Myoung-Mo Kim (Marine Georesources & Geotechnology, 2015)

Association of IgE-mediated allergen sensitivity and promoter polymorphisms of chemokine (C–C motif) ligand 5 gene in Han Chinese patients with allergic skin diseases - Ji-Chang Zhou; Yu-mei Zhu; Zheng Chen; Shan He; Shi-jie Zheng; Jun-luan Mo; Xiao-li Liu; Chun-mei Gong; Bin Hou; Hui Yang (Genes & Genomics, 2015)

Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China - Liang Yu; Pingzheng Mo; Zeping Wei; Ruiling Fu; Mai Yang; Binying Ji; Jian Wang; Shu Li; Amie J. Strong; Neal Touzjian; Nicholas Kushner; Xi-En Gui; et al. (Infectious Diseases, 2015)

HCV J6/JFH1 Tilts the Capability of Myeloid-Derived Dendritic Cells to Favor the Induction of Immunosuppression and Th17-Related Inflammatory Cytokines - Zhong Fang; Kai Zhu; Nining Guo; Na Zhang; Mo Guan; Chunfu Yang; Qinsong Pan; Ruicheng Wei; Chunhui Yang; Chaoyang Deng; Xiaoqing Liu; Ping Zhao; et al. (Pharmaceutical Research, 2015)

Rapid and simultaneous detection of three major diarrhea-causing viruses by multiplex real-time nucleic acid sequence-based amplification - Qiu-Hua Mo; Hai-Bo Wang; Hui-Rong Dai; Ji-Can Lin; Hua Tan; Qi Wang; Ze Yang (Archives of Virology, 2015)

Complete nucleotide sequence of Klebsiella phage P13 and prediction of an EPS depolymerase gene - Anqi Shang; Yang Liu; Jianlei Wang; Zhaolan Mo; Guiyang Li; Haijin Mou (Virus Genes, 2015)

Quantification of bovine β-casein allergen in baked foodstuffs based on ultra-performance liquid chromatography with tandem mass spectrometry - Qi Chen; Jingshun Zhang; Xing Ke; Shiyun Lai; Baohua Tao; Jinchuan Yang; Weimin Mo; Yiping Ren (Food Additives & Contaminants: Part A, 2015)

Spatial distribution of heavy metal contamination in soils near a primitive e-waste recycling site - Sheng-Xiang Quan; Bo Yan; Fan Yang; Ning Li; Xian-Ming Xiao; Jia-Mo Fu (Environmental Science and Pollution Research, 2015)

Changes of Serum Osteocalcin, Calcium, and Potassium in a Rat Model of Type 2 Diabetes - Lin Xiao; Xian Mo Wang; Tao Yang; Ying Xiong; Zhong Gui Zhang; Jun Ding; Chen Xu; Chang Yuan Xiong (Cell Biochemistry and Biophysics, 2015)

The protective roles of S-adenosylmethionine decarboxylase (SAMDC) gene in melon resistance to powdery mildew infection - Changming Liu; Xiaoling Li; Ruiping Yang; Yanling Mo; Yongqi Wang; Feng Xian; Xian Zhang; Fei Wang (Horticulture, Environment, and Biotechnology, 2014)

The effects of different crossing-linking conditions of genipin on type I collagen scaffolds: an in vitro evaluation - Xiujie Zhang; Xueying Chen; Ting Yang; Naili Zhang; Li Dong; Shaoying Ma; Xiaoming Liu; Mo Zhou; Baoxing Li (Cell and Tissue Banking, 2014)

Metabolic engineering of Escherichia coli for poly(3-hydroxypropionate) production from glycerol and glucose - Qi Wang; Peng Yang; Mo Xian; Lu Feng; Jiming Wang; Guang Zhao (Biotechnology Letters, 2014)

Synthesis and insecticidal activities of N-(5-dehydroabietyl-1,3,4-thiadiazol-2-yl)-benzenesulfonamides - Fangyao Li; Qijin Mo; Wengui Duan; Guishan Lin; Bo Cen; Naiyuan Chen; Zhangqi Yang (Medicinal Chemistry Research, 2014)

Rapid development of tissue bank achieved by International Atomic Energy Agency (IAEA) Tissue Banking Programme in China - Yu-Min Zhang; Jian-Ru Wang; Nai-Li Zhang; Xiao-Ming Liu; Mo Zhou; Shao-Ying Ma; Ting Yang; Bao-Xing Li (Cell and Tissue Banking, 2014)

Porcine bone grafts defatted by lipase: efficacy of defatting and assessment of cytocompatibility - Naili Zhang; Mo Zhou; Yumin Zhang; Xusheng Wang; Shaoying Ma; Li Dong; Ting Yang; Lina Ma; Baoxing Li (Cell and Tissue Banking, 2014)

Gadolinium promoted proliferation in mouse embryo fibroblast NIH3T3 cells through Rac and PI3K/Akt signaling pathways - Liming Shen; Aochu Yang; Pengwei Yao; Xiaohong Sun; Cheng Chen; Cuiping Mo; Lei Shi; Youjiao Chen; Qiong Liu (BioMetals, 2014)

Study of GOLPH3: a Potential Stress-Inducible Protein from Golgi Apparatus - Ting Li; Hong You; Jie Zhang; Xiaoye Mo; Wenfang He; Yang Chen; Xiangqi Tang; Zheng Jiang; Ranran Tu; Liuwang Zeng; Wei Lu; Zhiping Hu (Molecular Neurobiology, 2014)

MicroRNAs Expression and Function in Cerebral Ischemia Reperfusion Injury - Yu Di; Yang Lei; Feng Yu; Fan Changfeng; Wang Song; Mo Xuming (Journal of Molecular Neuroscience, 2014)

Coffee consumption and prostate cancer risk: an updated meta-analysis - Yu Lu; Limin Zhai; Jie Zeng; Qiliu Peng; Jian Wang; Yan Deng; Li Xie; Cuiju Mo; Shi Yang; Shan Li; Xue Qin (Cancer Causes & Control, 2014)

Application of T-DNA activation tagging to identify glutamate receptor-like genes that enhance drought tolerance in plants - Guihua Lu; Xiping Wang; Junhua Liu; Kun Yu; Yang Gao; Haiyan Liu; Changgui Wang; Wei Wang; Guokui Wang; Min Liu; Guanfan Mao; Binfeng Li; et al. (Plant Cell Reports, 2014)

Properties of Klebsiella phage P13 and associated exopolysaccharide depolymerase - Yang Liu; Guiyang Li; Zhaolan Mo; Zihan Chai; Anqi Shang; Haijin Mou (Journal of Ocean University of China, 2014)

Intercomparison of microwave remote-sensing soil moisture data sets based on distributed eco-hydrological model simulation and in situ measurements over the North China Plain - Jianxiu Qiu; Xingguo Mo; Suxia Liu; Zhonghui Lin; Lihu Yang; Xianfang Song; Guangying Zhang; Vahid Naeimi; Wolfgang Wagner (International Journal of Remote Sensing, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Genome-wide scan on total serum IgE levels identifies no common variants in a healthy Chinese male population - Ming Liao; Dianchun Shi; Yao Wang; Kai Zhang; Xin Chen; Yong Gao; Aihua Tan; Qiang Xuan; Xiaobo Yang; Yanlin Hu; Xue Qin; Haiying Zhang; et al. (Immunogenetics, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Phylogenetic diversity of bacterial endophytes of Panax notoginseng with antagonistic characteristics towards pathogens of root-rot disease complex - Li Ma; Yong Hong Cao; Ming Hui Cheng; Ying Huang; Ming He Mo; Yong Wang; Jian Zhong Yang; Fa Xiang Yang (Antonie van Leeuwenhoek, 2013)

Towards Sustainable Integrated Watershed Ecosystem Management: A Case Study in Dingxi on the Loess Plateau, China - Liding Chen; Lei Yang; Wei Wei; Ziting Wang; Baoru Mo; Guojun Cai (Environmental Management, 2013)

Effect of C/N ratios on the performance of earthworm eco-filter for treatment of synthetics domestic sewage - Yong-Jun Zhao; Cheng Yan; Yin-Liang Li; Ji-Hua Li; Mo Yang; Er Nie; Zheng Zheng; Xing-Zhang Luo (Environmental Science and Pollution Research, 2012)

Genome-wide association study identifies TNFSF13 as a susceptibility gene for IgA in a South Chinese population in smokers - Chen Yang; Wang Jie; Yang Yanlong; Guo Xuefeng; Tan Aihua; Gao Yong; Lu Zheng; Zhang Youjie; Zhang Haiying; Qin Xue; Qin Min; Mo Linjian; et al. (Immunogenetics, 2012)

Polycyclic aromatic hydrocarbons in animal-based foods from Shanghai: bioaccessibility and dietary exposure - Ying-Xin Yu; Liang Chen; Dan Yang; Yu-Ping Pang; Shao-Huan Zhang; Xin-Yu Zhang; Zhi-Qiang Yu; Ming-Hong Wu; Jia-Mo Fu (Food Additives & Contaminants: Part A, 2012)

Correlation between serum CA724 and gastric cancer: multiple analyses based on Chinese population - Xin-Zu Chen; Wei-Ke Zhang; Kun Yang; Lan-Lan Wang; Jin Liu; Li Wang; Jian-Kun Hu; Bo Zhang; Zhi-Xin Chen; Jia-Ping Chen; Zong-Guang Zhou; Xian-Ming Mo (Molecular Biology Reports, 2012)

Equilibrium and kinetics of adsorption of phosphate onto iron-doped activated carbon - Zhengfang Wang; Er Nie; Jihua Li; Mo Yang; Yongjun Zhao; Xingzhang Luo; Zheng Zheng (Environmental Science and Pollution Research, 2012)

Overexpression of a histone H3K4 demethylase, JMJ15, accelerates flowering time in Arabidopsis - Hongchun Yang; Huixian Mo; Di Fan; Ying Cao; Sujuan Cui; Ligeng Ma (Plant Cell Reports, 2012)

Pseudomonas aeruginosa Inhibits the Growth of Cryptococcus Species - Antonella Rella; Mo Wei Yang; Jordon Gruber; Maria Teresa Montagna; Chiara Luberto; Yong-Mei Zhang; Maurizio Del Poeta (Mycopathologia, 2012)

Lysinibacillus mangiferahumi sp. nov., a new bacterium producing nematicidal volatiles - Ling-Ling Yang; Ying Huang; Jie Liu; Li Ma; Ming-He Mo; Wen-Jun Li; Fa-Xiang Yang (Antonie van Leeuwenhoek, 2012)

Hydrogen sulfide protects H9c2 cells against doxorubicin-induced cardiotoxicity through inhibition of endoplasmic reticulum stress - Xiu-Yu Wang; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Ai-Ping Lan; Zhan-Li Yang; Fen Hu; Pei-Xi Chen; Xin-Xue Liao; Jian-Qiang Feng (Molecular and Cellular Biochemistry, 2012)

Characterization of Imcrop, a Mutator-like MITE family in the rice genome - Young-Jun Mo; Ki-Young Kim; Woon-Chul Shin; Gun-Mi Lee; Jong-Cheol Ko; Jeong-Kwon Nam; Bo-Kyeong Kim; Jae-Kwon Ko; Yeisoo Yu; Tae-Jin Yang (Genes & Genomics, 2012)

Inhibition of ROS-activated ERK1/2 pathway contributes to the protection of H2S against chemical hypoxia-induced injury in H9c2 cells - Xiao-Bian Dong; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Xiu-Yu Wang; Ai-Ping Lan; Fen Hu; Pei-Xi Chen; Jian-Qiang Feng; Mei-Fen Zhang; Xin-Xue Liao (Molecular and Cellular Biochemistry, 2012)

Development of an electrochemical immunoassay for detection of gatifloxacin in swine urine - Jian Yi; Meng Meng; Zhong-qiu Liu; Jin-fang Zhi; Yuan-yang Zhang; Jing Xu; Ya-bin Wang; Jin-ting Liu; Ri-mo Xi (Journal of Zhejiang University-SCIENCE B, 2012)

Characterization of EmpA protease in Vibrio anguillarum M3 - Yifan Han; Zhaolan Mo; Peng Xiao; Bin Hao; Jie Li; Guanpin Yang (Journal of Ocean University of China, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Four new species of Orbiliaceae from Yunnan, China - H. Y. Su; Y. Zhang; H. O. Baral; X. Y. Yang; M. H. Mo; Y. H. Cao; M. H. Chen; Z. F. Yu (Mycological Progress, 2011)

Assessing the impact of climate change on potential evapotranspiration in Aksu River Basin - Shouhong Zhang; Suxia Liu; Xingguo Mo; Chang Shu; Yang Sun; Chun Zhang (Journal of Geographical Sciences, 2011)

The roles of ascorbic acid and glutathione in symptom alleviation to SA-deficient plants infected with RNA viruses - Shao-Dong Wang; Feng Zhu; Shu Yuan; Hui Yang; Fei Xu; Jing Shang; Mo-Yun Xu; Shu-Dan Jia; Zhong-Wei Zhang; Jian-Hui Wang; De-Hui Xi; Hong-Hui Lin (Planta, 2011)

Response of Camptotheca acuminata calli stimulated by mechanical vibration - Dali Kang; Hongli Zhang; Qingqian Zeng; Xiaolu Mo; Yusheng Wang; Depo Yang (Acta Physiologiae Plantarum, 2011)

Protection of CHO cells by transfer of survivin driven by ovarian-specific promoter OSP-2 - Chun-Hua Tu; Wei-Peng Liu; Mei Dong; Li-Ping Cai; Ya-Qin Mo; Dong-Zi Yang (Molecular Biology Reports, 2011)

Specific cellular immune responses in mice immunized with DNA, adeno-associated virus and adenoviral vaccines of Epstein-Barr virus-LMP2 alone or in combination - Zhan Wang; SongMei Yang; Ling Zhou; HaiJun Du; WuNing Mo; Yi Zeng (Science China Life Sciences, 2011)

CD133+CD44+ subgroups may be human small intestinal stem cells - Neng-Yi Hou; Kun Yang; Tie Chen; Xin-Zu Chen; Bo Zhang; Xian-Ming Mo; Jian-Kun Hu (Molecular Biology Reports, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

EseD, a Putative T3SS Translocon Component of Edwardsiella tarda, Contributes to Virulence in Fish and is a Candidate for Vaccine Development - Bo Wang; Zhao Lan Mo; Peng Xiao; Jie Li; Yu Xia Zou; Bin Hao; Gui Yang Li (Marine Biotechnology, 2010)

Isolation and characterization of Bacillus polyfermenticus isolated from Meju, Korean soybean fermentation starter - Ae-Young Mo; Bora Kwon; Seralathan Kamala-Kannan; Kui-Jae Lee; Byung-Taek Oh; Dae-Hyuk Kim; Moon-Sik Yang; Jin-Hyung Kim; Seung-Moon Park (World Journal of Microbiology and Biotechnology, 2010)

In vitro and in vivo anti-inflammatory effects of pegmatite - Wol Soon Jo; Kwang Mo Yang; Yoo Jin Choi; Chang Hwa Jeong; Kyoung Jin Ahn; Byung Hyouk Nam; Sang Wha Lee; Su Yeong Seo; Min Ho Jeong (Molecular & Cellular Toxicology, 2010)

Oligometastases confined one organ from colorectal cancer treated by SBRT - Jin-Kyu Kang; Mi-Sook Kim; Jin Ho Kim; Seong Yul Yoo; Chul Koo Cho; Kwang Mo Yang; Hyung Jun Yoo; Young Seok Seo; Dong Han Lee; Hae Jin Kang; Young Han Kim; Ui-Sup Shin (Clinical & Experimental Metastasis, 2010)

Identification and molecular characterization of a Brachypodium distachyon GIGANTEA gene: functional conservation in monocot and dicot plants - Shin-Young Hong; Sangmin Lee; Pil Joon Seo; Moon-Sik Yang; Chung-Mo Park (Plant Molecular Biology, 2010)

Effects of chitosan/collagen substrates on the behavior of rat neural stem cells - ZhaoYang Yang; LinHong Mo; HongMei Duan; XiaoGuang Li (Science China Life Sciences, 2010)

Polymorphisms in arsenic metabolism genes, urinary arsenic methylation profile and cancer - Chi-Jung Chung; Yu-Mei Hsueh; Chyi-Huey Bai; Yung-Kai Huang; Ya-Li Huang; Mo-Hsiung Yang; Chien-Jen Chen (Cancer Causes & Control, 2009)

Estimation of soybean rust uredospore terminal velocity, dry deposition, and the wet deposition associated with rainfall - Xun Li; XiaoBing Yang; JanYou Mo; TangXun Guo (European Journal of Plant Pathology, 2009)

Tropical Malaysians and temperate Koreans exhibit significant differences in sweating sensitivity in response to iontophoretically administered acetylcholine - Jeong-Beom Lee; Jun-Sang Bae; Takaaki Matsumoto; Hun-Mo Yang; Young-Ki Min (International Journal of Biometeorology, 2009)

Critical effect of VEGF in the process of endothelial cell apoptosis induced by high glucose - Zhonghan Yang; Xuehua Mo; Qing Gong; Qiuhui Pan; Xia Yang; Weibin Cai; Chaoyang Li; Jian-xing Ma; Yunshao He; Guoquan Gao (Apoptosis, 2008)

Arsenic exposure, urinary arsenic speciation, and the incidence of urothelial carcinoma: a twelve-year follow-up study - Yung-Kai Huang; Ya-Li Huang; Yu-Mei Hsueh; Mo-Hsiung Yang; Meei-Maan Wu; Shu-Yuan Chen; Ling-I Hsu; Chien-Jen Chen (Cancer Causes & Control, 2008)

Beneficial effects of cardiac rehabilitation and exercise after percutaneous coronary intervention on hsCRP and inflammatory cytokines in CAD patients - Young-Joo Kim; Young-Oh Shin; Jun-Sang Bae; Jeong-Beom Lee; Joo-Hyun Ham; Youn-Jung Son; Jung-Kyu Kim; Chul Kim; Byoung-Kwon Lee; Jae-Keun Oh; Timothy Othman; Young-Ki Min; et al. (Pflügers Archiv - European Journal of Physiology, 2008)

ZNF418, a novel human KRAB/C2H2 zinc finger protein, suppresses MAPK signaling pathway - Yongqing Li; Dan Yang; Yan Bai; Xiaoyang Mo; Wen Huang; Wuzhou Yuan; Zhaochu Yin; Yun Deng; Oleg Murashko; Yuequn Wang; Xiongwei Fan; Chuanbing Zhu; et al. (Molecular and Cellular Biochemistry, 2008)

Effects of exercises on biophoton emission of the wrist - Frédéric Laager; Sang-Hyun Park; Joon-Mo Yang; Wook Song; Kwang-Sup Soh (European Journal of Applied Physiology, 2008)

Analysis of functional properties of Lactobacillus acidophilus - Ruixiang Zhao; Junliang Sun; Haizhen Mo; Yang Zhu (World Journal of Microbiology and Biotechnology, 2007)

Effect of vinasse irrigation on the activity of three enzymes and agronomic characters at seedling stage of sugarcane - Wang Yi-Ding; Mo Yun-Chuan; Wang Wei-Hao; Li Yang-Rui; Ye Yan-Ping (Sugar Tech, 2006)

Deep geoelectrical structure in and around the southern Korean Peninsula by GDS study - Seokhoon Oh; Jun-Mo Yang; Duk Kee Lee; Byung-Doo Kwon; Seung-Hwan Chung; Yoonho Song; Kyung Duck Min; Masao Nakada; Toru Mogi; Heuisoon Lee (Geosciences Journal, 2006)

Prolonged residence of temperate natives in the tropics produces a suppression of sweating - Jun-Sang Bae; Jeong-Beom Lee; Takaaki Matsumoto; Timothy Othman; Young-Ki Min; Hun-Mo Yang (Pflügers Archiv - European Journal of Physiology, 2006)

Subcellular localization, expression patterns, SNPs and association analyses of the porcine HUMMLC2B gene - Huan L. Wang; Heng Wang; Zheng M. Zhu; Chen F. Wang; Meng J. Zhu; De L. Mo; Shu L. Yang; Kui Li (Molecular Genetics and Genomics, 2006)

Molecular analysis of early rice stamen development using organ-specific gene expression profiling - Xiao-Chun Lu; Hua-Qin Gong; Mo-Li Huang; Su-Lan Bai; Yang-Bo He; Xizeng Mao; Zhi Geng; Song-Gang Li; Liping Wei; Jie-Shuai Yuwen; Zhi-Hong Xu; Shu-Nong Bai (Plant Molecular Biology, 2006)

Detection of Two Fungal Biocontrol Agents against Root-knot Nematodes by RAPD Markers - Ming Liang Zhu; Ming He Mo; Zhen Yuan Xia; Yun Hua Li; Shu Jun Yang; Tian Fei Li; Ke Qin Zhang (Mycopathologia, 2006)

Sscp analysis of variations in haplotypes of citrus tristeza virus isolated from yuzu (Citrus junos) in geographically separate regions of Korea - Dae Hyun Kim; Hye Kyung Shim; Jae Wook Hyeon; Hyeog Mo Kwon; Kwang Sik Kim; Min Su Choi; Jin Kyung Lee; Dong Giun Kim; Ju Sung Yang; Suk Chan Lee (Journal of Plant Biology, 2006)

Complete nucleotide sequence and genome organization of a Chinese isolate of tobacco bushy top virus * - X. H. Mo; X. Y. Qin; J. Wu; C. Yang; J. Y. Wu; Y. Q. Duan; T. F. Li; H. R. Chen (Archives of Virology, 2003)

Longitudinal changes in Ca, Mg, Fe, Cu, and Zn in breast milk of women in Taiwan over a lactation period of one year - Te-Hsien Lin; Yuh-Jyh Jong; Chi-Hsiun chiang; Mo-Hsiung Yang (Biological Trace Element Research, 1998)